Precision Measurement of the Proton Flux in Primary Cosmic Rays from Rigidity 1 GV to 1.8 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration; Finch, Evan (Physical Review Letters, 2015)
A precise measurement of the proton flux in primary cosmic rays with rigidity (momentum/charge) from 1 GV to 1.8 TV is presented based on 300 million events. Knowledge of the rigidity dependence of the proton flux is important in understanding the origin, acceleration, and propagation of cosmic rays. We present the detailed variation with rigidity of the flux spectral index for the first time. The spectral index progressively hardens at high rigidities.
Keywords: dept.phy

Precision Measurement of the Longitudinal Double-Spin Asymmetry for Inclusive Jet Production in Polarized Proton Collisions at √𝑠=200 GeV - STAR Collaboration (Physical Review Letters, 2015)
We report a new measurement of the midrapidity inclusive jet longitudinal double-spin asymmetry, 𝐴𝐿⁢𝐿, in polarized 𝑝⁢𝑝 collisions at center-of-mass energy √𝑠=200 GeV. The STAR data place stringent constraints on polarized parton distribution functions extracted at next-to-leading order from global analyses of inclusive deep-inelastic scattering (DIS), semi-inclusive DIS, and RHIC 𝑝⁢𝑝 data. The measured asymmetries provide evidence at the 3⁢𝜎 level for positive gluon polarization in the Bjorken-𝑥 region 𝑥>0.05.
Keywords: dept.phy

Beam-energy-dependent two-pion interferometry and the freeze-out eccentricity of pions measured in heavy ion collisions at the STAR detector - STAR Collaboration (Physical Review C, 2015)
We present results of analyses of two-pion interferometry in Au+Au collisions at √𝑠𝑁𝑁=7.7, 11.5, 19.6, 27, 39, 62.4, and 200 GeV measured in the STAR detector as part of the BNL Relativistic Heavy Ion Collider Beam Energy Scan program. The extracted correlation lengths (Hanbury-Brown–Twiss radii) are studied as a function of beam energy, azimuthal angle relative to the reaction plane, centrality, and transverse mass (𝑚𝑇) of the particles. The azimuthal analysis allows extraction of the eccentricity of the entire fireball at kinetic freeze-out. The energy dependence of this observable is expected to be sensitive to changes in the equation of state. A new global fit method is studied as an alternate method to directly measure the parameters in the azimuthal analysis. The eccentricity shows a monotonic decrease with beam energy that is qualitatively consistent with the trend from all model predictions and quantitatively consistent with a hadronic transport model.
Keywords: dept.phy

Precision Measurement of the Helium Flux in Primary Cosmic Rays of Rigidities 1.9 GV to 3 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2015)
Knowledge of the precise rigidity dependence of the helium flux is important in understanding the origin, acceleration, and propagation of cosmic rays. A precise measurement of the helium flux in primary cosmic rays with rigidity (momentum/charge) from 1.9 GV to 3 TV based on 50 million events is presented and compared to the proton flux. The detailed variation with rigidity of the helium flux spectral index is presented for the first time. The spectral index progressively hardens at rigidities larger than 100 GV. The rigidity dependence of the helium flux spectral index is similar to that of the proton spectral index though the magnitudes are different. Remarkably, the spectral index of the proton to helium flux ratio increases with rigidity up to 45 GV and then becomes constant; the flux ratio above 45 GV is well described by a single power law.
Keywords: dept.phy

Antiproton Flux, Antiproton-to-Proton Flux Ratio, and Properties of Elementary Particle Fluxes in Primary Cosmic Rays Measured with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2016)
A precision measurement by AMS of the antiproton flux and the antiproton-to-proton flux ratio in primary cosmic rays in the absolute rigidity range from 1 to 450 GV is presented based on 3.49×1⁢05 antiproton events and 2.42×1⁢09 proton events. The fluxes and flux ratios of charged elementary particles in cosmic rays are also presented. In the absolute rigidity range ∼60 to ∼500 GV, the antiproton ¯𝑝, proton 𝑝, and positron 𝑒+ fluxes are found to have nearly identical rigidity dependence and the electron 𝑒− flux exhibits a different rigidity dependence. Below 60 GV, the (¯𝑝/𝑝), (¯𝑝/𝑒+), and (𝑝/𝑒+) flux ratios each reaches a maximum. From ∼60 to ∼500 GV, the (¯𝑝/𝑝), (¯𝑝/𝑒+), and (𝑝/𝑒+) flux ratios show no rigidity dependence. These are new observations of the properties of elementary particles in the cosmos.
Keywords: dept.phy

Precision Measurement of the Boron to Carbon Flux Ratio in Cosmic Rays from 1.9 GV to 2.6 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2016)
Knowledge of the rigidity dependence of the boron to carbon flux ratio (B/C) is important in understanding the propagation of cosmic rays. The precise measurement of the B/C ratio from 1.9 GV to 2.6 TV, based on 2.3 million boron and 8.3 million carbon nuclei collected by AMS during the first 5 years of operation, is presented. The detailed variation with rigidity of the B/C spectral index is reported for the first time. The B/C ratio does not show any significant structures in contrast to many cosmic ray models that require such structures at high rigidities. Remarkably, above 65 GV, the B/C ratio is well described by a single power law 𝑅Δ with index Δ=−0.333±0.014⁢(fit)±0.005⁢(syst), in good agreement with the Kolmogorov theory of turbulence which predicts Δ=−1/3 asymptotically.
Keywords: dept.phy

Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed

Revisiting Intensity Interferometry Using Picosecond Timescale Resolution - Camarata, Matthew A.; Horch, E. P. (Bulletin of the American Astronomical Society, 2011)
After the success of Hanbury Brown, Davis, and their collaborators in measuring all stellar diameters resolvable by the 166-m interferometer at Narrabri nearly four decades ago, research into optical intensity interferometry was largely discontinued. Signal-to-noise ratios and timing resolutions limited the technique to relatively bright stars over a narrow bandwidth. Modern photon-correlation electronics, however, may help to revive the technique, allowing for increased temporal resolution and longer baselines. In this paper, the PicoHarp 300 Time-Correlated Single Photon Counting System is characterized in order to demonstrate its ability to perform interferometric measurements. Time correlations of coherent and incoherent source apertures are measured and their autocorrelations compared with theory. The speed of light is also directly measured using the shift in temporal correlation between offset detectors. Finally, the possibility of two independent systems, linked between two large-aperture telescopes, is discussed with the goal of determining whether longer baselines can be achieved.
Keywords: dept.phy; ⛔ No DOI found

Optimizing Speckle Data Reduction for Analysis of Faint Sources - Gaulin, Joseph; Horch, E.; Howell, S.; Ciardi, D. (American Astronomical Society, AAS Meeting, 2011)
Electron-multiplying CCD cameras are now being widely used in speckle imaging, and have been shown to deliver excellent photometric precision under good observing conditions. Successful image reconstructions have been made on binary stars fainter than 14th magnitude. However, improving the speckle signal-to-noise ratio and the fidelity of image reconstructions for faint sources would be extremely helpful in several areas of research where diffraction-limited images are required, including our own ongoing speckle observations of Kepler exoplanet candidate stars using the WIYN Telescope at Kitt Peak. In this paper, we investigate (1) robust cosmic ray rejection and (2) removal of low signal-to-noise frames as two ways to maximize data quality for faint source observations. Cosmic ray rejection is not normally a major concern in speckle imaging due to the brightness of the targets traditionally observed and the short frame times. Nonetheless, when imaging faint targets, more frames are needed to achieve a given signal-to-noise ratio, increasing the chance of cosmic ray events on the detector, and even a single cosmic ray hit in the frame sequence can significantly affect the source detection ability and photometry obtained in the observation. Similarly, faint sources often exhibit some frames with a well-defined image core while in other frames it is difficult to tell if the source is even present, primarily due to seeing variation during the observation. A new speckle reduction algorithm has been created that removes cosmic rays without throwing out frames and rejects frames with bad seeing, and its performance is investigated to determine to what extent this can improve source detection and photometric reliability in the final reconstructed image. Funding for this work was provided by the Kepler Science Center and by NSF Grant AST-0908125.
Keywords: dept.phy

Minor Planet Observations with the Differential Speckle Survey Instrument - Bouvier, Jean-Claude; Horch, E. (American Astronomical Society, AAS Meeting, 2011)
The Differential Speckle Survey Instrument (DSSI) is a dual-channel speckle imaging system that takes speckle patterns in two colors simultaneously using two electron-multiplying CCD cameras. The system has been shown to deliver excellent photometry of binary stars under good observing conditions, which raises the question of whether results of similar quality can be obtained on extended objects such as minor planets, and if so, to what limiting magnitude. In this study, we present speckle image reconstructions of images of 2 Pallas, 216 Kleopatra, and 283 Emma made from data taken at the WIYN 3.5-m Telescope at Kitt Peak. We compare two different phase reconstruction algorithms: (1) an iterative technique, and (2) a relaxation technique. Since Pallas is a flattened disk, Kleopatra has a dumbbell shape, and Emma is a binary asteroid with known orbital parameters, these three targets represent three distinct image morphologies that allow for a robust comparison of the two phase reconstruction programs. Prospects for future work in this area with DSSI are discussed. This work is funded by NSF grant AST-0908125.
Keywords: dept.phy

High-Resolution Speckle Imaging at Gemini-North: Exoplanets and Beyond - Howell, Steve B.; Horch, E.; Everett, M. E.; Ciardi, D. (American Astronomical Society, AAS Meeting, 2013)
Using our state-of-the-art 2-channel speckle imaging instrument, we have recently obtained diffraction-limited optical images at the 8-m Gemini-N telescope. The primary science goal was to search for faint (delta_mag = 4-6 mag) and nearby (<0.05") stellar companions around potential planet hosting stars as part of the small small exoplanet validation for the NASA Kepler and ESA CoRoT missions. As a demonstration of the instrument capabilities on Gemini, we achieved an angular resolution of ~20 mas which yielded the highest resolution ground-based optical image of the Pluto-Charon system ever obtained. Our instrument is likely to return to Gemini-N in mid-2013 for observations by general community programs
Keywords: dept.phy

The Relation Between Radius, Mass, and Incident Flux of Exoplanets - Weiss, Lauren M.; Marcy, G. W.; Rowe, J.; Isaacson, H. T.; Howard, A.; Fortney, J. J.; Miller, N.; Demory, B.; Fischer, D.; Adams, E. A.; Dupree, A. K.; Howell, S. B.; et al. (American Astronomical Society, AAS Meeting, 2013)
We measure the mass of a modestly irradiated giant or "warm Jupiter," KOI-94d, in order to calculate its density. We wish to determine whether this planet, which is in a 22 day orbit and receives 107 times as much incident flux as the Earth, is bloated like "hot Jupiters" or as dense as our own Jupiter. In addition to its warm Jupiter, KOI-94 hosts at least 3 smaller planets, all of which were detected through transits by the Kepler Mission. This presents the opportunity to characterize a multi-planet system and to test dynamic stability and formation theory through observations of the masses and orbital elements of these planets. With 26 radial velocity measurements of KOI-94 from the W. M. Keck Observatory/HIRES, we measure the mass of the giant planet and upper limits to the masses of the three smaller planets. Transit timing variations will allow us to hone the mass measurements of the three smaller planets. Using the KOI-94 system and all other planets with published values for both mass and radius, we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to ten Jupiter masses: log(Rp/RE) = 0.007 + 0.53 log(M/ME) - 0.001 log(F/[erg/s/cm^2]) for Mp < 150ME; log(Rp/RE) = 0.67 - 0.036 log(M/ME) + 0.06 log(F/[erg/s/cm^2]) for Mp > 150ME. We also solve these planes in density-mass-flux space: log(ρp/[g/cm^3]) = 0.69 - 0.57 log(M/ME) + 0.02 log(F/[erg/s/cm^2]) for Mp < 150ME; log(ρp/[g/cm^3]) = -1.23 + 1.10 log(M/ME) - 0.18 log(F/[erg/s/cm^2]) for Mp > 150ME.
Keywords: dept.phy

Exoplanet Characterization by Proxy for Kepler-61b: How a Nearby Star Bumped a Planet Out of the Habitable Zone - Ballard, Sarah; Charbonneau, D.; Fressin, F.; Torres, G.; Irwin, J.; Desert, J.; Ciardi, D.; Crepp, J. R.; Henze, C.; Bryson, S.; Howell, S. B.; Horch, E.; et al. (American Astronomical Society, AAS Meeting, 2013)
We present the validation and characterization of Kepler-61b: a 2.5 R_Earth planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon our identification of a spectroscopically similar star located 4.9 pc from Earth. This proxy star to Kepler-61 has a published direct interferometric radius and effective temperature measurement, which we apply in tandem with the Kepler photometry to characterize the planet Kepler-61b. The technique of identifying a nearby proxy star with directly measured properties allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had profound implications for the putative habitability of Kepler-61b. This work was performed in part under contract with the California Institute of Technology (Caltech) funded by NASA through the Sagan Fellowship Program
Keywords: dept.phy

Validation of Twelve Small Kepler Transiting Planets in the Habitable Zone - Caldwell, Douglas A.; Torres, Guillermo; Kipping, David M.; Ballard, Sarah; Batalha, Natalie; Borucki, William J.; Bryson, Steve; Ciardi, David R.; Crepp, Justin R.; Everett, Mark; Fressin, Francois; Henze, Christopher; et al. (American Astronomical Society, AAS Meeting, 2015)
We report on the work to validate twelve candidate-transiting planets from Kepler with orbital periods ranging from 34 to 207 days initially identified in the pipeline search of three years of Kepler data from quarters 1 to 12. The candidates were selected based on pipeline Data Validation models indicating that they are small and potentially in the habitable zone (HZ) of their parent stars. As their expected Doppler signals are too small for a direct measure of their masses, we verify their planetary nature by validating them statistically using the BLENDER technique. BLENDER simulates large numbers of false-positive scenarios and compares the resulting light curves with the Kepler photometry, taking into account additional information from the analysis of Kepler flux centroids and new follow-up observations, including high-resolution optical and NIR spectroscopy, adaptive optics imaging, and speckle imaging. For eleven of the candidates we show that the likelihood they are true planets is far greater than that of a false positive, to a 99.73% confidence level. For the twelfth candidate, the planet confidence level is about 99.2%. Using improved stellar parameters for the host stars, we derive planetary radii ranging from 1.12 to 2.73 R⊕. All twelve objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of the candidates that have been previously validated by others, our study doubles the number of known potentially rocky planets in the HZ.
Keywords: dept.phy

Stellar Multiples Among the KOIs - Alyse Hirsch, Lea; Everett, Mark; Ciardi, David; Furlan, Elise; Horch, Elliott; Howell, Steve; Teske, Johanna; Marcy, Geoffrey W. (Bulletin of the American Astronomical Society, 2015)
We examine high-resolution follow-up imaging data for 84 KOIs with stellar companions detected within 2”. These stars were observed in the optical using speckle interferometry (Gemini/DSSI or WIYN/DSSI) and/or in the near-infrared with adaptive optics imaging (Keck/NIRC2, Palomar/PHARO, or Lick/IRCAL), and all have imaging results in at least two filters. Their companions are all unresolved in the Kepler images, and fall on the same pixel of the Kepler detector; thus the planet radii calculated for planet candidates in these systems are subject to upward revision due to contamination of the target star’s light by the stellar companion. We calculate updated planet radii for these 84 planet candidates, assuming the planet orbits the brighter of the two stars. We also use isochrone models and distance estimates to assess the likelihood that the companion is bound. This analysis complements galaxy models that determine the probability of a chance alignment of a background star for each system (Everett et al., in prep.). Together, these data allow us to isolate a sub-population of Kepler planets and planet candidates that reside in physical binary systems, for comparison to the wider Kepler planet population.
Keywords: dept.phy; ⛔ No DOI found

Twinkle Twinkle Little Star - Speckle Imaging for Exoplanet Characterization - Howell, Steve B.; Scott, Nic; Horch, Elliott (American Astronomical Society, AAS Meeting, 2016)
The NASA K2 mission is finding many high-value exoplanets and world-wide follow-up is ensuing. The NASA TESS mission will soon be launched, requiring additional ground-based observations as well. As a part of the NASA-NSFNN-EXPLORE program to enable exoplanet research, our group is building two new speckle interferometry cameras for the Kitt Peak WIYN 3.5-m telescope and the Gemini-N 8-m telescope. Modeled after the successful DSSI visitor instrument that has been used at these telescopes for many years, speckle observations provide the highest resolution images available today from any ground- or space-based single telescope. They are the premier method through which small, rocky exoplanets can be validated. Available for public use in early 2017, WIYNSPKL and GEMSPKL will obtain simultaneous images in two filters with fast EMCCD readout, "speckle" and “wide-field” imaging modes, and user support for proposal writing, observing, and data reduction. We describe the new cameras, their design, and their benefits for exoplanet follow-up, characterization, and validation. Funding for this project comes from the NASA Exoplanet Exploration Program and NASA HQ.

Speckle Interferometry at Lowell's Discovery Channel Telescope - van Belle, Gerard; Horch, Elliott (American Astronomical Society, AAS Meeting, 2017)
The high-spatial-resolution technique of speckle interferometry has been in use at Lowell Observatory's Discovery Channel Telescope since 2014 with the Dual-channel Stellar Speckle Imager (DSSI; Horch et al. 2009) as a visiting instrument. Using its standard bandpasses of 692 and 880nm, we have used highly efficient DSSI instrument to inspect over a thousand stellar systems over the course of 2014 (Horch et al. 2015). We have also demonstrated the usefulness of the DSSI@DCT system for resolved observations of high-altitude (>1,000 miles) man-made satellites in highly non-sidereal rate orbits.

Instruments at the Lowell Observatory Discovery Channel Telescope (DCT) - Jacoby, George H.; Bida, Thomas A.; Fischer, Debra; Horch, Elliott; Kutyrev, Alexander; Mace, Gregory N.; Massey, Philip; Roe, Henry G.; Prato, Lisa A. (American Astronomical Society, AAS Meeting, 2017)
The Lowell Observatory Discovery Channel Telescope (DCT) has been in full science operation for 2 years (2015 and 2016). Five instruments have been commissioned during that period, and two additional instruments are planned for 2017. These include:+ Large Monolithic Imager (LMI) - a CCD imager (12.6 arcmin FoV)+ DeVeny - a general purpose optical spectrograph (2 arcmin slit length, 10 grating choices)+ NIHTS - a low resolution (R=160) YJHK spectrograph (1.3 arcmin slit)+ DSSI - a two-channel optical speckle imager (5 arcsec FoV)+ IGRINS - a high resolution (45,000) HK spectrograph, on loan from the University of Texas.In the upcoming year, instruments will be delivered from the University of Maryland (RIMAS - a YJHK imager/spectrograph) and from Yale University (EXPRES - a very high resolution stabilized optical echelle for PRV).Each of these instruments will be described, along with their primary science goals.
Keywords: dept.phy

K-KIDS: Companioins to K Dwarfs Within 50 Parsecs - Nusdeo, Daniel Anthony; Winters, Jennifer; Paredes-Alvarez, Leonardo; Horch, Elliott; Jao, Wei-Chun; Henry, Todd J.; RECONS Institute (American Astronomical Society, AAS Meeting, 2017)
How many K dwarfs have “kids?” Stellar multiplicity fractions have been obtained for most spectral types, most recently by Raghavan et al. (2010) and Winters et al. (2015), finding rates of 50% for solar-type stars and 27% for M dwarfs, respectively. These findings will be crucial to improving our understanding of solar-system formation, but there has not yet been a statistically significant survey for K dwarfs to bridge the gap between G and M stars. To create a sample for a robust multiplicity survey, an initial set of 1048 K dwarfs was built using the Hipparcos and 2MASS catalogs, the companions of which are called “K-KIDS.” Future releases from Gaia will help us to expand K-KIDS into a volume-complete sample out to 50-pc, and we project that the final sample will contain over 3000 stars, making this the largest volume-complete multiplicity survey ever undertaken. For observational purposes, the targeted K dwarfs are confined equatorially to -30 < DEC < +30 to ensure all stars are observable from either hemisphere. The survey for K-KIDS is split into three companion-separation regimes: small (0.02 - 2.00 arcseconds), medium (2.00 - 10.00 arcseconds), and distant (10.00+ arcseconds). Small separation companions are resolved using the Differential Speckle Survey Instrument, with which we have observed 964 out of 1048 systems to date, already finding 135 new K-KIDS. Medium separation companions are observed via a series of three observations per star at the CTIO 0.9-m telescope, integrating for 3, 30, and 300 seconds to reveal companions of various brightnesses. Finally, a common proper-motion search is used to find companions at distant separations via blinking of digitialized images in the SuperCOSMOS archive, in addition to a large-scale literature survey for previously-discovered multiples. The small and distant surveys are nearing completion, and continued progress on the medium survey ensures that a statistically significant multiplicity rate for K dwarfs will soon be in achieved. Furthermore, a new RV survey is planned using the CHIRON high-resolution spectrograph to find companions that cannot be directly imaged. This effort has been supported by the NSF through grants AST-1412026 and AST-1517413.
Keywords: dept.phy

Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy

Sixteen Years of Speckle Interferometry at the WIYN Observatory - Van Altena, Wm. F.; Horch, Elliott; Casetti-Dinescu, Dana I. (American Astronomical Society, 2017)
Speckle interferometry at Yale started in 1994 with a three-year program of observations at the Yale Southern Observatory at El Leoncito, Argentina. After this experience, we began a long-term program of speckle observations at the WIYN 3.5-m telescope at Kitt Peak National Observatory, first using a MAMA detector, then CCD and finally EMCCD technology. We describe the evolution of the program, its main results in terms of discovered components, orbital parameters and masses. While the Yale program ended in 2013, it provided the springboard for continued speckle efforts at WIYN, the Discovery Channel 4.3-m Telescope, and the Gemini 8.1-m Telescopes for binary star research, exoplanet science, and other projects. An important outcome of this research will be the incorporation of the soon to be released high-precision Gaia parallaxes into our observations.

Fundamental Stellar Parameters and Multiplicity Rates of M-Dwarfs through Optical Speckle and NIR AO Imaging - Hahne, Frederick; Horch, Elliott; Ciardi, David R.; van Belle, Gerard; Clark, Catherine; Winters, Jennifer; Henry, Todd J. (Bulletin of the American Astronomical Society, 2019)
We present preliminary fundamental stellar parameters and multiplicity rates of M dwarf stars using a combination of speckle imaging and adaptive optics. Our survey mainly uses the Differential Speckle Survey Instrument (DSSI) at Lowell Observatory's Discovery Channel Telescope (DCT). DSSI observes speckle patterns simultaneously at two separate wavelengths and the data for this project are composed of observations which span from 2016 to 2018. More recently, the speckle data for some of the target stars that have been found to be binary have been supplemented with observations using Adaptive Optics (AO) at Palomar Observatory. The combination of speckle data in the visible and AO data in the near-infrared allows us to make robust determinations of the luminosities and effective temperatures of the components in each case. Using the known Mass-Luminosity Relation, we also estimate the component masses. A discussion of interesting systems will be given.
Keywords: dept.phy; ⛔ No DOI found

Understanding the Multiplicity of TESS Exoplanet Host Candidates - Clark, Catherine; van Belle, Gerard; Horch, Elliott; von Braun, Kaspar (Bulletin of the American Astronomical Society, 2019)
While at first glance multi-star systems seem quite extreme, they are in fact the most common type of star system in our galaxy, throughout the stellar mass distribution. In particular, 40 to 50% of exoplanet host stars reside within multiple star systems. Given the degree to which initially undetected multiplicity has skewed Kepler results, high-resolution imaging of our nearby low-mass neighbors is necessary for both accurate characterization of transiting exoplanets, as well as a better understanding of stellar astrophysics. To address this frequent gap in our knowledge of exoplanet hosts, we will utilize speckle interferometry to directly image TESS exoplanet host candidates to complete our knowledge of individual star multiplicity. Our investigation will expand upon the speckle observations taken as a part of the POKEMON speckle survey of nearby M-dwarfs to better constrain the multiplicity of low-mass TESS exoplanet host candidates, and to constrain M-dwarf multiplicity by subtype across the entire M-dwarf sequence.
Keywords: dept.phy; ⛔ No DOI found

Exoplanet Host Star Characterization with QWSSI - van Belle, Gerard; Clark, Catherine; Horch, Elliott; Trilling, David (Bulletin of the American Astronomical Society, 2019)
QWSSI, the Quad-camera Wavefront-Sensing Speckle Imager, is a next-generation speckle imager that is being developed for Lowell Observatory's 4.3-meter Discovery Channel Telescopes. The principle behind QWSSI is to extend the capabilities of the speckle camera currently resident at Lowell, the Differential Speckle Survey Instrument (DSSI), in two ways. First, while DSSI currently observes in two visible channels, QWSSI will simultaneously observe in six narrow-band channels: four in the visible (0.5-0.9um), and one each in J- and H-band (1.2 and 1.6um). Second, the visible light unused for speckle imaging is carefully preserved and feeds a wavefront sensor (WFS), which is also run simultaneously with the speckle imaging. Simulations by Löbb (2016) indicate WFS data will provide significant gains in exploring stellar multiplicity, with marked improvements in primary-secondary contrast ratios and inner working angle (Horch et al. 2018). QWSSI will also be mountable on one of the three 1-meter telescopes being installed on the NPOI Array for engineering tests and preliminary science observations. QWSSI will expand on the already considerable exoplanetary work of the speckle imagers DSSI, NESSI (@ WIYN), Alopeke (Gemini-N), and Zorro (Gemini-S), improving the discovery space for existing targets, as well opening up new regions of that discovery space with its NIR channels.
Keywords: dept.phy; ⛔ No DOI found

Speckle Imaging at Gemini and the DCT - Horch, E. P.; Löbb, J.; Howell, S. B.; van Altena, W. F.; Henry, T. J.; van Belle, G. T. (Revista Mexicana de Astronomía y Astrofísica, 2018)
A program of speckle observations at Lowell Observatory's Discovery Channel Telescope (DCT) and the Gemini North and South Telescopes will be described. It has featured the Differential Speckle Survey Instrument (DSSI), built at Southern Connecticut State University in 2008. DSSI is a dual-port system that records speckle images in two colors simultaneously and produces diffraction limited images to V∼ 16.5 mag at Gemini and V∼ 14.5 mag at the DCT. Of the several science projects that are being pursued at these telescopes, three will be highlighted here. The first is high-resolution follow-up observations for Kepler and K2 exoplanet missions, the second is a study of metal-poor spectroscopic binaries in an attempt to resolve these systems and determine their visual orbits en route to making mass determinations, and the third is a systematic survey of nearby late-type dwarfs, where the multiplicity fraction will be directly measured and compared to that of G dwarfs. The current status of these projects is discussed and some representative results are given.
Keywords: binaries: visual; dept.phy; techniques: high angular resolution; techniques: interferometric; techniques: photometric; ⛔ No DOI found

An Optical System for Multi-wavelength Intensity Interferometry with the Southern Connecticut Stellar Interferometer - Dever, Matthew; Horch, Elliott (Bulletin of the American Astronomical Society, 2019)
The Southern Connecticut Stellar Interferometer is an astronomical intensity interferometer consisting of two telescopes. Each is currently equipped with a single-photon avalanche diode (SPAD) detector, and an ultra-fast timing module correlates counts between both photon detectors. The interferometer has previously demonstrated intensity correlations using the 1-pixel SPADs and extremely narrow band pass filters but was limited in the amount of light that could be collected, and therefore the signal-to-noise ratio that could be achieved. SCSU's recent acquisition of an 8-pixel SPAD detector has allowed for a new possibility: a different wavelength of light could be directed towards each of the 8 pixels of the detector, thus conducting 8 independent intensity interferometry experiments at the same time, if this could be implemented at both telescopes. Using materials and resources available in the Astronomical Instrumentation Laboratory at Southern Connecticut State University, an optical system has been developed to work toward this goal but outfitting the first telescope in this way. The light from the telescope is collimated and directed toward a reflective diffraction grating. This is then re-imaged using a second lens and directed onto the pixels of the photon detector. These optical components have been placed inside an aluminum housing and can be mounted to the telescope for test observations. A status report will be given on the observations so far. If this can be replicated at the other telescope, the signal-to-noise ratio achievable with the instrument could be improved by a factor of 2.8.
Keywords: ⛔ No DOI found

A Theoretical Study of Correlated Electron in the Frustrated Hubbard Model: Summary Report: Sabbatical Leave Spring 2010 - Enjalran, Matthew (2010)
This sabbatical leave was devoted to conducting theoretical, computational studies of correlated electrons with frustrated interactions and focus on the Hubbard model on the two-dimensional triangular and kagome lattices. Secondly, two Quantum Monte Carlo (QMC) methods were developed and applied to the models of the constrained path/phase QMC, and the determinant QMC methods.
Keywords: dept.phy; faculty_collection; sabbatical_report

An inquiry-based course in nano-photonics - Broadbridge, C.; Calvert, J.; Donnelly, J.; Garofano, J.; Massa, N. (2010)
We developed a curriculum to introduce nanotechnology and photonics concepts to community college students enrolled in a program designed to attract and retain students in technology associate degree programs. Working with the Center for Research on Interface Structures and Phenomena, an NSF Materials Research Science and Engineering Center, and the PHOTON projects, funded by the Advanced Technological Education program of NSF, we developed hands-on, inquiry-based activities to address the course goals: improve critical thinking, introduce science and technology concepts common to technology programs and provide opportunity to practice math skills in context. © 2010 SPIE.
Keywords: Advanced Technological Education; Associate degree; Community college; Critical thinking; Curricula; Education; Inquiry; Interface structures; Materials research; Math skills; Nano-photonics; Nanotechnology; Photonics; Science and Technology; Science and engineering; Students; Technology programs; dept.phy

Interface-induced polarization and inhibition of ferroelectricity in epitaxial SrTiO3/Si - Kolpak, A.M.; Walker, F.J.; Reiner, J.W.; Segal, Y.; Su, D.; Sawicki, M.S.; Broadbridge, C.C.; Zhang, Z.; Zhu, Y.; Ahn, C.H.; Ismail-Beigi, S. (Physical Review Letters, 2010)
We use SrTiO3/Si as a model system to elucidate the effect of the interface on ferroelectric behavior in epitaxial oxide films on silicon. Using both first-principles computations and synchrotron x-ray diffraction measurements, we show that structurally imposed boundary conditions at the interface stabilize a fixed (pinned) polarization in the film but inhibit ferroelectric switching. We demonstrate that the interface chemistry responsible for these phenomena is general to epitaxial silicon-oxide interfaces, impacting on the design of silicon-based functional oxide devices. © 2010 The American Physical Society.
Keywords: Epitaxial films; Epitaxial silicon; Ferroelectric behavior; Ferroelectric films; Ferroelectric switching; Ferroelectricity; First-principles; Functional oxides; Induced polarization; Interface chemistry; Mathematical models; Model system; Oxide films; Polarization; Semiconducting silicon compounds; Silicon oxides; Silicon-based; SrTiO; Strontium alloys; Synchrotron x ray diffraction; X ray diffraction; dept.phy

Probing three-dimensional surface force fields with atomic resolution: Measurement strategies, limitations, and artifact reduction - Baykara, M.Z.; Dagdeviren, O.E.; Schwendemann, T.C.; Mönig, H.; Altman, E.I.; Schwarz, U.D. (Beilstein Journal of Nanotechnology, 2012)
Noncontact atomic force microscopy (NC-AFM) is being increasingly used to measure the interaction force between an atomically sharp probe tip and surfaces of interest, as a function of the three spatial dimensions, with picometer and piconewton accuracy. Since the results of such measurements may be affected by piezo nonlinearities, thermal and electronic drift, tip asymmetries, and elastic deformation of the tip apex, these effects need to be considered during image interpretation. In this paper, we analyze their impact on the acquired data, compare different methods to record atomic-resolution surface force fields, and determine the approaches that suffer the least from the associated artifacts. The related discussion underscores the idea that since force fields recorded by using NC-AFM always reflect the properties of both the sample and the probe tip, efforts to reduce unwanted effects of the tip on recorded data are indispensable for the extraction of detailed information about the atomicscale properties of the surface. © 2012 Baykara et al.
Keywords: Artifact reduction; Atomic force microscopy; Atomic scale; Atomic-resolution; Elasticity; Electronic drift; Force fields; Force spectroscopy; Image interpretation; Interaction forces; Measurement strategies; NC-AFM; Noncontact atomic force microscopy; Probe tips; Spatial dimension; Surface forces; Three dimensional; Three-dimensional atomic force microscopy; Three-dimensional surface; Tip apex; Tip asymmetry; Tip elasticity; dept.phy

The effectiveness of multimedia and activity-based supplemental teaching resources in materials science education - Day, D.A.; Abbasi, E.; Liang, B.; Bhat, S.; DeMeo, S.; Garofano, J.; Grober, L.; Ferrari, N.; Broadbridge, C. (2012)
A comparative study investigating the integration of supplemental teaching resources in materials science education was developed for the purpose of determining the effectiveness of teaching strategies. Digital stories created by students, excerpts from the Nova Making Stuff documentaries, YouTube educational videos and student generated demo-kits were used as part of the investigation whereby two 9th grade science classes (n∼26) were evaluated. Each participant in the study received one period (40-min) of a traditional lesson on Materials Science including specific content, vocabulary, and a pre- and post- lesson assessment. Additionally, the students in each class participated in a 30-min supplemental component, e.g. video or activity-based demonstration using aforementioned kits or video compilation. Pre- and post- evaluations (e.g. open-ended and likert questions) were administered to all of the participants. As hypothesized, the students' feedback and performance on assessment activities reveal that the use of multimedia and activity-based resources may be equally effective teaching methods as traditional methods. © 2012 Materials Research Society.
Keywords: Activity-based; Assessment activities; Comparative studies; Educational videos; Effective teaching methods; Materials science; Multimedia systems; Students; Teaching resources; Teaching strategy; YouTube; dept.phy

Speckle camera imaging of the planet Pluto - Howell, S.B.; Horch, E.P.; Everett, M.E.; Ciardi, D.R. (Publications of the Astronomical Society of the Pacific, 2012)
We have obtained optical wavelength (692 nm and 880 nm) speckle imaging of the planet Pluto and its largest moon Charon. Using our DSSI speckle camera attached to the Gemini North 8 m telescope, we collected high resolution imaging with an angular resolution of ~20 mas, a value at the Gemini-N telescope diffraction limit. We have produced for this binary system the first speckle reconstructed images, from which we can measure not only the orbital separation and position angle for Charon, but also the diameters of the two bodies. Our measurements of these parameters agree, within the uncertainties, with the current best values for Pluto and Charon. The Gemini-N speckle observations of Pluto are presented to illustrate the capabilities of our instrument and the robust production of high accuracy, high spatial resolution reconstructed images. We hope our results will suggest additional applications of high resolution speckle imaging for other objects within our solar system and beyond. © 2012. The Astronomical Society of the Pacific. All rights reserved.
Keywords: dept.phy; peer-reviewed

Atom-specific forces and defect identification on surface-oxidized Cu(100) with combined 3D-AFM and STM measurements - Baykara, M.Z.; Todorović, M.; Mönig, H.; Schwendemann, T.C.; Ünverdi, O.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (Physical Review B - Condensed Matter and Materials Physics, 2013)
The influence of defects on the local structural, electronic, and chemical properties of a surface oxide on Cu(100) were investigated using atomic resolution three-dimensional force mapping combined with tunneling current measurements and ab initio density functional theory. Results reveal that the maximum attractive force between tip and sample occurs above the oxygen atoms; theory indicates that the tip, in this case, terminates in a Cu atom. Meanwhile, simultaneously acquired tunneling current images emphasize the positions of Cu atoms, thereby, providing species-selective contrast in the two complementary data channels. One immediate outcome is that defects due to the displacement of surface copper are exposed in the current maps, even though force maps only reflect a well-ordered oxygen sublattice. The exact nature of the defects is confirmed by the simulations, which also reveal that the arrangement of the oxygen atoms is not disrupted by the copper displacement. In addition, the experimental force maps uncover a position-dependent modulation of the attractive forces between the surface oxygen and the copper-terminated tips, which is found to reflect the surface's inhomogeneous chemical and structural environment. As a consequence, the demonstrated method has the potential to directly probe how defects affect surface chemical interactions. © 2013 American Physical Society.
Keywords: dept.phy

Optimizing K-14 instruction to infuse 21st century skills - Day, D.; Guo, C.; Ferrari, N.; Edgecumbe, H.; Broadbridge, C. (Materials Research Society, 2013)
This multi-phased study investigates the learning outcomes of courses taught in the K-14 classroom. Specifically, the methods and practices teachers use to develop and encourage 21st Century Skills including critical thinking skills and technological fluency in all subject areas, STEM and non-STEM related, are of great interest. Currently, these skills are in high demand in fields which develop advanced materials and are the backbone of the National Academies-developed Frameworks for K-12 Science Education. Phase I participants in this study included high school and college educators while Phase II of the study will involve K-14 students. In this study, educators were asked to rate their teaching self-efficacy in two primary areas: critical thinking skills and technological fluency. This included questions related to components in their current curriculum as well as methods of assessment [e.g., rubrics]. The instrument created to measure self-efficacy was based on a modified 'Science Teaching Efficacy Belief Instrument' (STEBI). All participants were from Connecticut. Results indicate that both STEM and non-STEM related subject areas offer an equally rich array of opportunities to effectively teach critical thinking and technological fluency at a variety of educational levels. The impact of Professional Development on teacher self-efficacy was of particular importance, especially in K-12 education. © 2013 Materials Research Society.
Keywords: Advanced materials; Critical thinking; Critical thinking skills; Curricula; Educational levels; Professional development; Science education; Science teaching; Students; Teaching; Technological fluency; dept.phy

Binaries and multiple stellar systems - Horch, E. (Planets, Stars and Stellar Systems Volume 4: Stellar Structure and Evolution, 2013)
Binary and multiple stellar systems have importance in three main areas of astronomy and astrophysics. First, because of the relatively simple gravitational interaction at work in the case of binary stars, these systems provide a basic check on stellar structure and evolution theory since the masses may be determined through observation. When these masses can be linked to other properties of the two stars, such as luminosity, color, and radius, they can provide very stringent constraints on stellar models. Second, the statistics of binary and multiple star systems provide clues to star formation mechanisms and environmental effects in the galactic gravitational potential and in clusters. Although a number of good results have been obtained in nearby star clusters and associations, knowledge of the field population has been somewhat limited until recently by a lack of large, complete samples of binaries. However, there appears to be a great deal of promise in this area for the coming decade in part due to astrometric satellites such as Hipparcos and Gaia. Third, the binary scenario is invoked to explain several important types of astrophysical phenomena such as Type Ia supernovae, cataclysmic variables, and stellar x-ray sources. Since the first of these mentioned is a standard candle for the extragalactic distance scale, it may even be said binary stars play a minor role in field of cosmology. However, in this chapter, the focus will mainly be on normal stars in binary and multiple-stellar systems. The basic physics of binaries will be reviewed, and the observational methods in use today will be discussed together with their limitations and prospects for the future. Finally, an overview of the current science in the three main areas mentioned where binaries have a significant impact will be given. © Springer Science+Business Media Dordrecht 2013.
Keywords: Astrometric; Binary star orbits; Detached binaries; Interacting binaries; Interferometric; Spectroscopic; Star clusters; Star formation; Stellar astrophysics; Stellar masses; dept.phy

Understanding scanning tunneling microscopy contrast mechanisms on metal oxides: A case study - Mönig, H.; Todorović, M.; Baykara, M.Z.; Schwendemann, T.C.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (ACS Nano, 2013)
A comprehensive analysis of contrast formation mechanisms in scanning tunneling microscopy (STM) experiments on a metal oxide surface is presented with the oxygen-induced (2√2×√2)R45 missing row reconstruction of the Cu(100) surface as a model system. Density functional theory and electronic transport calculations were combined to simulate the STM imaging behavior of pure and oxygen-contaminated metal tips with structurally and chemically different apexes while systematically varying bias voltage and tip-sample distance. The resulting multiparameter database of computed images was used to conduct an extensive comparison with experimental data. Excellent agreement was attained for a large number of cases, suggesting that the assumed model tips reproduce most of the commonly encountered contrast-determining effects. Specifically, we find that depending on the bias voltage polarity, copper-terminated tips allow selective imaging of two structurally distinct surface Cu sites, while oxygen-terminated tips show complex contrasts with pronounced asymmetry and tip-sample distance dependence. Considering the structural and chemical stability of the tips reveals that the copper-terminated apexes tend to react with surface oxygen at small tip-sample distances. In contrast, oxygen-terminated tips are considerably more stable, allowing exclusive surface oxygen imaging at small tip-sample distances. Our results provide a conclusive understanding of fundamental STM imaging mechanisms, thereby providing guidelines for experimentalists to achieve chemically selective imaging by properly selecting imaging parameters. © 2013 American Chemical Society.
Keywords: Bias voltage; Copper; Copper compounds; DFT simulation; Metal oxides; Metallic compounds; Oxygen; STM contrast; Scanning tunneling microscopy; Tip chemistry; dept.phy; metal oxide; tip asymmetry; tip chemistry; tip oxidation

MOST sub-arcsecond companions of Kepler exoplanet candidate host stars are gravitationally bound - Horch, E.P.; Howell, S.B.; Everett, M.E.; Ciardi, D.R. (Astrophysical Journal, 2014)
Using the known detection limits for high-resolution imaging observations and the statistical properties of true binary and line-of-sight companions, we estimate the binary fraction of Kepler exoplanet host stars. Our speckle imaging programs at the WIYN 3.5 m and Gemini North 8.1 m telescopes have observed over 600 Kepler objects of interest and detected 49 stellar companions within 1 arcsec. Assuming binary stars follow a log-normal period distribution for an effective temperature range of 3000-10,000 K, then the model predicts that the vast majority of detected sub-arcsecond companions are long period (P > 50 yr), gravitationally bound companions. In comparing the model predictions to the number of real detections in both observational programs, we conclude that the overall binary fraction of host stars is similar to the 40%-50% rate observed for field stars. © 2014. The American Astronomical Society. All rights reserved..
Keywords: Binaries: visual; Planetary systems; Stars: solar-type; Techniques: high angular resolution; Techniques: interferometric; Techniques: photometric; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2014)
Keywords: dept.phy

Simultaneous measurement of multiple independent atomic-scale interactions using scanning probe microscopy: Data interpretation and the effect of cross-talk - Baykara, M.Z.; Todorović, M.; Mönig, H.; Schwendemann, T.C.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (Journal of Physical Chemistry C, 2015)
In high-resolution scanning probe microscopy, it is becoming increasingly common to simultaneously record multiple channels representing different tip-sample interactions to collect complementary information about the sample surface. A popular choice involves simultaneous scanning tunneling microscopy (STM) and noncontact atomic force microscopy (NC-AFM) measurements, which are thought to reflect the chemical and electronic properties of the sample surface. With surface-oxidized Cu(100) as an example, we investigate whether atomic-scale information on chemical interactions can be reliably extracted from frequency shift maps obtained while using the tunneling current as the feedback parameter. Ab initio calculations of interaction forces between specific tip apexes and the surface are utilized to compare experiments with theoretical expectations. The examination reveals that constant-current operation may induce a noticeable influence of topography-feedback-induced cross-talk on the frequency shift data, resulting in misleading interpretations of local chemical interactions on the surface. Consequently, the need to apply methods such as 3D-AFM is emphasized when accurate conclusions about both the local charge density near the Fermi level, as provided by the STM channel, and the site-specific strength of tip-sample interactions (NC-AFM channel) are desired. We conclude by generalizing to the case where multiple atomic-scale interactions are being probed while only one of them is kept constant. © 2015 American Chemical Society.
Keywords: Ab initio calculations; Atomic force microscopy; Atomic-scale interaction; Calculations; Chemical interactions; Constant current operations; Crosstalk; Electronic properties; High resolution scanning; Hydrophobicity; Noncontact atomic force microscopy; Scanning tunneling microscopy; Simultaneous measurement; Tip-sample interaction; Topography; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2015)
Keywords: dept.phy

Three-dimensional interaction force and tunneling current spectroscopy of point defects on rutile TiO2(110) - Baykara, M.Z.; Mönig, H.; Schwendemann, T.C.; Ünverdi, Ö.; Altman, E.I.; Schwarz, U.D. (Applied Physics Letters, 2016)
The extent to which point defects affect the local chemical reactivity and electronic properties of an oxide surface was evaluated with picometer resolution in all three spatial dimensions using simultaneous atomic force/scanning tunneling microscopy measurements performed on the (110) face of rutile TiO2. Oxygen atoms were imaged as protrusions in both data channels, corresponding to a rarely observed imaging mode for this prototypical metal oxide surface. Three-dimensional spectroscopy of interaction forces and tunneling currents was performed on individual surface and subsurface defects as a function of tip-sample distance. An interstitial defect assigned to a subsurface hydrogen atom is found to have a distinct effect on the local density of electronic states on the surface, but no detectable influence on the tip-sample interaction force. Meanwhile, spectroscopic data acquired on an oxygen vacancy highlight the role of the probe tip in chemical reactivity measurements. © 2016 AIP Publishing LLC.
Keywords: Atoms; Defect density; Electron tunneling; Electronic properties; Interstitial defects; Local density of electronic state; Metals; Oxide minerals; Oxygen vacancies; Picometer resolution; Point defects; Prototypical metal oxide surfaces; Reactivity measurements; Subsurface hydrogens; Surface defects; Three-dimensional interaction; Tip-sample interaction; Titanium dioxide; dept.phy

Multifunctional in vivo imaging of pancreatic islets during diabetes development - Li, G.; Wu, B.; Ward, M.G.; Chong, C.N.; Mukherjee, S.; Chen, S.; Hao, M. (Journal of Cell Science, 2016)
Pancreatic islet dysfunction leading to insufficient glucose-stimulated insulin secretion triggers the clinical onset of diabetes. How islet dysfunction develops is not well understood at the cellular level, partly owing to the lack of approaches to study single islets longitudinally in vivo. Here, we present a noninvasive, high-resolution system to quantitatively image real-time glucose metabolism from single islets in vivo, currently not available with any other method. In addition, this multifunctional system simultaneously reports islet function, proliferation, vasculature and macrophage infiltration in vivo from the same set of images. Applying our method to a longitudinal high-fat diet study revealed changes in islet function as well as alternations in islet microenvironment. More importantly, this label-free system enabled us to image real-time glucose metabolism directly from single human islets in vivo for the first time, opening the door to noninvasive longitudinal in vivo studies of healthy and diabetic human islets. © 2016. Published by The Company of Biologists Ltd.
Keywords: Animals; Anterior Chamber; Article; Cell Proliferation; Collagen; Computer Systems; Diabetes; Diabetes Mellitus; Diet, High-Fat; Disease Models, Animal; Fluorescence; Glucose; Glucose metabolism; Humans; Imaging, Three-Dimensional; In vivo imaging; Injections, Intraperitoneal; Islets of Langerhans; Macrophages; Male; Mice; Multiphoton microscopy; NAD(P)H; Pancreatic islets; animal; animal cell; animal experiment; anterior eye chamber; autofluorescence imaging; autofluorescence imaging system; cell function; cell infiltration; cell proliferation; collagen; computer system; dept.phy; diabetes mellitus; disease course; disease model; drug effects; fluorescence; glucose; glucose metabolism; human; imaging system; in vivo study; intraperitoneal drug administration; lipid diet; macrophage; male; metabolism; microenvironment; mouse; nonhuman; pancreas islet; pathology; priority journal; three dimensional imaging; vascularization

Coherent diffractive photoproduction of ρ0 mesons on gold nuclei at 200 GeV/nucleon-pair at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2017)
The STAR Collaboration reports on the photoproduction of π+π- pairs in gold-gold collisions at a center-of-mass energy of 200 GeV/nucleon-pair. These pion pairs are produced when a nearly real photon emitted by one ion scatters from the other ion. We fit the π+π- invariant-mass spectrum with a combination of ρ0 and ω resonances and a direct π+π- continuum. This is the first observation of the ω in ultraperipheral collisions, and the first measurement of ρ-ω interference at energies where photoproduction is dominated by Pomeron exchange. The ω amplitude is consistent with the measured γp→ωp cross section, a classical Glauber calculation, and the ω→π+π- branching ratio. The ω phase angle is similar to that observed at much lower energies, showing that the ρ-ω phase difference does not depend significantly on photon energy. The ρ0 differential cross section dσ/dt exhibits a clear diffraction pattern, compatible with scattering from a gold nucleus, with two minima visible. The positions of the diffractive minima agree better with the predictions of a quantum Glauber calculation that does not include nuclear shadowing than with a calculation that does include shadowing. © 2017 American Physical Society.
Keywords: dept.phy; peer-reviewed

Elliptic flow of electrons from heavy-flavor hadron decays in Au + Au collisions at √sNN =200, 62.4, and 39 GeV - STAR Collaboration (Physical Review C, 2017)
We present measurements of elliptic flow (v2) of electrons from the decays of heavy-flavor hadrons (eHF) by the STAR experiment. For Au+Au collisions at sNN=200 GeV we report v2, for transverse momentum (pT) between 0.2 and 7 GeV/c, using three methods: the event plane method (v2EP), two-particle correlations (v2{2}), and four-particle correlations (v2{4}). For Au+Au collisions at sNN=62.4 and 39 GeV we report v2{2} for pT<2GeV/c. v2{2} and v2{4} are nonzero at low and intermediate pT at 200 GeV, and v2{2} is consistent with zero at low pT at other energies. The v2{2} at the two lower beam energies is systematically lower than at sNN=200 GeV for pT<1GeV/c. This difference may suggest that charm quarks interact less strongly with the surrounding nuclear matter at those two lower energies compared to sNN=200 GeV. © 2017 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurement of the cross section and longitudinal double-spin asymmetry for dijet production in polarized pp collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2017)
We report the first measurement of the longitudinal double-spin asymmetry ALL for midrapidity dijet production in polarized pp collisions at a center-of-mass energy of s=200 GeV. The dijet cross section was measured and is shown to be consistent with next-to-leading order (NLO) perturbative QCD predictions. ALL results are presented for two distinct topologies, defined by the jet pseudorapidities, and are compared to predictions from several recent NLO global analyses. The measured asymmetries, the first such correlation measurements, support those analyses that find positive gluon polarization at the level of roughly 0.2 over the region of Bjorken-x>0.05. © 2017 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurements of jet quenching with semi-inclusive hadron+jet distributions in Au+Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2017)
The STAR Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high transverse momentum hadron trigger, in central and peripheral Au+Au collisions at sNN=200 GeV. Charged jets are reconstructed with the anti-kT algorithm for jet radii R between 0.2 and 0.5 and with low infrared cutoff of track constituents (pT>0.2 GeV/c). A novel mixed-event technique is used to correct the large uncorrelated background present in heavy ion collisions. Corrected recoil jet distributions are reported at midrapidity, for charged-jet transverse momentum pT,jetch<30 GeV/c. Comparison is made to similar measurements for Pb+Pb collisions at s=2.76 TeV, to calculations for p+p collisions at s=200 GeV based on the pythia Monte Carlo generator and on a next-to-leading order perturbative QCD approach, and to theoretical calculations incorporating jet quenching. The recoil jet yield is suppressed in central relative to peripheral collisions, with the magnitude of the suppression corresponding to medium-induced charged energy transport out of the jet cone of 2.8±0.2(stat)±1.5(sys) GeV/c, for 10<pT,jetch<20 GeV/c and R=0.5. No medium-induced change in jet shape is observed for R<0.5. The azimuthal distribution of low-pT,jetch recoil jets may be enhanced at large azimuthal angles to the trigger axis, due to scattering off quasiparticles in the hot QCD medium. Measurement of this distribution gives a 90% statistical confidence upper limit to the yield enhancement at large deflection angles in central Au+Au collisions of 50±30(sys)% of the large-angle yield in p+p collisions predicted by pythia. © 2017 American Physical Society.
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2017)
Keywords: dept.phy

Characterization and discrimination of basal cell carcinoma and normal human skin tissues using resonance Raman spectroscopy - Liu, C.-H.; Wu, B.; Boydston-White, S.; Beckman, H.; Sriramoju, V.; Sordillo, L.; Zhang, C.; Smith, J.; Zhang, L.; Shi, L.; Alfano, R.R. (OSA - The Optical Society, 2017)
Resonance Raman spectroscopy is used for rapid detection of skin BCC cancer. The cross-validated classification accuracy is achieved to be as high as 98% using nonnegative matrix factorization along with support vector machine statistical method. © OSA 2017.
Keywords: Basal cell carcinoma; Classification accuracy; Factorization; Human skin; Matrix algebra; Nonnegative matrix factorization; Raman spectroscopy; Rapid detection; Resonance Raman spectroscopy; dept.phy

Erratum to: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing (Scientific Reports, (2017), 7, 1, (7155), 10.1038/s41598-017-07719-2) - Bordeenithikasem, P.; Liu, J.; Kube, S.A.; Li, Y.; Ma, T.; Scanley, B.E.; Broadbridge, C.C.; Vlassak, J.J.; Singer, J.P.; Schroers, J. (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper. © 2018, The Author(s).
Keywords: dept.phy; erratum; error

Speckle imaging through a coherent fiber bundle - Davidson, J.W., Jr.; Horch, E.P.; Majewski, S.R. (SPIE, 2018)
Speckle imaging is a well known method to achieve diffraction-limited (DL) imaging from ground-based telescopes. The traditional observing method for speckle has been to observe a single, unresolved, source per telescope pointing over a relatively small field of view (FOV). The need for large DL surveys of targets with high sky density motivates a desire for simultaneous speckle imaging over large FOVs, however it is currently impractical to attain this by covering the entire focal plane with fast readout detectors. An alternative approach is to connect a relatively small number of detector pixels to multiple interesting targets spanning a large FOV through the use of optical fibers, a technique employed in spectroscopy for decades. However, for imaging we require the use of coherent fiber bundles (CFBs). We discuss various design considerations for coherent fiber speckle imaging with an eye toward a multiplexed system using numerous configurable CFBs, and we test its viability with a prototype instrument that uses a single CFB to transport speckle images from the telescope focal plane to a traditionally designed, fast readout speckle camera. Using this device on University of Virginia's Fan Mountain Observatory 40-inch telescope we have for the first time successfully demonstrated speckle imaging through a CFB, using both optical and NIR detectors. Results are presented of DL speckle imaging of well-known close (including subarcsecond) binary stars resolved with this fiber-fed speckle system and compared to both literature results and traditional speckle imaging taken with the same camera directly, with no intervening CFB. © 2018 SPIE.
Keywords: Binary star; Cameras; Coherent fiber bundles; Exo-planets; Fiber optics; Focusing; High-resolution imaging; Interferometry; Optical fibers; Speckle; Speckle imaging; Stars; Telescopes; binary stars; coherent fiber bundles; dept.phy; exo-planets; fiber optics; high resolution imaging

Two-color speckle imaging of M-dwarfs with the Discovery Channel telescope - Hahne, F.W.; Horch, E.P.; Van Belle, G.T.; Clark, C.; Winters, J.G.; Henry, T.J. (SPIE, 2018)
Lowell Observatory and Southern Connecticut State University are currently involved in a joint project to determine the stellar multiplicity rates and the fundamental stellar parameters of M dwarf stars using the Differential Speckle Survey Instrument (DSSI) at Lowell's Discovery Channel Telescope (DCT). DSSI observes speckle patterns simultaneously at two separate wavelengths, allowing color measurements of the components of a binary system to be made in a single observation. This paper will describe the initial data gathering process, which began in 2016. Since then, over 1000 stars have been observed. We summarize the analysis on these objects so far, and discuss the relevance of these observations for existing and future space missions such as TESS, JWST, and Gaia. © 2018 SPIE.
Keywords: Color measurements; Discovery channel telescopes; Image reconstruction; Interferometry; Multiplicity rate; Optical properties; Speckle; Speckle imaging; Speckle patterns; Stars; Stellar parameters; Survey instruments; Telescopes; dept.phy; image reconstruction; stellar properties

Azimuthal anisotropy in Cu+Au collisions at s NN =200 GeV - STAR Collaboration (Physical Review C, 2018)
The azimuthal anisotropic flow of identified and unidentified charged particles has been systematically studied in Cu+Au collisions at sNN=200 GeV for harmonics n=1-4 in the pseudorapidity range |η|<1. The directed flow in Cu+Au collisions is compared with the rapidity-odd and, for the first time, the rapidity-even components of charged particle directed flow in Au+Au collisions at sNN=200 GeV. The slope of the directed flow pseudorapidity dependence in Cu+Au collisions is found to be similar to that in Au+Au collisions, with the intercept shifted toward positive pseudorapidity values, i.e., the Cu-going direction. The mean transverse momentum projected onto the spectator plane (px) in Cu+Au collision also exhibits approximately linear dependence on pseudorapidity with the intercept at about η≈-0.4 (shifted from zero in the Au-going direction), closer to the rapidity of the Cu+Au system center of mass. The observed dependencies find a natural explanation in a picture of the directed flow originating partly due the "tilted source" and partly due to the asymmetry in the initial density distribution. A charge dependence of (px) was also observed in Cu+Au collisions, consistent with an effect of the initial electric field created by charge difference of the spectator protons in two colliding nuclei. The rapidity-even component of directed flow in Au+Au collisions is close to that in Pb+Pb collisions at sNN=2.76 TeV, indicating a similar magnitude of dipolelike fluctuations in the initial-state density distribution. Higher harmonic flow in Cu+Au collisions exhibits similar trends to those observed in Au+Au and Pb+Pb collisions and is qualitatively reproduced by a viscous hydrodynamic model and a multiphase transport model. For all harmonics with n≥2 we observe an approximate scaling of vn with the number of constituent quarks; this scaling works as well in Cu+Au collisions as it does in Au+Au collisions. © 2018 American Physical Society.
Keywords: dept.phy; peer-reviewed

Global polarization of Λ hyperons in Au + Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2018)
Global polarization of Λ hyperons has been measured to be of the order of a few tenths of a percentage in Au+Au collisions at sNN = 200 GeV, with no significant difference between Λ and Λ. These new results reveal the collision energy dependence of the global polarization together with the results previously observed at sNN = 7.7-62.4 GeV and indicate noticeable vorticity of the medium created in noncentral heavy-ion collisions at the highest Relativistic Heavy Ion Collider collision energy. The signal is in rough quantitative agreement with the theoretical predictions from a hydrodynamic model and from a multi-phase transport model. The polarization is larger in more peripheral collisions, and depends weakly on the hyperon's transverse momentum and pseudorapidity ηH within |ηH|<1. An indication of the polarization dependence on the event-by-event charge asymmetry is observed at the 2σ level, suggesting a possible contribution to the polarization from the axial current induced by the initial magnetic field. © 2018 American Physical Society.
Keywords: dept.phy; peer-reviewed

Improved measurement of the longitudinal spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The longitudinal spin transfer DLL to Λ and Λ hyperons produced in high-energy polarized proton-proton collisions is expected to be sensitive to the helicity distribution functions of strange quarks and antiquarks of the proton, and to longitudinally polarized fragmentation functions. We report an improved measurement of DLL from data obtained at a center-of-mass energy of s=200 GeV with the STAR detector at RHIC. The data have an approximately twelve times larger figure of merit than prior results and cover |η|<1.2 in pseudorapidity with transverse momenta pT up to 6 GeV/c. In the forward scattering hemisphere at largest pT, the longitudinal spin transfer is found to be DLL=-0.036±0.048(stat)±0.013(sys) for Λ hyperons and DLL=0.032±0.043(stat)±0.013(sys) for Λ antihyperons. The dependences on η and pT are presented and compared with model evaluations. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Low- pT e+e- Pair Production in Au +Au Collisions at sNN =200 GeV and U + U Collisions at sNN =193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e+e- pair production in the mass region 0.4<Mee<2.6 GeV/c2 at low transverse momentum (pT<0.15 GeV/c) in noncentral Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Significant enhancement factors, expressed as ratios of data over known hadronic contributions, are observed in the 40%-80% centrality of these collisions. The excess yields peak distinctly at low pT with a width (âpT2â ©) between 40 and 60 MeV/c. The absolute cross section of the excess depends weakly on centrality, while those from a theoretical model calculation incorporating an in-medium broadened ρ spectral function and radiation from a quark gluon plasma or hadronic cocktail contributions increase dramatically with an increasing number of participant nucleons. Model calculations of photon-photon interactions generated by the initial projectile and target nuclei describe the observed excess yields but fail to reproduce the pT2 distributions. © 2018 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the »https://creativecommons.org/licenses/by/4.0/» Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by SCOAP3.
Keywords: Au+Au collisions; Colliding beam accelerators; Enhancement factor; Germanium compounds; Gold; Mass regions; Measurements of; Pair production; Photons; Transverse momenta; dept.phy; peer-reviewed

Transverse spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The transverse spin transfer from polarized protons to Λ and Λ hyperons is expected to provide sensitivity to the transversity distribution of the nucleon and to the transversely polarized fragmentation functions. We report the first measurement of the transverse spin transfer to Λ and Λ along the polarization direction of the fragmenting quark, DTT, in transversely polarized proton-proton collisions at s=200 GeV with the STAR detector at RHIC. The data correspond to an integrated luminosity of 18 pb-1 and cover the pseudorapidity range |η|<1.2 and transverse momenta pT up to 8 GeV/c. The dependence on pT and η are presented. The DTT results are found to be comparable with a model prediction and are also consistent with zero within uncertainties. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Speckle imaging of KOI binary stars with the WIYN telescope - Hess, N.M.; Thayer, P.R.; Horch, E.P.; Davidson, J.W., Jr.; Baptista, B.J.; Everett, M.E.; Howell, S.B. (SPIE, 2018)
Binary star systems where one of the stars is an exoplanet host appear to be more common than expected prior to the Kepler mission. The Kepler mission and subsequent ground-based follow-up work have revealed a number of Kepler Objects of Interest (KOIs) that have nearby stellar companions (within ∼1 arcsec). KOIs with stellar companions and at least one suspected exoplanet were selected for this work. Recent work on these stars has mainly focused on placing the companions on the H-R diagram and inferring if they are likely to be gravitationally bound based on whether their locations are consistent with a common isochrone. However, we have been observing these KOI double stars with speckle imaging over several years and are now in a position to assess whether these systems have components with a common proper motion, and can be seen as physically associated on that basis. We will give sample results of KOI double stars that are in fact common proper motion pairs. We compare our results with estimates of the multiplicity rate of exoplanet hosts from other methods and comment on the use of our data for constraining orbital parameters at this point, particularly the inclination angle. For transit observations, the inclination of the planetary orbit is already known, and the relationship between planetary and stellar orbital planes could have implications for star and planet formation. © 2018 SPIE.
Keywords: Binary star; Binary star system; Extrasolar planets; Host-stars; Inclination angles; Interferometry; Multiplicity rate; Orbital parameters; Orbits; Speckle; Speckle imaging; Stars; astrometry; binary stars; dept.phy; exoplanet host stars

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2018)
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H.; Gherasimova, M. (International Journal of High Speed Electronics and Systems, 2018)
Keywords: dept.phy

Preface - Jain, F.C.; Broadbridge, C.; Tang, H.; Gherasimova, M. (High Performance Materials and Devices for High-Speed Electronic Systems, 2018)
Keywords: Materials; dept.phy

Machine learning based analysis of human prostate cancer cell lines at different metastatic ability using native fluorescence spectroscopy with selective excitation wavelength - Xue, J.; Pu, Y.; Smith, J.; Gao, X.; Wu, B. (SPIE, 2018)
Native fluorescence spectra play important roles in cancer detection. It is widely acknowledged that the emission spectrum of a tissue is a superposition of spectra of various salient fluorophores. However, component quantification is essentially an ill-posed problem. To address this problem, the native fluorescence spectra of normal human very low (LNCap), moderately metastatic (DU-145), and advanced metastatic (PC-3) cell lines were studied by the selected wavelength of 300 nm to investigate the key fluorescent molecules such as tryptophan, collagen and NADH. The native fluorescence spectra of cancer cell lines at different risk levels were analyzed using various machine learning algorithms for feature detection and develop criteria to separate the three types of cells. Principal component analysis (PCA), nonnegative matrix factorization (NMF), and partial least squares fitting were used separately to reduce dimension, extract features and detect biomolecular alterations reflected in the spectra. The scores corresponding to the basis spectra were used for classification. A linear support vector machine (SVM) was used to classify the spectra of the cells with different metastatic ability. In detection of signals coming from tryptophan and NADH with observed data corrupted by noise and inference, a sufficient statistic can be obtained based on the basis spectra retrieved using nonnegative matrix factorization. This work shows changes of relative contents of tryptophan and NADH obtained from native fluorescence spectroscopy may present potential criteria for detecting cancer cell lines of different metastatic ability. © 2018 SPIE.
Keywords: Amino acids; Artificial intelligence; Cell culture; Cells; Diseases; Emission spectroscopy; Factorization; Feature extraction; Fluorescence; Fluorescence spectroscopy; Image retrieval; Learning algorithms; Least squares approximations; Matrix algebra; NADH; Native fluorescence; Native fluorescence (NFL) spectra; Nonnegative matrix factorization; Photonics; Principal component analysis; Spectrum analysis; Support vector machines; advanced metastatic (PC-3); dept.phy; low metastatic (LNCap); moderately metastatic (DU-145); nonnegative matrix factorization; principal component analysis; support vector machine (SVM) classifier; tryptophan

Characterization of iron doped zinc oxide nanoparticles using fluorescence spectroscopy - Fernando, M.; Singhal, R.; LeMaire, P.K.; Wu, B. (Optical Society of America (OSA), 2019)
ZnO and Fe-doped ZnO nanoparticles were analyzed in ethanol solution and dry powder form using fluorescence spectroscopy. Near-band-edge emission (NBE) and defect emission (DE) peaks were studied. A blue-shift was observed with the NBE emission peak. © OSA 2019. The Author(s).
Keywords: Blue shift; Defect emission; Dry powders; Emission peaks; Ethanol solutions; Fe-doped; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron oxides; Iron-doped; Nanoparticles; Near band edge emissions; Oxide minerals; Zinc oxide; ZnO nanoparticles; dept.phy

Thin Film Deposition and Carbon Nanotube Synthesis - Frey, J.; Schwendemann, T.C. (International Journal of High Speed Electronics and Systems, 2019)
Carbon nanotubes (CNTs) are a viable product for many different markets. One specific area of promise is the use of CNTs in supercapacitors. The CNT synthesis is a two-step process with the first being the formation of a thin film layer. The thin film substrate is created by means of the Thermal Evaporation Physical Vapor Deposition (TPVD) process. After the thin film substrate is deposited, the CNTs are grown in a Chemical Vapor Deposition (CVD) growth chamber. Analysis of the thin film substrate and CNTs is performed primarily using Scanning Electron Microscopy (SEM). The results show the inclusion of ultrapure water in the CVD process contributed to the success of CNT growth. Multiple prong CNT grow is seen for CVDs trails of silver thin film layer deposited on silicon substrates. The silver nanoparticle had a large diameter with an acute contact angle. The single prong growth indicates the iron nanoparticles formed an obtuse contact angle due to the amorphic surface of alumina substrate. The focus of this project is to explore and investigate different materials and conditions for optimal CNT synthesis in the hopes of creating a uniform forest of vertically aligned carbon nanotubes. © 2019 World Scientific Publishing Company.
Keywords: Alumina; Alumina substrates; Aluminum oxide; Carbon nanotube synthesis; Carbon nanotubes; Chemical vapor deposition; Chemical vapor depositions (CVD); Contact angle; Iron nanoparticles; Nanoparticles; Physical vapor deposition; Scanning electron microscopy; Silicon substrates; Silver nanoparticles; Substrates; Thermal evaporation; Thin film substrate; Thin films; Thin-film depositions; Vertically aligned carbon nanotube; dept.phy; peer-reviewed

Breast cancer diagnosis using fluorescence spectroscopy with dualwavelength excitation and machine learning - Gaoa, X.; Wu, B. (SPIE, 2019)
Intrinsic fluorescence spectra of fresh normal and cancerous human breast tissues were measured using two selective excitation wavelengths including 290nm and 340nm. Dual-wavelength excitation may reveal more molecular information than single-wavelength excitation. In the meantime, it is significantly faster than the acquisition of excitation-emission (EEM) matrix. Unsupervised machine learning algorithms principal component analysis (PCA) and non-negative matrix factorization (NMF) were used to reduce the dimensionality of the spectral data. The relative concentrations of the basis spectra retrieved by PCA and NMF were considered features of the samples and used to distinguish normal and malignant tissues. The performances of classification using support vector machine (SVM) based on PCA and NMF features were compared. The classification using spectral data with dual-wavelength excitation was compared with single-wavelength excitation. Classification based on NMF-retrieved components from spectral data with dual-wavelength excitation yielded the best performance. © 2019 SPIE.
Keywords: Biopsy; Breast Cancer; Breast cancer; Cancer diagnosis; Classification (of information); Diseases; Dual wavelength; Dual-wavelength excitation; Factorization; Fluorescence; Fluorescence spectroscopy; Histology; Learning algorithms; Machine learning; Matrix algebra; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Principal component analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Centrality and transverse momentum dependence of D0 -meson production at mid-rapidity in Au + Au collisions at s NN =200 GeV - STAR Collaboration (Physical Review C, 2019)
We report a new measurement of D0-meson production at mid-rapidity (|y|<1) in Au + Au collisions at sNN=200GeV utilizing the heavy flavor tracker, a high resolution silicon detector at the STAR experiment. Invariant yields of D0 mesons with transverse momentum pT9GeV/c are reported in various centrality bins (0-10%, 10-20%, 20-40%, 40-60%, and 60-80%). Blast-wave thermal models are used to fit the D0-meson pT spectra to study D0 hadron kinetic freeze-out properties. The average radial flow velocity extracted from the fit is considerably smaller than that of light hadrons (π,K, and p), but comparable to that of hadrons containing multiple strange quarks (φ,Ξ-), indicating that D0 mesons kinetically decouple from the system earlier than light hadrons. The calculated D0 nuclear modification factors reaffirm that charm quarks suffer a large amount of energy loss in the medium, similar to those of light quarks for pT>4GeV/c in central 0-10% Au + Au collisions. At low pT, the nuclear modification factors show a characteristic structure qualitatively consistent with the expectation from model predictions that charm quarks gain sizable collective motion during the medium evolution. The improved measurements are expected to offer new constraints to model calculations and help gain further insights into the hot and dense medium created in these collisions. © 2019 American Physical Society.
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetry for inclusive jet and dijet production in pp collisions at s =510 GeV - STAR Collaboration (Physical Review D, 2019)
We report the first measurement of the inclusive jet and the dijet longitudinal double-spin asymmetries, ALL, at midrapidity in polarized pp collisions at a center-of-mass energy s=510 GeV. The inclusive jet ALL measurement is sensitive to the gluon helicity distribution down to a gluon momentum fraction of x≈0.015, while the dijet measurements, separated into four jet-pair topologies, provide constraints on the x dependence of the gluon polarization. Both results are consistent with previous measurements made at s=200 GeV in the overlapping kinematic region, x>0.05, and show good agreement with predictions from recent next-to-leading order global analyses. © 2019 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurement of inclusive J/ψ suppression in Au+Au collisions at sNN=200 GeV through the dimuon channel at STAR - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2019)
J/ψ suppression has long been considered a sensitive signature of the formation of the Quark-Gluon Plasma (QGP) in relativistic heavy-ion collisions. In this letter, we present the first measurement of inclusive J/ψ production at mid-rapidity through the dimuon decay channel in Au+Au collisions at sNN=200 GeV with the STAR experiment. These measurements became possible after the installation of the Muon Telescope Detector was completed in 2014. The J/ψ yields are measured in a wide transverse momentum (pT) range of 0.15 GeV/c to 12 GeV/c from central to peripheral collisions. They extend the kinematic reach of previous measurements at RHIC with improved precision. In the 0-10% most central collisions, the J/ψ yield is suppressed by a factor of approximately 3 for pT>5 GeV/c relative to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The J/ψ nuclear modification factor displays little dependence on pT in all centrality bins. Model calculations can qualitatively describe the data, providing further evidence for the color-screening effect experienced by J/ψ mesons in the QGP. © 2019 The Author(s)
Keywords: Color-screening; J/ψ suppression; Quark-gluon plasma; dept.phy; peer-reviewed

Measurement of the longitudinal spin asymmetries for weak boson production in proton-proton collisions at s =510 GeV - STAR Collaboration (Physical Review D, 2019)
We report new STAR measurements of the single-spin asymmetries AL for W+ and W- bosons produced in polarized proton-proton collisions at s=510 GeV as a function of the decay-positron and decay-electron pseudorapidity. The data were obtained in 2013 and correspond to an integrated luminosity of 250 pb-1. The results are combined with previous results obtained with 86 pb-1. A comparison with theoretical expectations based on polarized lepton-nucleon deep-inelastic scattering and prior polarized proton-proton data suggests a difference between the ū and d quark helicity distributions for 0.05<x<0.25. In addition, we report new results for the double-spin asymmetries ALL for W±, as well as AL for Z/γ∗ production and subsequent decay into electron-positron pairs. © 2019 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurements of the transverse-momentum-dependent cross sections of J /ψ production at mid-rapidity in proton+proton collisions at s =510 and 500 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2019)
We present measurements of the differential cross sections of inclusive J/ψ meson production as a function of transverse momentum (pTJ/ψ) using the μ+μ- and e+e- decay channels in proton+proton collisions at center-of-mass energies of 510 and 500 GeV, respectively, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The measurement from the μ+μ- channel is for 0<pTJ/ψ<9 GeV/c and rapidity range |yJ/ψ|<0.4, and that from the e+e- channel is for 4<pTJ/ψ<20 GeV/c and |yJ/ψ|<1.0. The ψ(2S) to J/ψ ratio is also measured for 4<pTmeson<12 GeV/c through the e+e- decay channel. Model calculations, which incorporate different approaches toward the J/ψ production mechanism, are compared with experimental results and show reasonable agreement within uncertainties. © 2019 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

STAR Collaboration - STAR Collaboration (Nuclear Physics A, 2019)
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2019)
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (High Performance Logic and Circuits for High-Speed Electronic Systems, 2019)
Keywords: dept.phy

Three Red Suns in the Sky: A Transiting, Terrestrial Planet in a Triple M-dwarf System at 6.9 pc - Winters, J.G.; Medina, A.A.; Irwin, J.M.; Charbonneau, D.; Astudillo-Defru, N.; Horch, E.P.; Eastman, J.D.; Vrijmoet, E.H.; Henry, T.J.; Diamond-Lowe, H.; Winston, E.; Barclay, T.; et al. (Astronomical Journal, 2019)
We present the discovery from Transiting Exoplanet Survey Satellite (TESS) data of LTT 1445Ab. At a distance of 6.9 pc, it is the second nearest transiting exoplanet system found to date, and the closest one known for which the primary is an M dwarf. The host stellar system consists of three mid-to-late M dwarfs in a hierarchical configuration, which are blended in one TESS pixel. We use MEarth data and results from the Science Processing Operations Center data validation report to determine that the planet transits the primary star in the system. The planet has a radius of, an orbital period of days, and an equilibrium temperature of K. With radial velocities from the High Accuracy Radial Velocity Planet Searcher, we place a 3σ upper mass limit of 8.4 on the planet. LTT 1445Ab provides one of the best opportunities to date for the spectroscopic study of the atmosphere of a terrestrial world. We also present a detailed characterization of the host stellar system. We use high-resolution spectroscopy and imaging to rule out the presence of any other close stellar or brown dwarf companions. Nineteen years of photometric monitoring of A and BC indicate a moderate amount of variability, in agreement with that observed in the TESS light-curve data. We derive a preliminary astrometric orbit for the BC pair that reveals an edge-on and eccentric configuration. The presence of a transiting planet in this system hints that the entire system may be co-planar, implying that the system may have formed from the early fragmentation of an individual protostellar core. © 2019. The American Astronomical Society. All rights reserved..
Keywords: binaries: close; dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (LTT 1445); stars: low-mass

Human brain glioma grading using label free laser-induced fluorescence spectroscopy - Zhou, Y.; Liu, C.-H.; Zhu, K.; Wu, B.; Yu, X.; Cheng, G.; Zhao, M.; Zong, R.; Zhang, C.; Chen, H.; Li, S.; Liang, Q.; et al. (SPIE, 2019)
Laser-induced fluorescence (LIF) technique was used to generate spectral signatures of endogenous fluorophores relevant to the tissue molecular composition changes in human brain glioma tumors. The goal is to study the changes of fluorescence emission spectra from endogenous fluorophores in human brain glioma of different grades, and to find new biomarkers for prognostic optical molecular pathological diagnosis. Two hundred and thirty-seven (237) native fluorescence spectra from 61 subjects were measured using LabRAM HR Evolution micro photoluminescence (PL) system for four grades of glioma tumors in ex-vivo. The differences of four grades of glioma tumors were identified by the characteristic fluorophores fingerprints under the excitation laser wavelength at UV 325nm. To our best knowledge, this is the first report for human brain study using this technique. The fluorescence peaks of biomarkers with major contribution were found, including tryptophan, collagen, elastin, reduced nicotinamide adenine dinucleotide (NADH), flavin adenine dinucleotide (FAD) and phospholipids that play important roles in the cellular energy metabolism and glycolysis pathway. The ratios of peak intensities and the peak positions in fluorescence spectra of may be used to diagnose human brain diseases or to guide biopsy during surgical resection. © 2019 SPIE.
Keywords: Amino acids; Biomarkers; Biopsy; Brain; Cellular energy; Cellular energy metabolism; Emission spectroscopy; FAD; Fluorescence; Fluorescence microscopy; Fluorescence spectroscopy; Fluorophores; Grading; Human brain; Human brain glioma tissues; Laser excitation; Laser induced fluorescence spectroscopy; Laser optics; Laser produced plasmas; Metabolism; NADH; Native fluorescence; Native laser-induced fluorescence spectroscopy; Native-fluorescence; Nucleotides; Optical molecular pathology; Pathology; Phospholipids; Tryptophan; Tumors; dept.phy

A portable visible resonance Raman analyzer with a handheld optical fiber probe for in vivo diagnosis of brain glioblastoma multiforme in an animal model - Zhou, Y.; Zhang, S.; Wu, B.; Yu, X.; Cheng, G.; Zhu, K.; Zhao, M.; Zheng, J.; Zhang, M.; Liang, Q.; Liu, C.-H.; Alfano, R.R. (Optical Society of America (OSA), 2019)
A VRR-LRR analyzer with handheld fiber‐optic probe is reported for the first time for diagnosis of brain GBM in vivo. The sensitivity for identification is 80% compared with histopathology examination. © OSA 2019. The Author(s).
Keywords: Animal model; Fiberoptic probes; Glioblastoma multiforme; Handhelds; In-vivo; Optical fiber probe; Optical fibers; Probes; Resonance Raman; dept.phy

The same frequency of planets inside and outside open clusters of stars. - Meibom, Soren; Torres, Guillermo; Fressin, Francois; Latham, David; Rowe, Jason; Ciardi, David; Bryson, Steven; Rogers, Leslie; Henze, Christopher; Janes, Kenneth; Barnes, Sydney; Marcy, Geoffrey; et al. (Nature, 2013)
: Most stars and their planets form in open clusters. Over 95 per cent of such clusters have stellar densities too low (less than a hundred stars per cubic parsec) to withstand internal and external dynamical stresses and fall apart within a few hundred million years 1. Older open clusters have survived by virtue of being richer and denser in stars (1,000 to 10,000 per cubic parsec) when they formed. Such clusters represent a stellar environment very different from the birthplace of the Sun and other planet-hosting field stars. So far more than 800 planets have been found around Sun-like stars in the field 2. The field planets are usually the size of Neptune or smaller 3,4,5. In contrast, only four planets have been found orbiting stars in open clusters 6,7,8, all with masses similar to or greater than that of Jupiter. Here we report observations of the transits of two Sun-like stars by planets smaller than Neptune in the billion-year-old open cluster NGC6811. This demonstrates that small planets can form and survive in a dense cluster environment, and implies that the frequency and properties of planets in open clusters are consistent with those of planets around field stars in the Galaxy., (C) 2013 Nature Publishing Group
Keywords: Jupiter; Neptune; article; astronomy; cluster analysis; dept.phy; environment; frequency analysis; planet; priority journal; simulation; sun; velocity

Fluctuation-driven selection at criticality in a frustrated magnetic system: the case of multiple-k partial order on the pyrochlore lattice. - Javanparast, Behnam; Hao, Zhihao; Enjalran, Matthew; Gingras, Michel J P (Physical review letters, 2015)
We study the problem of partially ordered phases with periodically arranged disordered (paramagnetic) sites on the pyrochlore lattice, a network of corner-sharing tetrahedra. The periodicity of these phases is characterized by one or more wave vectors k={1/21/21/2}. Starting from a general microscopic Hamiltonian including anisotropic nearest-neighbor exchange, long-range dipolar interactions, and second- and third-nearest neighbor exchange, we use standard mean-field theory (SMFT) to identify an extended range of interaction parameters that support partially ordered phases. We demonstrate that thermal fluctuations ignored in SMFT are responsible for the selection of one particular partially ordered phase, e.g., the "4-k" phase over the "1-k" phase. We suggest that the transition into the 4-k phase is continuous with its critical properties controlled by the cubic fixed point of a Ginzburg-Landau theory with a four-component vector order parameter. By combining an extension of the Thouless-Anderson-Palmer method originally used to study fluctuations in spin glasses with parallel-tempering Monte Carlo simulations, we establish the phase diagram for different types of partially ordered phases. Our results elucidate the long-standing puzzle concerning the origin of the 4-k partially ordered phase observed in the Gd2Ti2O7 dipolar pyrochlore antiferromagnet below its paramagnetic phase transition temperature.
Keywords: Corner-sharing tetrahedra; Crystal lattices; Ginzburg Landau theory; Hamiltonians; Intelligent systems; Interaction parameters; Mean field theory; Microscopic hamiltonians; Monte Carlo methods; Parallel tempering Monte Carlo simulations; Paramagnetic phase transitions; Paramagnetism; Phase diagrams; Spin fluctuations; Thermal fluctuations; Vector order parameter; dept.phy

Global [LAMBDA] hyperon polarization in nuclear collisions. - STAR Collaboration (Nature, 2017)
: The measurement of an alignment between the angular momentum of a non-central collision between heavy ions and the spin of emitted particles reveals that the fluid produced in the collision is extremely vortical., The extreme energy densities generated by ultra-relativistic collisions between heavy atomic nuclei produce a state of matter that behaves surprisingly like a fluid, with exceptionally high temperature and low viscosity 1. Non-central collisions have angular momenta of the order of 1,000h, and the resulting fluid may have a strong vortical structure 2,3,4 that must be understood to describe the fluid properly. The vortical structure is also of particular interest because the restoration of fundamental symmetries of quantum chromodynamics is expected to produce novel physical effects in the presence of strong vorticity 5. However, no experimental indications of fluid vorticity in heavy ion collisions have yet been found. Since vorticity represents a local rotational structure of the fluid, spin-orbit coupling can lead to preferential orientation of particle spins along the direction of rotation. Here we present measurements of an alignment between the global angular momentum of a non-central collision and the spin of emitted particles (in this case the collision occurs between gold nuclei and produces [LAMBDA] baryons), revealing that the fluid produced in heavy ion collisions is the most vortical system so far observed. (At high energies, this fluid is a quark-gluon plasma.) We find that [LAMBDA] and Symbol hyperons show a positive polarization of the order of a few per cent, consistent with some hydrodynamic predictions 6. (A hyperon is a particle composed of three quarks, at least one of which is a strange quark; the remainder are up and down quarks, found in protons and neutrons.) A previous measurement 7 that reported a null result, that is, zero polarization, at higher collision energies is seen to be consistent with the trend of our observations, though with larger statistical uncertainties. These data provide experimental access to the vortical structure of the nearly ideal liquid 8 created in a heavy ion collision and should prove valuable in the development of hydrodynamic models that quantitatively connect observations to the theory of the strong force., (C) 2017 Nature Publishing Group
Keywords: dept.phy

Combinatorial Strategies for Synthesis and Characterization of Alloy Microstructures over Large Compositional Ranges. - Li, Yanglin; Jensen, Katharine E; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Scanley, B Ellen; Broadbridge, Christine C; Schroers, Jan (ACS combinatorial science, 2016)
The exploration of new alloys with desirable properties has been a long-standing challenge in materials science because of the complex relationship between composition and microstructure. In this Research Article, we demonstrate a combinatorial strategy for the exploration of composition dependence of microstructure. This strategy is comprised of alloy library synthesis followed by high-throughput microstructure characterization. As an example, we synthesized a ternary Au-Cu-Si composition library containing over 1000 individual alloys using combinatorial sputtering. We subsequently melted and resolidified the entire library at controlled cooling rates. We used scanning optical microscopy and X-ray diffraction mapping to explore trends in phase formation and microstructural length scale with composition across the library. The integration of combinatorial synthesis with parallelizable analysis methods provides a efficient method for examining vast compositional ranges. The availability of microstructures from this vast composition space not only facilitates design of new alloys by controlling effects of composition on phase selection, phase sequence, length scale, and overall morphology, but also will be instrumental in understanding the complex process of microstructure formation in alloys.
Keywords: *Alloys/ch [Chemistry]; *Combinatorial Chemistry Techniques/mt [Methods]; *Copper/ch [Chemistry]; *Gold/ch [Chemistry]; *Silicon/ch [Chemistry]; Alloys; Combinatorial Chemistry Techniques; Copper; Gold; High-Throughput Screening Assays; Materials Testing; Physical Phenomena; Silicon; alloy; alloy microstructure; chemistry; combinatorial chemistry; combinatorial materials science; copper; dept.phy; gold; high throughput screening; high-throughput; materials testing; phase mapping; physical phenomena; procedures; silicon

Charge-Dependent Directed Flow in Cu+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2017)
We present the first measurement of charge-dependent directed flow in Cu+Au collisions at sNN=200 GeV. The results are presented as a function of the particle transverse momentum and pseudorapidity for different centralities. A finite difference between the directed flow of positive and negative charged particles is observed that qualitatively agrees with the expectations from the effects of the initial strong electric field between two colliding ions with different nuclear charges. The measured difference in directed flow is much smaller than that obtained from the parton-hadron-string-dynamics model, which suggests that most of the electric charges, i.e., quarks and antiquarks, have not yet been created during the lifetime of the strong electric field, which is of the order of, or less than, 1 fm/c. © 2017 American Physical Society.
Keywords: Antiquarks; Charged particles; Colliding beam accelerators; Directed flow; Dynamics modeling; Electric fields; Nuclear charges; Pseudorapidities; Strong electric fields; Transverse momenta; dept.phy

Dijet imbalance measurements in Au+Au and pp collisions at sNN =200 GeV at STAR - STAR Collaboration (Physical Review Letters, 2017)
We report the first dijet transverse momentum asymmetry measurements from Au+Au and pp collisions at RHIC. The two highest-energy back-to-back jets reconstructed from fragments with transverse momenta above 2 GeV/c display a significantly higher momentum imbalance in heavy-ion collisions than in the pp reference. When reexamined with correlated soft particles included, we observe that these dijets then exhibit a unique new feature - momentum balance is restored to that observed in pp for a jet resolution parameter of R=0.4, while rebalancing is not attained with a smaller value of R=0.2. © 2017 American Physical Society.
Keywords: Asymmetry measurements; Colliding beam accelerators; Germanium compounds; Gold compounds; Heavy ion collision; Heavy ions; Momentum; Momentum balances; Pp collisions; Rebalancing; Resolution parameters; Soft particles; Transverse momenta; dept.phy

Beam-Energy Dependence of Directed Flow of Λ, Λ , K±, Ks0, and φ in Au+Au Collisions - STAR Collaboration (Physical Review Letters, 2018)
Rapidity-odd directed-flow measurements at midrapidity are presented for Λ, Λ, K±, Ks0, and φ at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV in Au+Au collisions recorded by the Solenoidal Tracker detector at the Relativistic Heavy Ion Collider. These measurements greatly expand the scope of data available to constrain models with differing prescriptions for the equation of state of quantum chromodynamics. Results show good sensitivity for testing a picture where flow is assumed to be imposed before hadron formation and the observed particles are assumed to form via coalescence of constituent quarks. The pattern of departure from a coalescence-inspired sum rule can be a valuable new tool for probing the collision dynamics. © 2018 authors. Published by the American Physical Society.
Keywords: Au+Au collisions; Beam energies; Colliding beam accelerators; Collision dynamics; Directed flow; Elementary particles; Equation of state; Equations of state; Germanium compounds; Gold compounds; Heavy ions; High energy physics; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; Tracker detector; dept.phy; peer-reviewed

Polarization of Λ (Λ ̄) Hyperons along the Beam Direction in Au+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2019)
The Λ (Λ̄) hyperon polarization along the beam direction has been measured in Au+Au collisions at sNN=200 GeV, for the first time in heavy-ion collisions. The polarization dependence on the hyperons' emission angle relative to the elliptic flow plane exhibits a second harmonic sine modulation, indicating a quadrupole pattern of the vorticity component along the beam direction, expected due to elliptic flow. The polarization is found to increase in more peripheral collisions, and shows no strong transverse momentum (pT) dependence at pT greater than 1 GeV/c. The magnitude of the signal is about 5 times smaller than those predicted by hydrodynamic and multiphase transport models; the observed phase of the emission angle dependence is also opposite to these model predictions. In contrast, the kinematic vorticity calculations in the blast-wave model tuned to reproduce particle spectra, elliptic flow, and the azimuthal dependence of the Gaussian source radii measured with the Hanbury Brown-Twiss intensity interferometry technique reproduce well the modulation phase measured in the data and capture the centrality and transverse momentum dependence of the polarization signal. © 2019 American Physical Society.
Keywords: Azimuthal dependence; Colliding beam accelerators; Emission angle dependence; Gaussian beams; Heavy ion collision; Heavy ions; Hyperon polarization; Interferometry; Interferometry technique; Modulation; Multiphase transport; Polarization; Polarization dependence; Polarization signals; Vorticity; dept.phy; peer-reviewed

Low- p T e + e − Pair Production in Au + Au Collisions at √ s N N = 200 GeV and U + U Collisions at √ s N N = 193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e^{+}e^{-} pair production in the mass region 0.4
Keywords: dept.phy; peer-reviewed

First Observation of the Directed Flow of D0 and D0 ̄ in Au+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2019)
We report the first measurement of rapidity-odd directed flow (v1) for D0 and D0̄ mesons at midrapidity (|y|<0.8) in Au+Au collisions at sNN=200 GeV using the STAR detector at the Relativistic Heavy Ion Collider. In 10-80% Au+Au collisions, the slope of the v1 rapidity dependence (dv1/dy), averaged over D0 and D0̄ mesons, is -0.080±0.017(stat)±0.016(syst) for transverse momentum pT above 1.5 GeV/c. The absolute value of D0 meson dv1/dy is about 25 times larger than that for charged kaons, with 3.4σ significance. These data give a unique insight into the initial tilt of the produced matter, and offer constraints on the geometric and transport parameters of the hot QCD medium created in relativistic heavy-ion collisions. © 2019 American Physical Society.
Keywords: Absolute values; Au+Au collisions; Bosons; Colliding beam accelerators; Directed flow; Germanium compounds; Gold compounds; Hadrons; Heavy ions; Mid-rapidity; Relativistic Heavy Ion Collider; Relativistic heavy ion collision; Transport parameters; Transverse momenta; dept.phy; peer-reviewed

Observation of Excess J /ψ Yield at Very Low Transverse Momenta in Au+Au Collisions at sNN =200 GeV and U+ U Collisions at sNN =193 GeV - STAR Collaboration (Physical Review Letters, 2019)
We report on the first measurements of J/ψ production at very low transverse momentum (pT<0.2 GeV/c) in hadronic Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Remarkably, the inferred nuclear modification factor of J/ψ at midrapidity in Au+Au (U+U) collisions reaches about 24 (52) for pT<0.05 GeV/c in the 60%-80% collision centrality class. This noteworthy enhancement cannot be explained by hadronic production accompanied by cold and hot medium effects. In addition, the dN/dt distribution of J/ψ for the very low pT range is presented for the first time. The distribution is consistent with that expected from the Au nucleus and shows a hint of interference. Comparison of the measurements to theoretical calculations of coherent production shows that the excess yield can be described reasonably well and reveals a partial disruption of coherent production in semicentral collisions, perhaps due to the violent hadronic interactions. Incorporating theoretical calculations, the results strongly suggest that the dramatic enhancement of J/ψ yield observed at extremely low pT originates from coherent photon-nucleus interactions. In particular, coherently produced J/ψ's in violent hadronic collisions may provide a novel probe of the quark-gluon plasma. © 2019 authors. Published by the American Physical Society.
Keywords: Au+Au collisions; Colliding beam accelerators; Germanium compounds; Gold compounds; Hadronic collisions; Hadronic interactions; Isomers; Nitrogen compounds; Nuclear modification factors; Quark-gluon plasma; Semicentral collisions; Theoretical calculations; Transverse momenta; dept.phy; peer-reviewed

Kinematics of stars in the outskirts of the clouds - Casetti, Dana (2019)
I will review recent observations of the kinematics of stars in the outskirts of the Magellanic Clouds and in the Magellanic Stream, and discuss these observations in the context of the interaction of the Clouds with the Galaxy and with each other.
Keywords: dept.phy

Erratum: “understanding the effects of stellar multiplicity on the derived planet radii from transit surveys: implications for kepler, k2, and tess” (2015, apj, 805, 16) - Ciardi, David R; Beichman, Charles A; Horch, Elliott P; Howell, Steve B (The Astrophysical Journal, 2017)
Keywords: dept.phy

Author Correction: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.
Keywords: dept.phy; peer-reviewed

K2 discovers a busy bee: an unusual transiting neptune found in the beehive cluster - Obermeier, Christian; Henning, Thomas; Schlieder, Joshua E.; Crossfield, Ian J. M.; Petigura, Erik A.; Howard, Andrew W.; Sinukoff, Evan; Isaacson, Howard; Ciardi, David R.; David, Trevor J.; Hillenbrand, Lynne A.; Beichman, Charles A.; et al. (The Astronomical Journal, 2016)
Open clusters have been the focus of several exoplanet surveys, but only a few planets have so far been discovered. The Kepler spacecraft revealed an abundance of small planets around small cool stars, therefore, such cluster members are prime targets for exoplanet transit searches. Kepler's new mission, K2, is targeting several open clusters and star-forming regions around the ecliptic to search for transiting planets around their low-mass constituents. Here, we report the discovery of the first transiting planet in the intermediate-age (800 Myr) Beehive cluster (Praesepe). K2-95 is a faint (Kp = 15.5 mag) dwarf from K2's Campaign 5 with an effective temperature of 3471 ±124 K, approximately solar metallicity and a radius of 0.402± 0.050.R⊕ We detected a transiting planet with a radius of3.47+0.78 -0.53R⊕ and an orbital period of 10.134 days. We combined photometry, medium/high-resolution spectroscopy, adaptive optics/speckle imaging, and archival survey images to rule out any false-positive detection scenarios, validate the planet, and further characterize the system. The planet's radius is very unusual as M-dwarf field stars rarely have Neptune-sized transiting planets. The comparatively large radius of K2-95b is consistent with the other recently discovered cluster planets K2-25b (Hyades) and K2-33b (Upper Scorpius), indicating systematic differences in their evolutionary states or formation. These discoveries from K2 provide a snapshot of planet formation and evolution in cluster environments and thus make excellent laboratories to test differences between field-star and cluster planet populations. © 2016. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; eclipses; peer-reviewed; stars: individual (K2-95); stars: low-mass; techniques: photometric; techniques: spectroscopic

ϒ production in U + U collisions at sNN =193 GeV measured with the STAR experiment ϒ PRODUCTION in U + U COLLISIONS at ⋯ L. ADAMCZYK et al. - Adamczyk, Leszek; Adkins, J. K.; Agakishiev, G.; Aggarwal, M. M.; Ahammed, Zubayer; Alekseev, I. G.; Anderson, Derek; Aoyama, Ryo; Aparin, A.; Arkhipkin, D.; Aschenauer, E. C.; Ashraf, Muhammad Usman; et al. (Physical Review C, 2016)
Keywords: dept.phy; peer-reviewed

Proper motion of the Draco dwarf galaxy from Subaru Suprime-Cam data - Casetti-Dinescu, Dana I.; Girard, Terrence M. (Monthly Notices of the Royal Astronomical Society, 2016)
We have measured the absolute proper motion of the Draco dwarf spheroidal galaxy using Subaru Suprime-Cam images taken at three epochs, with time baselines of 4.4 and 7 yr. The magnitude limit of the proper-motion study is i = 25, thus allowing for thousands of background galaxies and Draco stars to be used to perform extensive astrometric tests and to derive the correction to an inertial reference frame. The derived proper motion is (μα, μδ) = (-0.284 ± 0.047, -0.289 ± 0.041) mas yr-1. This motion implies an orbit that takes Draco to a pericentre of ~20 kpc; a somewhat disruptive orbit suggesting that tides might account for the rising velocity-dispersion profile of Draco seen in line-of-sight velocity studies. The orbit is only marginally consistent with Draco's membership to the vast polar structure of Galactic satellites, in contrast to a recent Hubble Space Telescope proper-motion measurement that finds alignment very likely. Our study is a test case to demonstrate that deep imaging with mosaic cameras of appropriate resolution can be used for high-accuracy, ground-based proper-motion measurement. As a useful by-product of the study, we also identify two faint brown-dwarf candidates in the foreground field. © 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Astrometry; Brown dwarfs; Galaxies: dwarf; Galaxies: individual: Draco; Proper motions; dept.phy; peer-reviewed

Time reversal optical tomography: Detecting and locating tumors in an ex vivo model human breast - Wu, Binlin; Alrubaiee, M.; Gayen, S. K. (Optics and Laser Technology, 2016)
Time reversal optical tomography (TROT), a recently introduced diffuse optical imaging approach, is used to detect, locate, and obtain cross-section images of tumors inside a "model human breast." The model cancerous breast is assembled as a semi-cylindrical slab of uniform thickness using ex vivo human breast tissues with two pieces of tumors embedded in it. The experimental arrangement used a 750-nm light beam from a Ti:sapphire laser to illuminate an end face (source plane) of the sample in a multi-source probing scheme. A multi-detector signal acquisition scheme measured transmitted light intensity distribution on the other end face (detector plane). The perturbations in light intensity distribution in the detector plane were analyzed using TROT to obtain locations of the tumor pieces in three dimensions and estimate their cross sections. The estimated locations and dimensions of targets are in good agreement with the results of a corroborating magnetic resonance imaging experiment. © 2015 Elsevier Ltd. All rights reserved.
Keywords: Biological tissues; Breast Cancer; Breast cancer; Histology; Image reconstruction; Infrared devices; Infrared imaging; Inverse image reconstruction; Light propagation; Light propagation in biological tissues; Location; Magnetic resonance imaging; Medical imaging; Near-infrared imaging; Optical tomography; Sapphire; Signal processing; Thermography (imaging); Time reversal; Tissue; Tumors; dept.phy

Two new long-period giant planets from the McDonald observatory planet search and two stars with long-period radial velocity signals related to stellar activity cycles - Endl, Michael; Brugamyer, Erik; Cochran, William D.; MacQueen, Phillip J.; Robertson, Paul; Meschiari, Stefano; Ramirez, Ivan; Shetrone, Matthew D.; Gullikson, Kevin; Johnson, Marshall C.; Wittenmyer, Robert A.; Horner, Jonathan; et al. (The Astrophysical Journal, 2016)
We report the detection of two new long-period giant planets orbiting the stars HD 95872 and HD 162004 (φ1 Dra B) by the McDonald Observatory planet search. The planet HD 95872b has a minimum mass of 4.6 MJup and an orbital semimajor axis of 5.2 AU. The giant planet φ1 Dra Bb has a minimum mass of 1.5 MJup and an orbital semimajor axis of 4.4 AU. Both of these planets qualify as Jupiter analogs. These results are based on over one and a half decades of precise radial velocity (RV) measurements collected by our program using the McDonald Observatory Tull Coude spectrograph at the 2.7 m Harlan J. Smith Telescope. In the case of φ1 Dra B we also detect a long-term nonlinear trend in our data that indicates the presence of an additional giant planet, similar to the Jupiter-Saturn pair. The primary of the binary star system, φ1 Dra A, exhibits a very large amplitude RV variation due to another stellar companion. We detect this additional member using speckle imaging. We also report two cases - HD 10086 and HD 102870 (β Virginis) - of significant RV variation consistent with the presence of a planet, but that are probably caused by stellar activity, rather than reflexive Keplerian motion. These two cases stress the importance of monitoring the magnetic activity level of a target star, as long-term activity cycles can mimic the presence of a Jupiter-analog planet. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: activity; techniques: radial velocities

Refrustration and competing orders in the prototypical Dy2Ti2O7 spin ice material - Henelius, Patrik; Lin, T.; Enjalran, Matthew; Hao, Zhihao; Rau, Jeffrey G.; Altosaar, Jaan; Flicker, Felix; Yavors'kii, T.; Gingras, Michel J. P. (Physical Review B, 2016)
Spin ices, frustrated magnetic materials analogous to common water ice, have emerged over the past 15 years as exemplars of high frustration in three dimensions. Recent experimental developments aimed at interrogating anew the low-temperature properties of these systems, in particular whether the predicted transition to long-range order occurs, behoove researchers to scrutinize our current dipolar spin ice model description of these materials. In this work, we do so by combining extensive Monte Carlo simulations and mean-field theory calculations to analyze data from previous magnetization, diffuse neutron scattering, and specific-heat measurements on the paradigmatic Dy2Ti2O7 spin ice material. In this work, we also reconsider the possible importance of the nuclear specific heat Cnuc in Dy2Ti2O7. We find that Cnuc is not entirely negligible below a temperature ∼0.5 K and must therefore be taken into account in a quantitative analysis of the calorimetric data of this compound below that temperature. We find that in this material, small effective spin-spin exchange interactions compete with the magnetostatic dipolar interaction responsible for the main spin ice phenomenology. This causes an unexpected "refrustration" of the long-range order that would be expected from the incompletely self-screened dipolar interaction and which positions the material at the boundary between two competing classical long-range-ordered ground states. This allows for the manifestation of new physical low-temperature phenomena in Dy2Ti2O7, as exposed by recent specific-heat measurements. We show that among the four most likely causes for the observed upturn of the specific heat at low temperature [an exchange-induced transition to long-range order, quantum non-Ising (transverse) terms in the effective spin Hamiltonian, the nuclear hyperfine contribution, and random disorder], only the last appears to be reasonably able to explain the calorimetric data. © 2016 American Physical Society.
Keywords: CattaneoChristov heat flux; Oldroyd-B fluid; dept.phy; nonlinear analysis

197 candidates and 104 validated planets in k2's first five fields - Crossfield, Ian J M; Ciardi, David R; Petigura, Erik A; Sinukoff, Evan; Schlieder, Joshua E; Schlieder, Joshua E; Howard, Andrew W; Beichman, Charles A; Isaacson, Howard; Dressing, Courtney D; Christiansen, Jessie L; Fulton, Benjamin J; et al. (Astrophysical Journal Supplement Series, 2016)
We present 197 planet candidates discovered using data from the first year of the NASA K2 mission (Campaigns 0-4), along with the results of an intensive program of photometric analyses, stellar spectroscopy, high-resolution imaging, and statistical validation. We distill these candidates into sets of 104 validated planets (57 in multi-planet systems), false positives, and 63 remaining candidates. Our validated systems span a range of properties, with median values of RP= 2.3 R⊕, P = 8.6 days, Teff = 5300 K, and Kp = 12.7mag. Stellar spectroscopy provides precise stellar and planetary parameters for most of these systems. We show that K2 has increased by 30% the number of small planets known to orbit moderately bright stars (1-4 R R⊕, Kp = 9-13 mag). Of particular interest are planets smaller than 2 R⊕, orbiting stars brighter than Kp = 11.5 mag, 5 receiving Earth-like irradiation levels, and several multi-planet systems - including 4 planets orbiting the M dwarf K2-72 near mean-motion resonances. By quantifying the likelihood that each candidate is a planet we demonstrate that our candidate sample has an overall false positive rate of 15%-30%, with rates substantially lower for small candidates (<2R⊕) and larger for candidates with radii >8 R⊕ and/or with P<3 days. Extrapolation of the current planetary yield suggests that K2 will discover between 500 and 1000 planets in its planned four-year mission, assuming sufficient follow-up resources are available. Efficient observing and analysis, together with an organized and coherent follow-up strategy, are essential for maximizing the efficacy of planet-validation efforts for K2, TESS, and future large-scale surveys. © 2016. The American Astronomical Society. All rights reserved.
Keywords: catalogs; dept.phy; planets and satellites: fundamental parameters; planets and satellites: general; techniques: high angular resolution; techniques: photometric; techniques: spectroscopic

Three temperate neptunes orbiting nearby stars - Fulton, Benjamin J; Howard, Andrew W; Weiss, Lauren M; Sinukoff, Evan; Petigura, Erik A; Isaacson, Howard; Hirsch, Lea A; Marcy, Geoffrey W; Henry, Gregory W; Grunblatt, Samuel K; Huber, Daniel; Huber, Daniel; et al. (The Astrophysical Journal, 2016)
We present the discovery of three modestly irradiated, roughly Neptune-mass planets orbiting three nearby Solartype stars. HD 42618 b has a minimum mass of 15.4±2.4 M⊕, a semimajor axis of 0.55 au, an equilibrium temperature of 337 K, and is the first planet discovered to orbit the solar analogue host star, HD 42618. We also discover new planets orbiting the known exoplanet host stars HD 164922 and HD 143761 (p CrB). The new planet orbiting HD 164922 has a minimum mass of 12.9±1.6 M⊕ and orbits interior to the previously known Jovian mass planet orbiting at 2.1 au. HD 164922 c has a semimajor axis of 0.34 au and an equilibrium temperature of 418 K. HD 143761 c orbits with a semimajor axis of 0.44 au, has a minimum mass of 25±2 M⊕, and is the warmest of the three new planets with an equilibrium temperature of 445 K. It orbits exterior to the previously known warm Jupiter in the system. A transit search using space-based CoRoT data and ground-based photometry from the Automated Photometric Telescopes (APTs) at Fairborn Observatory failed to detect any transits, but the precise, high-cadence APT photometry helped to disentangle planetary-reflex motion from stellar activity. These planets were discovered as part of an ongoing radial velocity survey of bright, nearby, chromospherically inactive stars using the Automated Planet Finder (APF) telescope at Lick Observatory. The high-cadence APF data combined with nearly two decades of radial velocity data from Keck Observatory and gives unprecedented sensitivity to both short-period low-mass, and long-period intermediate-mass planets. © 2016. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; planetary systems; stars: individual (HD 42618, HD 164922, HD 143761)

Speckle imaging at large telescopes: current results and future prospects - Horch, Elliott P (SPIE, 2016)
In recent years, speckle imaging has proven very useful for certain problems in single-Aperture high-resolution imaging, including searching for faint stellar companions near exoplanet host stars and for satellite imaging. These developments have largely been the result of the availability of electron-multiplying CCD cameras, which allow for greater sensitivity and better photometric linearity when compared with other detectors that have comparable speed. This in turn has led to an increased use for speckle imaging at mid-sized and large telescopes. Some results of these efforts will be discussed, and the outlook for the future of speckle will be given. © 2016 SPIE.
Keywords: CCD cameras; Electron multiplying ccds; Faint Companion Detection; Future prospects; High resolution; High-Resolution Astronomy; High-resolution imaging; Image Reconstruction; Image reconstruction; Interferometry; Large telescopes; Satellite imaging; Single aperture; Speckle; Speckle Imaging; Speckle imaging; Telescopes; dept.phy

SCSI: the southern connecticut stellar interferometer - Horch, Elliott P; Weiss, Samuel A; Rupert, Justin D; Dimaio, Alex J; Nusdeo, Daniel A; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo; Giudice, Andrea (SPIE, 2016)
The construction of a new prototype visible-light intensity interferometer for use in stellar astronomy is described. The instrument is located in New Haven, Connecticut, at Southern Connecticut State University, but key components of the system are also portable and have been taken to existing research-class telescopes to maximize sensitivity and baseline. The interferometer is currently a two-station instrument, but it is easily expandable to several stations for simultaneous measurement using multiple baselines. The design features single photon avalanche diode (SPAD) arrays, which increase the throughput and signal-To-noise ratio of the instrument. Predicted system performance and preliminary observations will be discussed. © 2016 SPIE.
Keywords: Avalanche diodes; Design features; Intensity Interferometry; Interferometers; Interferometry; Particle beams; Photon Counting; Photon counting; Photons; Signal to noise ratio; Simultaneous measurement; Single Photon Avalanche Diode Arrays; Single photon avalanche diode; Single-photon avalanche diode arrays; Stars; Stellar interferometers; Timing Correlation; Ultra-High-Resolution Astronomy; Ultrahigh resolution; Visible light; dept.phy

Speckle imaging excludes low-mass companions orbiting the exoplanet host star trappist-1 - Howell, Steve B; Everett, Mark E; Horch, Elliott P; Winters, Jennifer G; Hirsch, Lea A; Nusdeo, Dan; Scott, Nicholas J (The Astrophysical Journal, 2016)
We have obtained the highest-resolution images available of TRAPPIST-1 using the Gemini-South telescope and our speckle imaging camera. Observing at 692 and 883 nm, we reached the diffraction limit of the telescope providing a best resolution of 27 mas or, at the distance of TRAPPIST-1, a spatial resolution of 0.32 au. Our imaging of the star extends from 0.32 to 14.5 au. We show that to a high confidence level, we can exclude all possible stellar and brown dwarf companions, indicating that TRAPPIST-1 is a single star. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; stars: imaging; stars: individual (TRAPPIST-1, 2MASS J23062928-0502285)

Combinatorial development of antibacterial Zr-Cu-Al-Ag thin film metallic glasses. - Liu, Yanhui; Padmanabhan, Jagannath; Cheung, Bettina; Liu, Jingbei; Chen, Zheng; Scanley, B Ellen; Wesolowski, Donna; Pressley, Mariyah; Broadbridge, Christine C; Altman, Sidney; Schwarz, Udo D; Kyriakides, Themis R; et al. (Scientific Reports, 2016)
Metallic alloys are normally composed of multiple constituent elements in order to achieve integration of a plurality of properties required in technological applications. However, conventional alloy development paradigm, by sequential trial-and-error approach, requires completely unrelated strategies to optimize compositions out of a vast phase space, making alloy development time consuming and labor intensive. Here, we challenge the conventional paradigm by proposing a combinatorial strategy that enables parallel screening of a multitude of alloys. Utilizing a typical metallic glass forming alloy system Zr-Cu-Al-Ag as an example, we demonstrate how glass formation and antibacterial activity, two unrelated properties, can be simultaneously characterized and the optimal composition can be efficiently identified. We found that in the Zr-Cu-Al-Ag alloy system fully glassy phase can be obtained in a wide compositional range by co-sputtering, and antibacterial activity is strongly dependent on alloy compositions. Our results indicate that antibacterial activity is sensitive to Cu and Ag while essentially remains unchanged within a wide range of Zr and Al. The proposed strategy not only facilitates development of high-performing alloys, but also provides a tool to unveil the composition dependence of properties in a highly parallel fashion, which helps the development of new materials by design.
Keywords: *Alloys/ch [Chemistry]; *Aluminum/ch [Chemistry]; *Anti-Bacterial Agents/ch [Chemistry]; *Combinatorial Chemistry Techniques; *Silver/ch [Chemistry]; Alloys; Alloys/pd [Pharmacology]; Aluminum; Anti-Bacterial Agents; Anti-Bacterial Agents/pd [Pharmacology]; Combinatorial Chemistry Techniques; Copper; Copper/ch [Chemistry]; Escherichia coli; Escherichia coli/de [Drug Effects]; Escherichia coli/gd [Growth & Development]; Escherichia coli/ul [Ultrastructure]; Glass; Glass/ch [Chemistry]; Microscopy, Atomic Force; Silver; Structure-Activity Relationship; Zirconium; Zirconium/ch [Chemistry]; alloy; aluminum; antiinfective agent; atomic force microscopy; chemistry; combinatorial chemistry; copper; dept.phy; drug effect; glass; growth, development and aging; peer-reviewed; silver; structure activity relation; ultrastructure; zirconium

A quintuple star system containing two eclipsing binaries - Rappaport, S; Lehmann, H; Kalomeni, B; Borkovits, T; Latham, D W; Bieryla, Allyson; Ngo, Henry; Mawet, Dimitri; Howell, Steve B; Horch, Elliott P; Jacobs, T L; Lacourse, D; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present a quintuple star system that contains two eclipsing binaries. The unusual architecture includes two stellar images separated by 11 arcsec on the sky: EPIC 212651213 and EPIC 212651234. The more easterly image (212651213) actually hosts both eclipsing binaries which are resolved within that image at 0.09 arcsec, while the westerly image (212651234) appears to be single in adaptive optics (AO), speckle imaging, and radial velocity (RV) studies. The 'A' binary is circular with a 5.1-d period, while the 'B' binary is eccentric with a 13.1-d period. The γ velocities of the A and B binaries are different by ~10 km s-1. That, coupled with their resolved projected separation of 0.09 arcsec, indicates that the orbital period and separation of the 'C' binary (consisting of A orbiting B) are ≃65 yr and ≃25 au, respectively, under the simplifying assumption of a circular orbit. Motion within the C orbit should be discernible via future RV, AO, and speckle imaging studies within a couple of years. The C system (i.e. 212651213) has an RV and proper motion that differ from that of 212651234 by only ~1.4 kms-1 and ~3 mas yr-1. This set of similar space velocities in three dimensions strongly implies that these two objects are also physically bound, making this at least a quintuple star system. © 2016 The Authors.
Keywords: Binaries: close; Binaries: eclipsing; Binaries: general; Binaries: spectroscopic; Binaries: visual; dept.phy; peer-reviewed

Differential speckle and wide-field imaging for the Gemini-North and WIYN telescopes - Scott, Nicholas J; Howell, Steve B; Horch, Elliott P (SPIE, 2016)
Two new instruments are currently being built for the Gemini-North and WIYN telescopes. They are based on the existing DSSI (Differential Speckle Survey Instrument), but the new dual-channel instruments will have both speckle and "wide-field" imaging capabilities. Nearly identical copies of the instrument will be installed as a public access permanent loan at the Gemini-N and WIYN telescopes. Many exoplanet targets will come from the NASA K2 and TESS missions. The faint limiting magnitude, for speckle observations, will remain around 16 to 17th magnitude depending on observing conditions, while wide-field, high speed imaging should be able to go to 21+. For Gemini, the instrument will be remotely operable from either the mid-level facility at Hale Pohaku or the remote operations base in Hilo. © 2016 SPIE.
Keywords: High resolution imaging; High speed imaging; High-resolution imaging; Image reconstruction; Imaging capabilities; Instrumentation; Interferometry; NASA; Remote operation; Speckle; Speckle interferometry; Survey instruments; Telescopes; Wide field imaging; dept.phy

Speckle interferometry of secondary components in nearby visual binaries - Tokovinin, Andrei; Horch, Elliott P (The Astronomical Journal, 2016)
Statistical characterization of secondary subsystems in binaries helps to distinguish between various scenarios of multiple-star formation. The Differential Speckle Survey Instrument was used at the Gemini-N telescope for several hours in 2015 July to probe the binarity of 25 secondary components in nearby solar-type binaries. Six new subsystems were resolved, with meaningful detection limits for the remaining targets. The large incidence of secondary subsystems agrees with other similar studies. The newly resolved subsystem HIP 115417 Ba,Bb causes deviations in the observed motion of the outer binary from which an astrometric orbit of Ba,Bb with a period of 117 years is deduced. © 2016. The American Astronomical Society. All rights reserved.
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: low-mass

Speckle interferometry at SOAR in 2015 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2016)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope in 2015 are provided, totaling 1303 measurements of 924 resolved binary and multiple stars, and non-resolutions of 260 targets. The separations range from 12 mas to 3.″37 (median 0.″17); the maximum measured magnitude difference is 6.7 mag. We resolved 27 pairs for the first time, including 10 as inner or outer subsystems in previously known binaries, e.g., the 50 mas pair in Cha. Newly resolved pairs are commented upon. We discuss three apparently non-hierarchical systems that have been discovered in this series, arguing that their unusual configurations are the result of projection. The resolved quadruple system HIP 71510 is also studied. © 2016. The American Astronomical Society. All rights reserved..
Keywords: binaries: general; dept.phy; peer-reviewed

Stellar companions to the exoplanet host stars HD 2638 and HD 164509 - Wittrock, Justin M; Kane, Stephen R; Horch, Elliott P; Hirsch, Lea A; Howell, Steve B; Ciardi, David R; Everett, Mark E; Teske, Johanna K (The Astronomical Journal, 2016)
An important aspect of searching for exoplanets is understanding the binarity of the host stars. It is particularly important, because nearly half of the solar-like stars within our own Milky Way are part of binary or multiple systems. Moreover, the presence of two or more stars within a system can place further constraints on planetary formation, evolution, and orbital dynamics. As part of our survey of almost a hundred host stars, we obtained images at 692 and 880 nm bands using the Differential Speckle Survey Instrument (DSSI) at the Gemini-North Observatory. From our survey, we detect stellar companions to HD-2638 and HD-164509. The stellar companion to HD-2638 has been previously detected, but the companion to HD-164509 is a newly discovered companion. The angular separation for HD-2638 is 0.512±0 002 and for HD-164509 is 0.697 0. 00 ' 2. This corresponds to a projected separation of 25.6±1.9 au and 36.5±1.9 au, respectively. By employing stellar isochrone models, we estimate the mass of the stellar companions of HD-2638 and HD-164509 to be 0.483±0.007-Me and 0.416 0.007 M, respectively, and their effective temperatures to be 3570±8K and 3450±7K, respectively. These results are consistent with the detected companions being late-type M dwarfs. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HD 2638, HD 164509); techniques: high angular resolution

Measurement of muscle food spoilage using fluorescence imaging - Wu, Binlin; Dahlberg, Kevin (Proceedings of SPIE, 2016)
Keywords: dept.phy

A new method using multiphoton imaging and morphometric analysis for differentiating chromophobe renal cell carcinoma and oncocytoma kidney tumors - Wu, Binlin; Mukherjee, Sushmita; Jain, Manu (SPIE, 2016)
Distinguishing chromophobe renal cell carcinoma (chRCC) from oncocytoma on hematoxylin and eosin images may be difficult and require time-consuming ancillary procedures. Multiphoton microscopy (MPM), an optical imaging modality, was used to rapidly generate sub-cellular histological resolution images from formalin-fixed unstained tissue sections from chRCC and oncocytoma. Tissues were excited using 780nm wavelength and emission signals (including second harmonic generation and autofluorescence) were collected in different channels between 390 nm and 650 nm. Granular structure in the cell cytoplasm was observed in both chRCC and oncocytoma. Quantitative morphometric analysis was conducted to distinguish chRCC and oncocytoma. To perform the analysis, cytoplasm and granules in tumor cells were segmented from the images. Their area and fluorescence intensity were found in different channels. Multiple features were measured to quantify the morphological and fluorescence properties. Linear support vector machine (SVM) was used for classification. Re-substitution validation, cross validation and receiver operating characteristic (ROC) curve were implemented to evaluate the efficacy of the SVM classifier. A wrapper feature algorithm was used to select the optimal features which provided the best predictive performance in separating the two tissue types (classes). Statistical measures such as sensitivity, specificity, accuracy and area under curve (AUC) of ROC were calculated to evaluate the efficacy of the classification. Over 80% accuracy was achieved as the predictive performance. This method, if validated on a larger and more diverse sample set, may serve as an automated rapid diagnostic tool to differentiate between chRCC and oncocytoma. An advantage of such automated methods are that they are free from investigator bias and variability. Copyright © 2016 SPIE.
Keywords: Artificial intelligence; Autofluorescence; Cancer diagnosis; Cells; Classification (of information); Computer aided diagnosis; Cytology; Diagnosis; Diseases; Fluorescence; Harmonic generation; Imaging techniques; Kidney cancer; Learning algorithms; Learning systems; Morphometric analysis; Multi-photon microscopy; Multiphoton microscopy; Nonlinear optics; Support vector machines; Tissue; Tumors; autofluorescence; cancer diagnosis; classification; dept.phy; imaging; kidney cancer; machine learning; morphometric analysis

Observations of binary stars with the differential speckle survey instrument. VI. Measures during 2014 at the Discovery Channel Telescope - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W.; Ciastko, Lindsay A.; Everett, Mark E.; Bjorkman, Karen S. (The Astronomical Journal, 2015)
We present the results of 938 speckle measures of double stars and suspected double stars drawn mainly from the Hipparcos Catalog, as well as 208 observations where no companion was noted. One hundred fourteen pairs have been resolved for the first time. The data were obtained during four observing runs in 2014 using the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope. The measurement precision obtained when comparing to ephemeris positions of binaries with very well-known orbits is generally less than 2 mas in separation and 0.°5 in position angle. Differential photometry is found to have internal precision of approximately 0.1 mag and to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We also estimate the detection limit in the cases where no companion was found. Visual orbital elements are derived for six systems. © 2015. The American Astronomical Society. All rights reserved.
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: interferometric; techniques: photometric

Computational nanocharacterization for combinatorially developed bulk metallic glass - Gossett, Eric; Scanley, Ellen; Liu, Yanhui; Li, Yanglin; Liu, Ze; Sohn, Sungwoo; Schroers, Jan; Broadbridge, Christine; Schwendemann, Todd C. (International Journal of High Speed Electronics and Systems, 2015)
Bulk metallic glasses synthesized at specialized facilities at Yale using magnetron cosputtering are sent to Southern Connecticut State University for elemental characterization. Characterization is done using a Zeiss Sigma VP SEM coupled with an Oxford EDS. Characterization is automated using control software provided by Oxford. Collected data is processed and visualized using computational methods developed internally. Processed data is then organized into a database suitable for web retrieval. This technique allows for the rapid characterization of a combinatorial wafer to be carried out in ~11 hours for a single wafer containing ~600 unique compounds. © 2015 World Scientific Publishing Company.
Keywords: Bulk metallic glass; Combinatorial synthesis; Computational methods; Control software; Glass; Magnetron co-sputtering; Magnetron sputtering; Metallic glass; Nano-characterization; Single wafer; Spectrography; Web retrieval; combinatorial synthesis; computational methods; dept.phy; energy dispersive X-ray spectrography; magnetron sputtering; nano-characterization; peer-reviewed

Combinatorial exploration of color in gold-based alloys - Liu, Jingbei; Liu, Yanhui; Gong, Pan; Li, Yanglin; Moore, Kimberly M.; Scanley, Ellen; Walker, Fred; Broadbridge, Christine; Schroers, Jan (Gold Bulletin, 2015)
Combinatorial approaches comprised of combinatorial magnetron co-sputtering deposition and fast screening methods are introduced to study color as a function of composition in Au-based alloys. The microstructures of the thin films and bulk alloys are identified by X-ray diffraction, and their colors of the alloys are characterized by optical reflectivity. The results reveal that when comparing microstructures and reflectivity, thin films are similar to bulk alloys. In Au-Ag-Cu solid solutions, the color of the ternary alloy follows the rule of mixture. For colors resulting from AuAl2 intermetallic, the color of an alloy scales with the percentage of the intermetallic phase and the deviation from its ideal binary composition. In the Au-Al-Cu library, we found a ∼90 % AuAl2 area fraction compositional window where copper addition can be tuned to improve mechanical properties while keeping purple color, even though Al and CuAl2 phases exist. Moreover, when comparing the color in Au-Cu-Si-Ag amorphous and crystalline state solid solution for the same composition, the colors are essentially identical. © 2015 The Author(s).
Keywords: Aluminum; Amorphous alloys; Amorphous silicon; Amorphousalloys; Binary composition; Color; Combinatorial approach; Crystalline materials; Crystalline state; Decorative thin film coating; Decorative thin films; Gold; Gold alloys; Gold based alloys; Gold coatings; Intermetallic phase; Intermetallics; Magnetron co-sputtering; Magnetrons; Microstructure; Optical reflectivity; Reflection; Silver; Silver alloys; Solid solution; Solid solutions; Thin films; X ray diffraction; dept.phy

Influence of stellar multiplicity on planet formation. III. adaptive optics imaging of kepler stars with gas giant planets - Wang, Ji; Fischer, Debra A.; Horch, Elliott P.; Xie, Ji-Wei (The Astrophysical Journal, 2015)
As hundreds of gas giant planets have been discovered, we study how these planets form and evolve in different stellar environments, specifically in multiple stellar systems. In such systems, stellar companions may have a profound influence on gas giant planet formation and evolution via several dynamical effects such as truncation and perturbation. We select 84 Kepler Objects of Interest (KOIs) with gas giant planet candidates. We obtain high-angular resolution images using telescopes with adaptive optics (AO) systems. Together with the AO data, we use archival radial velocity data and dynamical analysis to constrain the presence of stellar companions. We detect 59 stellar companions around 40 KOIs for which we develop methods of testing their physical association. These methods are based on color information and galactic stellar population statistics. We find evidence of suppressive planet formation within 20 AU by comparing stellar multiplicity. The stellar multiplicity rate (MR) for planet host stars is 0+5-0% within 20 AU. In comparison, the stellar MR is 18% ± 2% for the control sample, i.e., field stars in the solar neighborhood. The stellar MR for planet host stars is 34% ± 8% for separations between 20 and 200 AU, which is higher than the control sample at 12% ± 2%. Beyond 200 AU, stellar MRs are comparable between planet host stars and the control sample. We discuss the implications of the results on gas giant planet formation and evolution. © 2015. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; methods: observational; methods: statistical; planet-star interactions; planetary systems; planets and satellites: formation; techniques: high angular resolution

Oxide 2D electron gases as a route for high carrier densities on (001) Si - Kornblum, Lior; Jin, Eric N.; Kumah, Divine; Ernst, Alexis T.; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2015)
Two dimensional electron gases (2DEGs) formed at the interfaces of oxide heterostructures draw considerable interest owing to their unique physics and potential applications. Growing such heterostructures on conventional semiconductors has the potential to integrate their functionality with semiconductor device technology. We demonstrate 2DEGs on a conventional semiconductor by growing GdTiO3-SrTiO3 on silicon. Structural analysis confirms the epitaxial growth of heterostructures with abrupt interfaces and a high degree of crystallinity. Transport measurements show the conduction to be an interface effect, ∼9 × 1013 cm-2 electrons per interface. Good agreement is demonstrated between the electronic behavior of structures grown on Si and on an oxide substrate, validating the robustness of this approach to bridge between lab-scale samples to a scalable, technologically relevant materials system. © 2015 AIP Publishing LLC.
Keywords: D electrons; Degree of crystallinity; Electron gas; Electronic behaviors; Heterojunctions; Interface effect; Materials systems; Oxide heterostructures; Oxide substrates; Semiconducting silicon; Semiconductor devices; Silicon; Transport measurements; Two dimensional electron gas; dept.phy

A seismic and gravitationally bound double star observed by Kepler - Appourchaux, T; Antia, H M; Ball, Warrick H; Creevey, O; Lebreton, Y; Verma, Kuldeep; Vorontsov, Sergei V; Campante, T L; Campante, T L; Davies, G R; Davies, G R; Gaulme, Patrick; et al. (Astronomy and Astrophysics, 2015)
Context. Solar-like oscillations have been observed by Kepler and CoRoT in many solar-type stars, thereby providing a way to probe stars using asteroseismology. Aims. The derivation of stellar parameters has usually been done with single stars. The aim of the paper is to derive the stellar parameters of a double-star system (HIP93511), for which an interferometric orbit has been observed along with asteroseismic measurements. Methods. We used a time series of nearly two years of data for the double star to detect the two oscillation-mode envelopes that appear in the power spectrum. Using a new scaling relation based on luminosity, we derived the radius and mass of each star. We derived the age of each star using two proxies: one based upon the large frequency separation and a new one based upon the small frequency separation. Using stellar modelling, the mode frequencies allowed us to derive the radius, the mass, and the age of each component. In addition, speckle interferometry performed since 2006 has enabled us to recover the orbit of the system and the total mass of the system. Results. From the determination of the orbit, the total mass of the system is 2.34-0.33 +0.45 M⊙. The total seismic mass using scaling relations is 2.47 ± 0.07 M⊙. The seismic age derived using the new proxy based upon the small frequency separation is 3.5 ± 0.3 Gyr. Based on stellar modelling, the mean common age of the system is 2.7-3.9 Gyr. The mean total seismic mass of the system is 2.34-2.53 M⊙ consistent with what we determined independently with the orbit. The stellar models provide the mean radius, mass, and age of the stars as RA = 1.82-1.87R⊙, MA = 1.25-1.39 M⊙, AgeA = 2.6-3.5 Gyr; RB = 1.22-1.25 R⊙, MB = 1.08-1.14 M⊙, AgeB = 3.35-4.21 Gyr. The models provide two sets of values for Star A: [1.25-1.27] M⊙ and [1.34-1.39] M⊙. We detect a convective core in Star A, while Star B does not have any. For the metallicity of the binary system of Z ≈ 0.02, we set the limit between stars having a convective core in the range [1.14-1.25] M⊙. © ESO, 2015.
Keywords: Asteroseismology; Binaries: general; Interferometry; Orbits; Seismology; Separation; Speckle; Stars; Stars: evolution; Stars: solar types; asteroseismology; astrometry; binaries: general; dept.phy; stars: evolution; stars: solar-type

A kinematically-distinct RR-Lyrae overdensity in the inner regions of the milky way - Casetti-Dinescu, Dana I; Nusdeo, Daniel A; Girard, Terrence M; Korchagin, V I; Altena, William F Van (The Astrophysical Journal, 2015)
We combine the Siding Spring Survey of RR Lyrae stars with the Southern Proper Motion Catalog 4, in order to detect and kinematically characterize overdensities in the inner halo of the Milky Way. We identify one such overdensity above the Galactic plane, in quadrant 4 of the Galaxy. The overdensity extends at least 20° in longitude, has an average heliocentric distance of 8 kpc with a depth of 4 kpc, and is confined within 4 kpc of the Galactic plane. Its metallicity distribution is distinct from that of the field population having a peak at -1.3 and a pronounced tail to -2.0. Proper motions indicate a net vertical motion away from the plane, and a low orbital angular momentum. Qualitatively, these orbit properties suggest a possible association with ω Centauri's parent satellite. However, comparison to a specific ω Cen N-body disruption model does not give a good match with observations. Line of sight velocities, and more extensive N-body modeling will help clarify the nature of this overdensity. © 2015. The American Astronomical Society. All rights reserved.
Keywords: Galaxy: halo; Galaxy: kinematics and dynamics; dept.phy; stars: variables: RR Lyrae; ⚠️ Invalid DOI

Understanding the effects of stellar multiplicity on the derived planet radii from transit surveys: implications for kepler, k2, and TESS - Ciardi, David R; Beichman, Charles A; Horch, Elliott P; Howell, Steve B (The Astrophysical Journal, 2015)
We present a study on the effect of undetected stellar companions on the derived planetary radii for Kepler Objects of Interest (KOIs). The current production of the KOI list assumes that each KOI is a single star. Not accounting for stellar multiplicity statistically biases the planets toward smaller radii. The bias toward smaller radii depends on the properties of the companion stars and whether the planets orbit the primary or the companion stars. Defining a planetary radius correction factor, XR, we find that if the KOIs are assumed to be single, then, on average, the planetary radii may be underestimated by a factor of 〈XR〉 ≈ 1.5. If typical radial velocity and high-resolution imaging observations are performed and no companions are detected, then this factor reduces to 〈XR〉 ≈ 1.2. The correction factor 〈XR〉 is dependent on the primary star properties and ranges from 〈XR〉 ≈ 1.6 for A and F stars to 〈XR〉 ≈ 1.2 for K and M stars. For missions like K2 and TESS where the stars may be closer than the stars in the Kepler target sample, observational vetting (primary imaging) reduces the radius correction factor to 〈XR〉 ≈ 1.1. Finally, we show that if the stellar multiplicity rates are not accounted for correctly, then occurrence rate calculations for Earth-sized planets may overestimate the frequency of small planets by as much as 15%-20%. © 2015. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; dept.phy; planetary systems

Patterned deposition of nanoparticles using dip pen nanolithography for synthesis of carbon nanotubes - Dahlberg, Kevin; Woods, Kelly; Jenkins, Carol; Broadbridge, Christine; Schwendemann, Todd C (Materials Research Society, 2015)
Ordered carbon nanotube (CNT) growth by deposition of nanoparticle catalysts using dip pen nanolithography (DPN) is presented. DPN is a direct write, tip based lithography technique capable of multi-component deposition of a wide range of materials with nanometer precision. A Nanolnk NLP 2000 is used to pattern different catalytic nanoparticle solutions on various substrates. To generate a uniform pattern of nanoparticle clusters, various conditions need to be considered. These parameters include: the humidity in the vessel, temperature, and tip-surface dwell time. By patterning different nanoparticle solutions next to each other, identical growth conditions can be compared for different catalysts in a streamlined analysis process. Fe, Ni, and Co nanoparticle solutions patterned on silicon, mica, and graphite substrates serve as nucleation sites for CNT growth. The CNTs were synthesized by a chemical vapor deposition (CVD) reaction. Each nanoparticle patterned substrate is placed in a tube furnace held at 725°C during CNT growth. The carbon source used in the growth chamber is toluene. The toluene is injected at a rate of 5 mL/hr. Growth is observed for Fe and Ni nanoparticle patterns, but is lacking for the Co patterns. The results of these reactions provide important information regarding efficient and highly reproducible mechanisms for CNT growth. © 2015 Materials Research Society.
Keywords: Carbon nanotubes; Catalysts; Catalytic nanoparticle; Chemical vapor deposition; Chemical vapor depositions (CVD); Deposition; Dip-pen nanolithography; Lithography; Mica; Nanolithography; Nanoparticle catalysts; Nanoparticle clusters; Nanoparticle solutions; Nanoparticles; Nanotubes; Nickel; Patterned deposition; Patterned substrates; Silicate minerals; Substrates; Synthesis (chemical); Toluene; Vapor deposition; Yarn; dept.phy

High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

Research Experiences for Students: Interdisciplinary skill development to prepare the future workforce for success - Ferrari, Nicole; Jenkins, Carol; Garofano, Jacquelynn; Day, Deborah A; Schwendemann, Todd C; Broadbridge, Christine (Materials Research Society, 2015)
Research Experiences for Undergraduates (REU) programs traditionally function as a recruitment vehicle to encourage students to pursue further studies in STEM (Science, Technology, Engineering and Math) and as an opportunity for STEM majors to delve deeper into their chosen fields of study. Based on a critical examination of REU student feedback, evaluators at CRISP (Center for Research on Interface Structures and Phenomena) have found that in addition to these conventional benefits of research-based experiences, the value of interdisciplinary skill development is integral to the REU experience and these contributions may warrant a more formal evaluative definition. Using the emerging 21st Century Skills Framework, CRISP has begun conducting a series of small-scale studies in an effort to define the contribution of student research experiences in cross-disciplinary skill development and the positive effects that exposure to real-world science practices have on refinement of career decisions and vocational success. Using Likert-type survey methods, this study directly examines current and former REU students' perceptions of the importance of interdisciplinary 21st century skills such as creativity, collaboration, communication, information literacy, and problem-solving in their REU experience and their perceived value of these skills in their future and/or current careers. Through better understanding the role these "soft skills" play in student research experiences, CRISP hopes to maximize these interdisciplinary benefits within its REU program to best prepare students for the complex demands of the 21st century workplace. © 2015 Materials Research Society.
Keywords: Amphibious vehicles; Cross-disciplinary; Education; Engineering research; Functions; Information literacy; Interdisciplinary skills; Interface structures; Problem solving; Research Experiences for Undergraduates programs; Research experiences for students; Research-based experiences; Skill development; Students; dept.phy

Cutting the cord: toward wireless optical intensity interferometry - Horch, Elliott P (SPIE, 2015)
Intensity interferometry, which was first used for obtaining ultra-high-resolution image information in astronomy in the 1960's and 1970's, is now being revived using modern detectors and electronics. This paper explores the possibility of wireless optical interferometry made possible by technological advancements in timing correlation, signal processing, and detector technology. If this can be achieved, then baselines of one to several kilometers may be possible in optical interferometry in the coming years. This would improve the resolution over the current generation of amplitude-based optical interferometers by a factor of at least ten. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only. © 2015 SPIE.
Keywords: Avalanche diodes; Correlation detectors; Current generation; Detector technology; Interferometry; Optical correlation; Optical interferometer; Optical interferometry; Particle beams; Photon counting; Photons; Signal processing; Single photon avalanche diode; Single photon avalanche diodes; Technological advancement; Timing correlation; Ultra-high-resolution astronomy; Ultrahigh resolution; dept.phy

Observations of binary stars with the differential speckle survey instrument. V. toward an empirical metal-poor mass–luminosity relation - Horch, Elliott P; Altena, William F Van; Demarque, Pierre; Howell, Steve B; Everett, Mark E; Ciardi, David R; Teske, Johanna K; Henry, Todd J; Winters, Jennifer G (The Astronomical Journal, 2015)
In an effort to better understand the details of the stellar structure and evolution of metal-poor stars, the Gemini North telescope was used on two occasions to take speckle imaging data of a sample of known spectroscopic binary stars and other nearby stars in order to search for and resolve close companions. The observations were obtained using the Differential Speckle Survey Instrument, which takes data in two filters simultaneously. The results presented here are of 90 observations of 23 systems in which one or more companions was detected, and six stars where no companion was detected to the limit of the camera capabilities at Gemini. In the case of the binary and multiple stars, these results are then further analyzed to make first orbit determinations in five cases, and orbit refinements in four other cases. The mass information is derived, and since the systems span a range in metallicity, a study is presented that compares our results with the expected trend in total mass as derived from the most recent Yale isochrones as a function of metal abundance. These data suggest that metal-poor main-sequence stars are less massive at a given color than their solar-metallicity analogues in a manner consistent with that predicted from the theory. © 2015. The American Astronomical Society. All rights reserved..
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Dynamical masses of young M dwarfs: masses and orbital parameters of gj 3305 ab, the wide binary companion to the imaged exoplanet host 51 eri - Montet, Benjamin T; Bowler, Brendan P; Shkolnik, Evgenya L; Deck, Katherine M; Wang, Ji; Horch, Elliott P; Liu, Michael C; Hillenbrand, Lynne A; Kraus, Adam L; Charbonneau, David; Hillenbrand, Lynne A; Kraus, Adam L; et al. (The Astrophysical Journal, 2015)
We combine new high resolution imaging and spectroscopy from Keck/NIRC2, Discovery Channel Telescope/DSSI, and Keck/HIRES with published astrometry and radial velocities to measure individual masses and orbital elements of the GJ 3305 AB system, a young (∼20 Myr) M+M binary (unresolved spectral type M0) member of the β Pictoris moving group comoving with the imaged exoplanet host 51 Eri. We measure a total system mass of 1.11 ± 0.04 , a period of 29.03 ± 0.50 year, a semimajor axis of 9.78 ± 0.14 AU, and an eccentricity of 0.19 ± 0.02. The primary component has a dynamical mass of 0.67 ± 0.05 and the secondary has a mass of 0.44 ± 0.05 . The recently updated BHAC15 models are consistent with the masses of both stars to within Given the observed masses the models predict an age of the GJ 3305 AB system of 37 ± 9 Myr. Based on the observed system architecture and our dynamical mass measurement, it is unlikely that the orbit of 51 Eri b has been significantly altered by the Kozai-Lidov mechanism. © 2015. The American Astronomical Society. All rights reserved..
Keywords: astrometry; binaries: close; dept.phy; stars: fundamental parameters; stars: individual (GJ 3305 AB)

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Speckle interferometry at soar in 2014 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2015)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope (SOAR) telescope in 2014 are given. A total of 1641 observations were taken, yielding 1636 measurements of 1218 resolved binary and multiple stars and 577 non-resolutions of 441 targets. We resolved for the first time 56 pairs, including some nearby astrometric or spectroscopic binaries and ten new subsystems in previously known visual binaries. The calibration of the data is checked by linear fits to the positions of 41 wide binaries observed at SOAR over several seasons. The typical calibration accuracy is 0.°1 in angle and 0.3% in pixel scale, while the measurement errors are on the order of 3 mas. The new data are used here to compute 194 binary star orbits, 148 of which are improvements on previous orbital solutions and 46 are first-time orbits. © 2015. The American Astronomical Society. All rights reserved..
Keywords: binaries: general; dept.phy; peer-reviewed

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438), KOI-4742 (Kepler-442)); techniques: photometric

On the occurrence rate of hot jupiters in different stellar environments - Wang, Ji; Fischer, Debra A; Horch, Elliott P; Huang, Xu (The Astrophysical Journal, 2015)
Many hot Jupiters (HJs) are detected by the Doppler and transit techniques. From surveys using these two techniques, however, the measured HJ occurrence rates differ by a factor of two or more. Using the California Planet Survey sample and the Kepler sample, we investigate the causes for this difference in the HJ occurrence rate. First, we find that 12.8% ± 0.24% of HJs are misidentified in the Kepler mission because of photometric dilution and subgiant contamination. Second, we explore the differences between the Doppler sample and the Kepler sample that can account for the different HJ occurrence rate. Third, we discuss how to measure the fundamental HJ occurrence rates by synthesizing the results from the Doppler and Kepler surveys. The fundamental HJ occurrence rates are measures of the HJ occurrence rate as a function of stellar multiplicity and evolutionary stage, e.g., the HJ occurrence rate for single and multiple stars or for main-sequence and subgiant stars. While we find qualitative evidence that HJs occur less frequently in subgiants and multiple stellar systems, we conclude that our current knowledge of stellar properties and the stellar multiplicity rate is too limited for us to reach any quantitative result for the fundamental HJ occurrence rates. This concern extends to ηEarth, the occurrence rate of Earth-like planets. © 2015. The American Astronomical Society. All rights reserved.
Keywords: Fundamental parameters stars; Methods; Photometric techniques; Radial velocities; Solar-type stars; Statistical planets and satellites; Statistics techniques; dept.phy

Microscopy and team-based interdisciplinary materials research to achieve 21st century skills - Broadbridge, Christine; Sadowski, Thomas; Garofano, Jacquelynn; DaPonte, John S. (Microscopy and Microanalysis, 2014)
Keywords: dept.phy

Recent star formation in the leading arm of the Magellanic Stream - Casetti-Dinescu, Dana I.; Bidin, Christian Moni; Girard, Terrence M.; Méndez, Réne A.; Vieira, Katherine; Korchagin, Vladimir I.; Altena, William F. van (The Astrophysical Journal, 2014)
Strongly interacting galaxies undergo a short-lived but dramatic phase of evolution characterized by enhanced star formation, tidal tails, bridges, and other morphological peculiarities. The nearest example of a pair of interacting galaxies is the Magellanic Clouds, whose dynamical interaction produced the gaseous features known as the Magellanic Stream trailing the pair's orbit about the Galaxy, the bridge between the Clouds, and the leading arm (LA), a wide and irregular feature leading the orbit. Young, newly formed stars in the bridge are known to exist, giving witness to the recent interaction between the Clouds. However, the interaction of the Clouds with the Milky Way (MW) is less well understood. In particular, the LA must have a tidal origin; however, no purely gravitational model is able to reproduce its morphology and kinematics. A hydrodynamical interaction with the gaseous hot halo and disk of the Galaxy is plausible as suggested by some models and supporting neutral hydrogen (H I) observations. Here we show for the first time that young, recently formed stars exist in the LA, indicating that the interaction between the Clouds and our Galaxy is strong enough to trigger star formation in certain regions of the LA—regions in the outskirts of the MW disk (R ∼ 18 kpc), far away from the Clouds and the bridge.
Keywords: Galaxy: general; Magellanic Clouds; dept.phy; galaxies: interactions; stars: early-type

An analytic algorithm to calculate the inclination, ascending node, and semimajor axis of spectroscopic binary orbits using a single speckle measurement and the parallax - Docobo, Jose Angel; Campo, P P; Andrade, Manuel; Horch, Elliott P (Astrophysical Bulletin, 2014)
It is well known that in spectroscopic binary orbits, the inclination, the ascending node, and the semimajor axis remain undetermined, therefore the principal objective of this research is to establish an analytic methodology for the calculation of these parameters for spectroscopic binaries, both single-lined (SB1) and double-lined (SB2). In other words, the goal is to determine their “three-dimensional” orbits using a single speckle measurement (ρ, θ, t) and the parallax (π). Moreover, estimates of the individual masses of each system can also be obtained. The proposed algorithm was successfully applied to SB1 systems: YSC 148 (HD 37393) and CHR 225 (HD 34318), and SB2 systems: LSC 1 Aa1,2 (HD 200077) and Mkt 11 Aa, Ab (HD 358). In this late case, previously determined spectroscopic and visual orbits have been used to compare and contrast the results obtained from them with our results. The methodology presented is especially interesting for those cases in which it is only possible to resolve the spectroscopic binary in the zones of maximum angular separation by optical means thereby making it impossible to avail of sufficient observations in order to calculate the visual orbit. © Pleiades Publishing, Ltd. 2014.
Keywords: dept.phy; general; high angular resolution—techniques; interferometric—binaries; techniques

The three-dimensional orbit and physical properties of the binary COU 2031 (WDS 04464+4221, HIP 22196, HD 30090) - Docobo, Jose Angel; Griffin, R F; Tamazian, V S; Horch, Elliott P; Campo, P P (Monthly Notices of the Royal Astronomical Society, 2014)
We report a comprehensive study of the binary system COU 2031, based on simultaneous and independent astrometric visual and speckle observations and on radial-velocity measurements. The similarity of the two orbital solutions allows us to obtain not only a consistent 3D orbit and a precise value of the parallax of the system but also to determine the physical properties of the components. © 2014 The Authors.
Keywords: Binaries: spectroscopic; Binaries: visual; Stars: individual: COU 2031; dept.phy; peer-reviewed

Characterization of carbon nanotube growth via CVD synthesis from a liquid precursor - Jenkins, Carol; Cruz, Melissa; Depalma, Jen; Conroy, Michael; Benardo, Barbara; Horbachuk, Michael; Sadowski, Tom; Broadbridge, Christine; Schwendemann, Todd C (International Journal of High Speed Electronics and Systems, 2014)
As novel theories and uses of carbon nanotubes (CNT) advance, it becomes increasingly important to characterize the methods of production. One such method of CNT production uses a liquid phase precursor (hydrocarbon with nanoparticle catalyst mix) that is injected into a tube furnace with a flowing carrier gas. The CNTs are grown in high purity and are collected on the surface of the quartz tube. The system allows for a number of variables to be tested such as growth temperatures, flow rate of the carrier gas, precursor injection rates and variations of precursor mix however, here only thermal effects are considered. Under thermal conditions ranging from 500 to 850°C, multi-walled carbon nanotubes (MWCNTs) are synthesized and characterized to determine inner and outer diameter as well as tube thickness. © 2014 World Scientific Publishing Company.
Keywords: Carbon nanotube growth; Carbon nanotubes; Carbon nanotubes (CNT); Chemical vapor deposition; Chemical vapor deposition (CVD); Chemical vapor depositions (CVD); Liquid precursors; Liquid-phase precursors; Liquids; Nanoparticle catalysts; Outer diameters; Precursor injection; Thermal condition; Transmission electron microscopy; Transmission electron microscopy (TEM); Tubes (components); dept.phy; peer-reviewed

A high density two-dimensional electron gas in an oxide heterostructure on Si (001) - Jin, Eric N; Kornblum, Lior; Kumah, Divine; Zou, Ke; Broadbridge, Christine; Ngai, J H; Ahn, C H; Walker, Fred (APL Materials, 2014)
We present the growth and characterization of layered heterostructures comprised of LaTiO3 and SrTiO3 epitaxially grown on Si (001). Magnetotransport measurements show that the sheet carrier densities of the heterostructures scale with the number of LaTiO3/SrTiO3 interfaces, consistent with the presence of an interfacial 2-dimensional electron gas (2DEG) at each interface. Sheet carrier densities of 8.9 × 1014 cm-2 per interface are observed. Integration of such high density oxide 2DEGs on silicon provides a bridge between the exceptional properties and functionalities of oxide 2DEGs and microelectronic technologies. © 2014 Author(s).
Keywords: dept.phy

Limits on stellar companions to exoplanet host stars with eccentric planets - Kane, Stephen R; Howell, Steve B; Horch, Elliott P; Feng, Ying; Hinkel, Natalie R; Ciardi, David R; Everett, Mark E; Howard, Andrew W; Wright, Jason T (The Astrophysical Journal, 2014)
Though there are now many hundreds of confirmed exoplanets known, the binarity of exoplanet host stars is not well understood. This is particularly true of host stars that harbor a giant planet in a highly eccentric orbit since these are more likely to have had a dramatic dynamical history that transferred angular momentum to the planet. Here we present observations of four exoplanet host stars that utilize the excellent resolving power of the Differential Speckle Survey Instrument on the Gemini North telescope. Two of the stars are giants and two are dwarfs. Each star is host to a giant planet with an orbital eccentricity >0.5 and whose radial velocity (RV) data contain a trend in the residuals to the Keplerian orbit fit. These observations rule out stellar companions 4-8 mag fainter than the host star at passbands of 692 nm and 880 nm. The resolution and field of view of the instrument result in exclusion radii of 0.″05-1.″4, which excludes stellar companions within several AU of the host star in most cases. We further provide new RVs for the HD 4203 system that confirm that the linear trend previously observed in the residuals is due to an additional planet. These results place dynamical constraints on the source of the planet's eccentricities, place constraints on additional planetary companions, and inform the known distribution of multiplicity amongst exoplanet host stars. © 2014. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; planetary systems; stars: individual (HD 4203, HD 168443, HD 1690, HD 137759); techniques: Radial velocities; techniques: high angular resolution

High proper motion x-ray binaries from the yale southern proper motion survey - Maccarone, Thomas J.; Girard, Terrence M.; Casetti-Dinescu, Dana I. (Monthly Notices of the Royal Astronomical Society, 2014)
We discuss the results of cross-correlating catalogues of bright X-ray binaries with the Yale Southern Proper Motion Catalog (version 4.0). Several objects already known to have large proper motions from Hipparcos are recovered. Two additional objects are found which show substantial proper motions, both of which are unusual in their X-ray properties. One is IGR J17544-2619, one of the supergiant fast X-ray transients. Assuming the quoted distances in the literature for this source of about 3 kpc are correct, this system has a peculiar velocity of about 275 km s-1-greater than the velocity of a Keplerian orbit at its location of the Galaxy and in line with the expectations formed from suggestions that the supergiant fast X-ray transients should be highly eccentric. We discuss the possibility that these objects may help explain the existence of short gamma-ray bursts outside the central regions of galaxies. The other is the source 2A 1822-371, which is a member of the small class of objects which are low-mass X-ray binaries and long (i.e. >100 ms) X-ray pulsars. This system also shows both an anomalously high X-ray luminosity and a large orbital period derivative for a system with its orbital period, and some possible indications of an eccentric orbit. A coherent picture can be developed by adding in the proper motion information in which this system formed in the Perseus spiral arm of the Galaxy about 3 Myr ago and retains a slightly eccentric orbit which leads to enhanced mass transfer. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Proper motions; X-rays: binaries; dept.phy; peer-reviewed

An Earth-Sized Planet in the Habitable Zone of a Cool Star. - Quintana, Elisa; Barclay, Thomas; Raymond, Sean; Rowe, Jason; Bolmont, Emeline; Caldwell, Douglas; Howell, Steve; Kane, Stephen; Huber, Daniel; Crepp, Justin; Lissauer, Jack; Ciardi, David; et al. (Science, 2014)
The quest for Earth-like planets is a major focus of current exoplanet research. Although planets that are Earth-sized and smaller have been detected, these planets reside in orbits that are too close to their host star to allow liquid water on their surfaces. We present the detection of Kepler-186f, a 1.11 ± 0.14 Earth-radius planet that is the outermost of five planets, all roughly Earth-sized, that transit a 0.47 ± 0.05 solar-radius star. The intensity and spectrum of the star's radiation place Kepler-186f in the stellar habitable zone, implying that if Kepler-186f has an Earth-like atmosphere and water at its surface, then some of this water is likely to be in liquid form.
Keywords: Earth; Earth (Planet); Exobiology; Extraterrestrial Environment; Planets; Stars, Celestial; Water; astrobiology; astronomy; atmosphere; cosmic radiation; dept.phy; habitat use; microclimate; priority journal; review; solar system; surface property; water

Use of the gabor filter for edge detection in the analysis of zinc oxide nanowire images - Scanley, B E; Sadowski, Thomas; Pelligra, Candice; Kreider, M E; Osuji, Chinedum O; Broadbridge, Christine (Microscopy and Microanalysis, 2014)
Keywords: dept.phy

Intensity interferometry for the 21st century - Horch, Elliott P.; van Belle, G. T.; Genet, R. M.; Holenstein, B. D. (Journal of Astronomical Instrumentation, 2013)
Advances in detector technology and electronic timing capabilities in recent years have resulted in a new opportunity for ultra-high resolution in astronomy using intensity interferometry. We have been working with this technology and describe here the potential as we see it. Two separate opportunities exist at present: The use of Single Photon Avalanche Diode (SPAD) detectors with existing research-grade telescopes and photomultipliers coupled with light bucket telescopes. In the future, there may also be potential for space-based intensity interferometry. While intensity interferometry is not likely to replace amplitude-based interferometry, it does have certain advantages in terms of portability, use of large baselines, narrow-band imaging, and imaging in the blue. We see a new possibility for its use particularly in stellar astrophysics for these reasons. © 2013 World Scientific Publishing Company.
Keywords: Instrumentation: Interferometers; dept.phy; high angular resolution; techniques: Interferometric

Kepler-63b: A giant planet in a polar orbit around a young sun-like star - Sanchis-Ojeda, Roberto; Winn, Joshua N.; Marcy, Geoffrey W.; Howard, Andrew W.; Isaacson, Howard; Johnson, John Asher; Torres, Guillermo; Albrecht, Simon; Campante, Tiago L.; Chaplin, William J.; Davies, Guy R.; Lund, Mikkel N.; et al. (The Astrophysical Journal, 2013)
We present the discovery and characterization of a giant planet orbiting the young Sun-like star Kepler-63 (KOI-63, M⊙Kp = 11.6, T eff = 5576 K, M⊙ = 0.98 M⊙). The planet transits every 9.43 days, with apparent depth variations and brightening anomalies caused by large starspots. The planet's radius is 6.1 ± 0.2 R ⊕, based on the transit light curve and the estimated stellar parameters. The planet's mass could not be measured with the existing radial-velocity data, due to the high level of stellar activity, but if we assume a circular orbit, then we can place a rough upper bound of 120 M ⊙⊕ (3σ). The host star has a high obliquity (ψ = 104°), based on the Rossiter-McLaughlin effect and an analysis of starspot-crossing events. This result is valuable because almost all previous obliquity measurements are for stars with more massive planets and shorter-period orbits. In addition, the polar orbit of the planet combined with an analysis of spot-crossing events reveals a large and persistent polar starspot. Such spots have previously been inferred using Doppler tomography, and predicted in simulations of magnetic activity of young Sun-like stars. © 2013. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (Kepler-63); stars: rotation; starspots

Exoplanet characterization by proxy: A transiting 2.15 r ⊕ planet near the habitable zone of the late K dwarf Kepler-61 - Ballard, Sarah; Charbonneau, David; Fressin, Francois; Torres, Guillermo; Irwin, Jonathan; Desert, Jean-Michel; Newton, Elisabeth; Mann, Andrew W.; Ciardi, David R.; Crepp, Justin R.; Henze, Christopher E.; Bryson, Stephen T.; et al. (The Astrophysical Journal, 2013)
We present the validation and characterization of Kepler-61b: a 2.15 R ⊕ planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon a comparison with a set of spectroscopically similar stars with directly measured radii and temperatures. We apply a stellar prior drawn from the weighted mean of these properties, in tandem with the Kepler photometry, to infer a planetary radius for Kepler-61b of 2.15 ± 0.13 R ⊕ and an equilibrium temperature of 273 ± 13 K (given its period of 59.87756 ± 0.00020 days and assuming a planetary albedo of 0.3). The technique of leveraging the physical properties of nearby “proxy” stars allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had implications for the putative habitability of Kepler-61b: the planet is 10% warmer and larger than inferred from K-band spectral characterization. From the Kepler photometry, we estimate a stellar rotation period of 36 days, which implies a stellar age of >1 Gyr. We summarize the evidence for the planetary nature of the Kepler-61 transit signal, which we conclude is 30,000 times more likely to be due to a planet than a blend scenario. Finally, we discuss possible compositions for Kepler-61b with a comparison to theoretical models as well as to known exoplanets with similar radii and dynamically measured masses.
Keywords: dept.phy; eclipses; planetary systems; stars: individual (Kepler-61, KOI 1361, KIC 6960913)

Spitzer observations of gj 3470 b: a very low-density neptune-size planet orbiting a metal-rich m dwarf* - Demory, Brice-Olivier; Torres, Guillermo; Neves, V.; Rogers, Leslie A.; Gillon, Michaël; Horch, Elliott P.; Sullivan, Peter W.; Bonfils, Xavier; Delfosse, Xavier; Forveille, Thierry; Lovis, Christophe; Mayor, Michel; et al. (The Astrophysical Journal, 2013)
We present Spitzer/IRAC 4.5 μm transit photometry of GJ 3470 b, a Neptune-size planet orbiting an M1.5 dwarf star with a 3.3 day period recently discovered in the course of the HARPS M-dwarf survey. We refine the stellar parameters by employing purely empirical mass-luminosity and surface brightness relations constrained by our updated value for the mean stellar density, and additional information from new near-infrared spectroscopic observations. We derive a stellar mass of and a radius of of M* = 0.539 +0.047-0.043 M⊙ and a radius of R* = 0.568+0.037-0.031 R⊙. We determine the host star of GJ 3470 b to be metal-rich, with a metallicity of [Fe/H] = +0.20 ± 0.10 and an effective temperature of Teff = 3600 ± 100 K. The revised stellar parameters yield a planetary radius Rp= 4.83+0.22-0.21 R⊕that is 13% larger than the value previously reported in the literature. We find a planetary mass M p= 13.9+1.5-1.4 M⊕ that translates to a very low planetary density, ρp = 0.72+0.13 -0.12 g cm-3, which is 33% smaller than the original value. With a mean density half of that of GJ 436 b, GJ 3470 b is an example of a very low-density low-mass planet, similar to Kepler-11 d, Kepler-11 e, and Kepler-18 c, but orbiting a much brighter nearby star that is more conducive to follow-up studies. © 2013. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (GJ 3470); techniques: photometric; techniques: spectroscopic

The mass of KOI-94d and a relation for planet radius, mass, and incident flux - Weiss, Lauren M.; Marcy, Geoffrey W.; Rowe, Jason F.; Howard, Andrew W.; Isaacson, Howard; Fortney, Jonathan J.; Miller, Neil; Demory, Brice-Olivier; Fischer, Debra A.; Adams, Elisabeth R.; Dupree, Andrea K.; Howell, Steve B.; et al. (The Astrophysical Journal, 2013)
We measure the mass of a modestly irradiated giant planet, KOI-94d. We wish to determine whether this planet, which is in a 22 day orbit and receives 2700 times as much incident flux as Jupiter, is as dense as Jupiter or rarefied like inflated hot Jupiters. KOI-94 also hosts at least three smaller transiting planets, all of which were detected by the Kepler mission. With 26 radial velocities of KOI-94 from the W. M. Keck Observatory and a simultaneous fit to the Kepler light curve, we measure the mass of the giant planet and determine that it is not inflated. Support for the planetary interpretation of the other three candidates comes from gravitational interactions through transit timing variations, the statistical robustness of multi-planet systems against false positives, and several lines of evidence that no other star resides within the photometric aperture. We report the properties of KOI-94b (M P = 10.5 ± 4.6 M ⊕, R P = 1.71 ± 0.16 R ⊕, P = 3.74 days), KOI-94c (M P = M ⊕, R P = 4.32 ± 0.41 R ⊕, P = 10.4 days), KOI-94d (M P = 106 ± 11 M ⊕, R P = 11.27 ± 1.06 R ⊕, P = 22.3 days), and KOI-94e (M P = M ⊕, R P = 6.56 ± 0.62 R ⊕, P = 54.3 days). The radial velocity analyses of KOI-94b and KOI-94e offer marginal (>2σ) mass detections, whereas the observations of KOI-94c offer only an upper limit to its mass. Using the KOI-94 system and other planets with published values for both mass and radius (138 exoplanets total, including 35 with M P < 150 M ⊕), we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to 13 Jupiter masses: (R P/R ⊕) = 1.78(M P/M ⊕)0.53(F/erg s–1 cm–2)–0.03 for M P < 150 M ⊕, and R P/R ⊕ = 2.45(M P/M ⊕)–0.039(F/erg s–1 cm–2)0.094 for M P > 150 M ⊕. These equations can be used to predict the radius or mass of a planet.
Keywords: dept.phy; planets and satellites: composition; techniques: photometric; techniques: spectroscopic

A sub-Mercury-sized exoplanet. - Barclay, Thomas; Rowe, Jason; Lissauer, Jack; Huber, Daniel; Fressin, Francois; Howell, Steve; Bryson, Stephen; Chaplin, William; Desert, Jean-Michel; Lopez, Eric; Marcy, Geoffrey; Mullally, Fergal; et al. (Nature, 2013)
Since the discovery of the first exoplanets, it has been known that other planetary systems can look quite unlike our own. Until fairly recently, we have been able to probe only the upper range of the planet size distribution, and, since last year, to detect planets that are the size of Earth or somewhat smaller. Hitherto, no planets have been found that are smaller than those we see in the Solar System. Here we report a planet significantly smaller than Mercury. This tiny planet is the innermost of three that orbit the Sun-like host star, which we have designated Kepler-37. Owing to its extremely small size, similar to that of the Moon, and highly irradiated surface, the planet, Kepler-37b, is probably rocky with no atmosphere or water, similar to Mercury. © 2013 Macmillan Publishers Limited. All rights reserved.
Keywords: Earth; article; astronomy; atmosphere; dept.phy; irradiance; irradiation; moon; orbit determination; planetary surface; priority journal; size structure; solar system; sun; water

Observations of binary stars with the differential speckle survey instrument. iv. observations of kepler, corot, and hipparcos stars from the gemini north telescope - Horch, Elliott P.; Howell, Steve B.; Everett, Mark E.; Ciardi, David R. (The Astronomical Journal, 2012)
We present the results of 71 speckle observations of binary and unresolved stars, most of which were observed with the DSSI speckle camera at the Gemini North Telescope in 2012 July. The main purpose of the run was to obtain diffraction-limited images of high-priority targets for the Kepler and CoRoT missions, but in addition, we observed a number of close binary stars where the resolution limit of Gemini was used to better determine orbital parameters and/or confirm results obtained at or below the diffraction limit of smaller telescopes. Five new binaries and one triple system were discovered, and first orbits are calculated for other two systems. Several systems are discussed in detail. © 2012. The American Astronomical Society. All rights reserved..
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Exploring atomic-scale lateral forces in the attractive regime: a case study on graphite (0001) - Baykara, Mehmet Z.; Schwendemann, Todd C.; Albers, Boris J.; Pilet, N.; Mönig, Harry; Altman, Eric I.; Schwarz, Udo D. (Nanotechnology, 2012)
A non-contact atomic force microscopy-based method has been used to map the static lateral forces exerted on an atomically sharp Pt/Ir probe tip by a graphite surface. With measurements carried out at low temperatures and in the attractive regime, where the atomic sharpness of the tip can be maintained over extended time periods, the method allows the quantification and directional analysis of lateral forces with piconewton and picometer resolution as a function of both the in-plane tip position and the vertical tip-sample distance, without limitations due to a finite contact area or to stick-slip-related sudden jumps of tip apex atoms. After reviewing the measurement principle, the data obtained in this case study are utilized to illustrate the unique insight that the method offers. In particular, the local lateral forces that are expected to determine frictional resistance in the attractive regime are found to depend linearly on the normal force for small tip-sample distances. © 2012 IOP Publishing Ltd.
Keywords: Atomic force; Atomic force microscopy; Atomic scale; Contact areas; Directional Analysis; Frictional resistance; Graphite; Graphite surfaces; Lateral force; Low temperatures; Measurement principle; Non-contact; Normal forces; Picometer resolution; Probe tips; Slip forming; Time-periods; Tip apex; Tip-sample distance; dept.phy

Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341, 11512246, KOI 168, 1102, Kepler-23, Kepler-24); techniques: miscellaneous

Kepler-20: a sun-like star with three sub-neptune exoplanets and two earth-size candidates - Gautier, Thomas N.; Charbonneau, David; Rowe, Jason F.; Marcy, Geoffrey W.; Isaacson, Howard; Torres, Guillermo; Fressin, Francois; Rogers, Leslie A.; Désert, Jean-Michel; Buchhave, Lars A.; Latham, David W.; Quinn, Samuel N.; et al. (The Astrophysical Journal, 2012)
We present the discovery of the Kepler-20 planetary system, which we initially identified through the detection of five distinct periodic transit signals in the Kepler light curve of the host star 2MASS J19104752+4220194. From high-resolution spectroscopy of the star, we find a stellar effective temperature T eff = 5455 100 K, a metallicity of [Fe/H] = 0.01 0.04, and a surface gravity of log g = 4.4 0.1. We combine these estimates with an estimate of the stellar density derived from the transit light curves to deduce a stellar mass of M = 0.912 0.034 M and a stellar radius of R = 0.944 +0.060 -0.095 R. For three of the transit signals, we demonstrate that our results strongly disfavor the possibility that these result from astrophysical false positives. We accomplish this by first identifying the subset of stellar blends that reproduce the precise shape of the light curve and then using the constraints on the presence of additional stars from high angular resolution imaging, photometric colors, and the absence of a secondary component in our spectroscopic observations. We conclude that the planetary scenario is more likely than that of an astrophysical false positive by a factor of 2 × 105 (Kepler-20b), 1 × 105 (Kepler-20c), and 1.1 × 103 (Kepler-20d), sufficient to validate these objects as planetary companions. For Kepler-20c and Kepler-20d, the blend scenario is independently disfavored by the achromaticity of the transit: from Spitzer data gathered at 4.5 μm, we infer a ratio of the planetary to stellar radii of 0.075 0.015 (Kepler-20c) and 0.065 0.011 (Kepler-20d), consistent with each of the depths measured in the Kepler optical bandpass. We determine the orbital periods and physical radii of the three confirmed planets to be 3.70days and 1.91+0.12 -0.21 R ⊕ for Kepler-20b, 10.85days and 3.07+0.20 -0.31 R ⊕ for Kepler-20c, and 77.61days and 2.75+0.17 -0.30 R ⊕ for Kepler-20d. From multi-epoch radial velocities, we determine the masses of Kepler-20b and Kepler-20c to be 8.7 2.2 M ⊕ and 16.1 3.5 M ⊕, respectively, and we place an upper limit on the mass of Kepler-20d of 20.1 M ⊕ (2σ). © 2012 The American Astronomical Society. All rights reserved.
Keywords: dept.phy; eclipses; planetary systems

Transit timing observations from kepler: III. confirmation of 4 multiple planet systems by a fourier-domain study of anti-correlated transit timing variations - Steffen, Jason H.; Fabrycky, Daniel C.; Ford, Eric B.; Carter, Joshua A.; Désert, Jean-Michel; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Rowe, Jason F.; Ragozzine, Darin; Welsh, William F.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to confirm the planetary nature of objects in systems with multiple transiting exoplanet candidates. This method involves a Fourier-domain analysis of the deviations in the transit times from a constant period that result from dynamical interactions within the system. The combination of observed anticorrelations in the transit times and mass constraints from dynamical stability allow us to claim the discovery of four planetary systems, Kepler-25, Kepler-26, Kepler-27 and Kepler-28, containing eight planets and one additional planet candidate. © 2012 Fermi Research Alliance LLC, Contractor for the U.S. Dept of Energy Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Celestial mechanics; Methods: data analysis; Stars: individual: KIC 4349452; Stars: individual: KIC 5792202; Stars: individual: KIC 6949607; Stars: individual: KIC 9757613; dept.phy; peer-reviewed

KEPLER-21b: A 1.6 REarth planet transiting the bright oscillating F subgiant star HD179070 - Howell, Steve B.; Rowe, Jason F.; Bryson, Stephen T.; Quinn, Samuel N.; Marcy, Geoffrey W.; Isaacson, Howard; Ciardi, David R.; Chaplin, William J.; Metcalfe, Travis S.; Monteiro, Mário J. P. F. G.; Appourchaux, Thierry; Basu, Sarbani; et al. (The Astrophysical Journal, 2012)
We present Kepler observations of the bright (V = 8.3), oscillating star HD179070. The observations show transit-like events which reveal that the star is orbited every 2.8days by a small, 1.6 R Earth object. Seismic studies of HD179070 using short cadence Kepler observations show that HD179070 has a frequency-power spectrum consistent with solar-like oscillations that are acoustic p-modes. Asteroseismic analysis provides robust values for the mass and radius of HD179070, 1.34 ± 0.06 M ⊙ and 1.86 ± 0.04 R ⊙, respectively, as well as yielding an age of 2.84 ± 0.34Gyr for this F5 subgiant. Together with ground-based follow-up observations, analysis of the Kepler light curves and image data, and blend scenario models, we conservatively show at the >99.7% confidence level (3σ) that the transit event is caused by a 1.64 0.04 R Earth exoplanet in a 2.785755 ± 0.000032day orbit. The exoplanet is only 0.04 AU away from the star and our spectroscopic observations provide an upper limit to its mass of ∼10 M Earth (2σ). HD179070 is the brightest exoplanet host star yet discovered by Kepler. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (HD 179070: KIC 3632418); stars: interiors; stars: late-type; stars: magnetic field; stars: oscillations (including pulsations); techniques: photometric

Positive attitudinal shifts with the physics by inquiry curriculum across multiple implementations - Lindsey, Beth A; Hsu, Leonardo; Sadaghiani, Homeyra R; Taylor, Jack W; Cummings, Karen (Physical Review Special Topics - Physics Education Research, 2012)
Recent publications have documented positive attitudinal shifts on the Colorado Learning Attitudes about Science Survey (CLASS) among students enrolled in courses with an explicit epistemological focus. We now report positive attitudinal shifts in classes using the Physics by Inquiry (PbI) curriculum, which has only an implicit focus on student epistemologies and nature of science issues. These positive shifts have occurred in several different implementations of the curriculum, across multiple institutions and multiple semesters. In many classes, students experienced significant attitudinal shifts in the problem-solving categories of the CLASS, despite the conceptual focus of most PbI courses.
Keywords: dept.phy

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22, KIC 10593626)

Portable intensity interferometry - Horch, Elliott P; Camarata, Matthew A (2012)
A limitation of the current generation of long baseline optical interferometers is the need to make the light interfere prior to detection. This is unlike the radio regime where signals can be recorded fast enough to use electronics to accomplish the same result. This paper describes a modern optical intensity interferometer based on electronics with picosecond timing resolution. The instrument will allow for portable optical interferometry with much larger baselines than currently possible by using existing large telescopes. With modern electronics, the limiting magnitude of the technique at a 4-m aperture size becomes competitive with some amplitude-based interferometers. The instrumentation will permit a wireless mode of operation with GPS clocking technology, extending the work to extremely large baselines. We discuss the basic observing strategy, a planned observational program at the Lowell Observatory 1.8-m and 1.0-m telescopes, and the science that can realistically be done with this instrumentation. © 2012 SPIE.
Keywords: Aperture sizes; Binary star; Binary stars; Current generation; Intensity interferometry; Interferometers; Interferometry; Large telescopes; Long base line; Mode of operations; Optical intensities; Optical interferometer; Optical interferometry; Optical telescopes; Picosecond timing; Single photon avalanche diode; Single photon avalanche diodes; Stars; Stellar disks; Stellar radii; Telescopes; dept.phy

The infrared light curve of SN 2011fe in m101 and the distance to m101 - Matheson, Thomas; Joyce, Richard R; Allen, Lori E; Saha, A; Silva, David R; Woodvasey, W M; Adams, Joshua J; Anderson, R E; Beck, Tracy L; Bentz, Misty C; Bershady, Matthew A; Binkert, W S; et al. (The Astrophysical Journal, 2012)
We present near-infrared light curves of supernova (SN) 2011fe in M101, including 34 epochs in H band starting 14days before maximum brightness in the B band. The light curve data were obtained with the WIYN High-Resolution Infrared Camera. When the data are calibrated using templates of other Type Ia SNe, we derive an apparent H-band magnitude at the epoch of B-band maximum of 10.85 ± 0.04. This implies a distance modulus for M101 that ranges from 28.86 to 29.17mag, depending on which absolute calibration for Type Ia SNe is used. © © 2012. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; galaxies: distances and redshifts; galaxies: individual (M101); supernovae: individual (SN 2011fe)

Speckle Observations of Binary Stars with the Wiyn Telescope. Vii. Measures During 2008-2009 - Horch, Elliott P.; Bahi, Lizzie Anne P.; Gaulin, Joseph R.; Howell, Steve B.; Sherry, William Henry; Gallé, Roberto Baena; van Altena, William F. (The Astronomical Journal, 2011)
Five hundred thirty-one speckle measures of binary stars are reported. These data were taken mainly during the period 2008 June through 2009 October at the WIYN 3.5m Telescope at Kitt Peak and represent the last data set of single-filter speckle observations taken in the WIYN speckle program prior to the use of the current two-channel speckle camera. The astrometric and photometric precision of these observations is consistent with previous papers in this series: we obtain a typical linear measurement uncertainty of approximately 2.5mas, and the magnitude differences reported have typical uncertainties in the range of 0.1-0.14 mag. In combination with measures already in the literature, the data presented here permit the revision of the orbit of A 1634AB (= HIP 76041) and the first determination of visual orbital elements for HDS 1895 (= HIP 65982).
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Kepler-18b, c, and d: a system of three planets confirmed by transit timing variations, light curve validation, warm-spitzer photometry, and radial velocity measurements* - Cochran, William D.; Fabrycky, Daniel C.; Torres, Guillermo; Fressin, Francois; Désert, Jean-Michel; Ragozzine, Darin; Sasselov, Dimitar; Fortney, Jonathan J.; Rowe, Jason F.; Brugamyer, Erik; Bryson, Stephen T.; Carter, Joshua A.; et al. (Astrophysical Journal Supplement Series, 2011)
We report the detection of three transiting planets around a Sun-like star, which we designate Kepler-18. The transit signals were detected in photometric data from the Kepler satellite, and were confirmed to arise from planets using a combination of large transit-timing variations (TTVs), radial velocity variations, Warm-Spitzer observations, and statistical analysis of false-positive probabilities. The Kepler-18 star has a mass of 0.97 M ⊙, a radius of 1.1 R ⊙, an effective temperature of 5345K, and an iron abundance of [Fe/H] = +0.19. The planets have orbital periods of approximately 3.5, 7.6, and 14.9 days. The innermost planet "b" is a "super-Earth" with a mass of 6.9 ± 3.4 M ⊕, a radius of 2.00 ± 0.10 R ⊕, and a mean density of 4.9 ± 2.4gcm3. The two outer planets "c" and "d" are both low-density Neptune-mass planets. Kepler-18c has a mass of 17.3 ± 1.9 M ⊕, a radius of 5.49 ± 0.26 R ⊕, and a mean density of 0.59 0.07gcm 3, while Kepler-18d has a mass of 16.4 ± 1.4 M ⊕, a radius of 6.98 ± 0.33 R ⊕ and a mean density of 0.27 ± 0.03gcm3. Kepler-18c and Kepler-18d have orbital periods near a 2:1 mean-motion resonance, leading to large and readily detected TTVs. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-18, KIC 8644288, 2MASS J19521906+4444467); techniques: photometric; techniques: spectroscopic

Origin of 90° domain wall pinning in Pb(Zr0.2Ti0.8)O3 heteroepitaxial thin films - Su, Dong; Meng, Qingping; Vaz, Carlos A. F.; Han, Myung-Geun; Segal, Y.; Walker, Fred; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H. (Applied Physics Letters, 2011)
We describe a transmission-electron-microscopy study of the ferroelectric domains in an epitaxial Pb(Zr0.2Ti0.8)O3 (PZT) film grown on La0.7Sr0.3MnO3/SrTiO 3(001). We directly observe the pinning of 90 domain walls by pairs of misfit dislocations, respectively, with Burgers vectors a [100] and a [001]. Model calculations based on the elastic theory confirm our finding that, in addition to the depolarization field surrounding the dislocation, the strain field of misfit dislocation-pairs plays the primary role in the formation and pinning of a domains. © 2011 American Institute of Physics.
Keywords: Depolarization fields; Domain walls; Domain-wall pinning; Elastic theory; Epitaxial growth; Ferroelectric domains; Ferroelectricity; Heteroepitaxial thin films; Heterojunctions; Lanthanum compounds; Lead; Manganese oxide; Model calculations; PZT; Strain fields; Zirconium; dept.phy

Domain pinning and valence state switching in Pb(Zr0.2Ti0.8)O3/La0.8Sr0.2MnO3 heterostructures - Su, Dong; Vaz, Carlos A. F.; Segal, Y.; Walker, Fred; Ahn, Chong H.; Han, M-G; Sawicki, Monica; Broadbridge, Christine (Microscopy and Microanalysis, 2011)
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. III. measures below the diffraction limit of the WIYN telescope - Horch, Elliott P.; van Altena, William F.; Howell, Steve B.; Sherry, William Henry; Ciardi, David R. (The Astronomical Journal, 2011)
In this paper, we study the ability of CCD- and electron-multiplying-CCD- based speckle imaging to obtain reliable astrometry and photometry of binary stars below the diffraction limit of the WIYN 3.5 m Telescope. We present a total of 120 measures of binary stars, 75 of which are below the diffraction limit. The measures are divided into two groups that have different measurement accuracy and precision. The first group is composed of standard speckle observations, that is, a sequence of speckle images taken in a single filter, while the second group consists of paired observations where the two observations are taken on the same observing run and in different filters. The more recent paired observations were taken simultaneously with the Differential Speckle Survey Instrument, which is a two-channel speckle imaging system. In comparing our results to the ephemeris positions of binaries with known orbits, we find that paired observations provide the opportunity to identify cases of systematic error in separation below the diffraction limit and after removing these from consideration, we obtain a linear measurement uncertainty of 3-4 mas. However, if observations are unpaired or if two observations taken in the same filter are paired, it becomes harder to identify cases of systematic error, presumably because the largest source of this error is residual atmospheric dispersion, which is color dependent. When observations are unpaired, we find that it is unwise to report separations below approximately 20 mas, as these are most susceptible to this effect. Using the final results obtained, we are able to update two older orbits in the literature and present preliminary orbits for three systems that were discovered by Hipparcos. © 2011. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Observations of Binary Stars with the Differential Speckle Survey Instrument. II. Hipparcos Stars Observed in 2010 January and June - Horch, Elliott P.; Gomez, Shamilia C.; Sherry, William Henry; Howell, Steve B.; Ciardi, David R.; Anderson, Lisa M.; van Altena, William F. (The Astronomical Journal, 2011)
The results of 497 speckle observations of Hipparcos stars and selected other targets are presented. Of these, 367 were resolved into components and 130 were unresolved. The data were obtained using the Differential Speckle Survey Instrument at the WIYN 3.5 m Telescope. (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, YaleUniversity, and theNational Optical AstronomyObservatories.) Since the first paper in this series, the instrument has been upgraded so that it now uses two electron-multiplying CCD cameras. The measurement precision obtained when comparing to ephemeris positions of binaries with very well known orbits is approximately 1-2 mas in separation and better than 0.̊ 6 in position angle. Differential photometry is found to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We derive preliminary orbits for two systems. © 2011. The American Astronomical Society.
Keywords: Binaries: Visual; Techniques: High angular resolution; Techniques: Interferometric; Techniques: Photometric; dept.phy; peer-reviewed

Team-based interdisciplinary materials research using image processing - Garofano, Jacquelynn; Sadowski, Thomas; DaPonte, John S.; Broadbridge, Christine (2011)
There is an acute and well-documented need for image processing of microscopy data in materials science regarding, for example, the characterization of the structure/property relationship of a given materials system. In our work, image processing has been used as a framework for conducting interdisciplinary team-based research that effectively integrates programs within the Center for Research on Interface Structures and Phenomena (CRISP) Materials Research Science and Engineering Center (MRSEC), e.g. research experiences for undergraduates (REU), teachers (RET) and high school fellowships. This research resulted from a five-year long collaboration between CRISP and the Physics and Computer Science Departments at Southern Connecticut State University (SCSU). This paper will focus on the implementation of team-based research experiences as a vehicle for interdisciplinary science and education. Representative results of several of the studies are presented and discussed. © 2011 Materials Research Society.
Keywords: Characterization; Engineering research; High school; Image processing; Interface structures; Interfaces (materials); Materials research; Materials systems; Research experience; Science and engineering; dept.phy

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b, KIC 10264660, 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Kepler-15b: A hot jupiter enriched in heavy elements and the first kepler mission planet confirmed with the hobby-eberly telescope - Endl, Michael; Macqueen, Phillip J; Cochran, William D; Brugamyer, Erik; Buchhave, Lars A; Rowe, Jason F; Lucas, P W; Isaacson, Howard; Bryson, Steve; Howell, Steve B; Fortney, Jonathan J; Hansen, Terese; et al. (Astrophysical Journal Supplement Series, 2011)
We report the discovery of Kepler-15b (KOI-128), a new transiting exoplanet detected by NASA's Kepler mission. The transit signal with a period of 4.94days was detected in the quarter 1 (Q1) Kepler photometry. For the first time, we have used the High Resolution Spectrograph (HRS) at the Hobby-Eberly Telescope (HET) to determine the mass of a Kepler planet via precise radial velocity (RV) measurements. The 24 HET/HRS RVs and 6 additional measurements from the Fibre-fed chelle Spectrograph spectrograph at the Nordic Optical Telescope reveal a Doppler signal with the same period and phase as the transit ephemeris. We used one HET/HRS spectrum of Kepler-15 taken without the iodine cell to determine accurate stellar parameters. The host star is a metal-rich ([Fe/H]= 0.36 ± 0.07) G-type main-sequence star with Teff = 5515 ± 124 K. The semi-amplitude K of the RV orbit is 78.7+8.5 -9.5ms-1, which yields a planet mass of 0.66 ± 0.1 M Jup. The planet has a radius of 0.96 ± 0.06R Jup and a mean bulk density of 0.9 ± 0.2 gcm-3. The radius of Kepler-15b is smaller than the majority of transiting planets with similar mass and irradiation level. This suggests that the planet is more enriched in heavy elements than most other transiting giant planets. For Kepler-15b we estimate a heavy element mass of 30-40 M ⊕. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (Kepler-15, KOI-128, KIC 11359879, 2MASS J19444814+4908244); techniques: image processing; techniques: photometric; techniques: radial Velocities; techniques: spectroscopic

The WIYN Speckle Survey: Toward the Thin and Thick Disk Binary Populations - Horch, Elliott P.; van Altena, William F.; Docobo, J. A.; Tamazian, V. S.; Balega, Y. Y. (INTERNATIONAL WORKSHOP ON DOUBLE AND MULTIPLE STARS: DYNAMICS, PHYSICS, AND INSTRUMENTATION, 2011)
The WIYN Observatory speckle program has been in operation since 1997, taking data mainly with a large-format, low-noise CCD detector. However, new instrumentation, first used in 2008, has created the possibility to use two detectors simultaneously, collecting light in two different filters. The program also now has access to two electron-multiplying CCD cameras, which dramatically improve the limiting magnitude of the diffraction-limited imaging capabilities. The application of this instrumentation to an ongoing survey of the Hipparcos Double Stars and other projects is discussed. © 2011 American Institute of Physics.
Keywords: binaries: visual; dept.phy; stars: stellar populations; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Speckle camera observations for the NASA kepler mission follow-up program - Howell, Steve B; Everett, Mark E; Sherry, William Henry; Horch, Elliott P; Ciardi, David R (The Astronomical Journal, 2011)
We present the first results from a speckle imaging survey of stars classified as candidate exoplanet host stars discovered by the Kepler mission. We use speckle imaging to search for faint companions or closely aligned background stars that could contribute flux to the Kepler light curves of their brighter neighbors. Background stars are expected to contribute significantly to the pool of false positive candidate transiting exoplanets discovered by the Kepler mission, especially in the case that the faint neighbors are eclipsing binary stars. Here, we describe our Kepler follow-up observing program, the speckle imaging camera used, our data reduction, and astrometric and photometric performance. Kepler stars range from R = 8 to 16 and our observations attempt to provide background non-detection limits 5-6mag fainter and binary separations of ∼0.05-2.0 arcsec. We present data describing the relative brightness, separation, and position angles for secondary sources, as well as relative plate limits for non-detection of faint nearby stars around each of 156 target stars. Faint neighbors were found near 10 of the stars. © 2011. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; instrumentation: high angular resolution; peer-reviewed; planets and satellites: general; techniques: photometric

The atomic structure and polarization of strained SrTiO3/Si - Kumah, Divine; Reiner, James W.; Segal, Y.; Kolpak, Alexie M.; Zhang, Zhizhi; Su, Dong; Zhu, Yimei; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2010)
For thin film devices based on coupling ferroelectric polarization to charge carriers in semiconductors, the role of the interface is critical. To elucidate this role, we use synchrotron x-ray diffraction to determine the interface structure of epitaxial SrTiO3 grown on the (001) surface of Si. The average displacement of the O octahedral sublattice relative to the Sr sublattice determines the film polarization and is measured to be about 0.05 nm toward the Si, with Ti off-center displacements 0.009 nm away from the substrate. Measurements of films with different boundary conditions on the top of the SrTiO3 show that the polarization at the SrTiO3 /Si interface is dominated by oxide-Si chemical interactions. © 2010 American Institute of Physics.
Keywords: Atomic structure; Chemical interactions; Crystal atomic structure; Different boundary condition; Ferroelectric polarization; Interface structures; Polarization; Semiconducting silicon compounds; Silicon; SrTiO; Strontium alloys; Sub-lattices; Synchrotron x ray diffraction; Thin film devices; X ray diffraction; dept.phy

Kepler observations of three pre-launch exoplanet candidates: discovery of two eclipsing binaries and a new exoplanet - Howell, Steve Bruce; Rowe, Jason F.; Sherry, William; von Braun, Kaspar; Ciardi, David R.; Bryson, Stephen T.; Feldmeier, John J.; Horch, Elliott P.; van Belle, Gerard T. (The Astrophysical Journal, 2010)
Three transiting exoplanet candidate stars were discovered in a ground-based photometric survey prior to the launch of NASA's Kepler mission. Kepler observations of them were obtained during Quarter 1 of the Kepler mission. All three stars are faint by radial velocity follow-up standards, so we have examined these candidates with regard to eliminating false positives and providing high confidence exoplanet selection.We present a first attempt to exclude false positives for this set of faint stars without high-resolution radial velocity analysis. This method of exoplanet confirmation will form a large part of the Kepler mission follow-up for Jupiter-sized exoplanet candidates orbiting faint stars. Using the Kepler light curves and pixel data, as well as medium-resolution reconnaissance spectroscopy and speckle imaging, we find that two of our candidates are binary stars. One consists of a late-F star with an early M companion, while the other is a K0 star plus a late M-dwarf/brown dwarf in a 19 day elliptical orbit. The third candidate (BOKS-1) is an r = 15 G8V star hosting a newly discovered exoplanet with a radius of 1.12 RJupiter in a 3.9 day orbit. © 2010 The American Astronomical Society. All rights reserved.
Keywords: Binaries: eclipsing; Brown dwarfs; Planetary systems; dept.phy

Visualizing bone porosities using a tabletop scanning electron microscope - Krishnamoorthy, D.; DaPonte, J.; Broadbridge, C. C.; Daniel, D.; Alter, L. (Visual Information Processing XIX, 2010)
Pores are naturally occurring entities in bone. Changes in pore size and number are often associated with diseases such as Osteoporosis and even microgravity during spaceflight. Studying bone perforations may yield great insight into bone's material properties, including bone density and may contribute to identifying therapies to halt or potentially reverse bone loss. Current technologies used in this field include nuclear magnetic resonance, micro-computed tomography and the field emission scanning electron microscope (FE-SEM) 2, 5. However, limitations in each method limit further advancement. The objective of this study was to assess the effectiveness of using a new generation of analytical instruments, the TM-1000 tabletop, SEM with back-scatter electron (BSE) detector, to analyze cortical bone porosities. Hind limb unloaded and age-based controlled mouse femurs were extracted and tested in vitro for changes in pores on the periosteal surface. An important advantage of using the tabletop is the simplified sample preparation that excludes extra coatings, dehydration and fixation steps that are otherwise required for conventional SEM. For quantitative data, pores were treated as particles in order to use an analyze particles feature in the NIH ImageJ software. Several image-processing techniques for background smoothing, thresholding and filtering were employed to produce a binary image suitable for particle analysis. It was hypothesized that the unloaded bones would show an increase in pore area, as the lack of mechanical loading would affect bone-remodeling processes taking place in and around pores. Preliminary results suggest only a slight different in frequency but not in size of pores between unloaded and control femurs.
Keywords: Bone; Computerized tomography; Data processing; Electron microscopes; Electrons; Intracortical; Mammals; Particle analysis; Periosteal; Resonance; Scanning; Scanning electron microscope; Scanning electron microscopy; Threshold; Tomography; dept.phy

Kepler Planet-Detection Mission: Introduction and First Results. - Borucki, William; Koch, David; Basri, Gibor; Batalha, Natalie; Brown, Timothy; Caldwell, Douglas; Caldwell, John; Christensen-Dalsgaard, Jorgen; Cochran, William; DeVore, Edna; Dunham, Edward; Dupree, Andrea; et al. (Science, 2010)
The Kepler mission was designed to determine the frequency of Earth-sized planets in and near the habitable zone of Sun-like stars. The habitable zone is the region where planetary temperatures are suitable for water to exist on a planet's surface. During the first 6 weeks of observations, Kepler monitored 156,000 stars, and five new exoplanets with sizes between 0.37 and 1.6 Jupiter radii and orbital periods from 3.2 to 4.9 days were discovered. The density of the Neptune-sized Kepler-4b is similar to that of Neptune and GJ 436b, even though the irradiation level is 800,000 times higher. Kepler-7b is one of the lowest-density planets (∼0.17 gram per cubic centimeter) yet detected. Kepler-5b, -6b, and -8b confirm the existence of planets with densities lower than those predicted for gas giant planets.
Keywords: Jupiter; article; astronomy; astrophysics; density; dept.phy; gas; irradiation; planetary atmosphere; planetary surface; priority journal; spacecraft; sun; temperature; water

Beta-Test Data On An Assessment Of Textbook Problem Solving Ability: An Argument For Right∕Wrong Grading? - Cummings, Karen; Marx, Jeffrey D.; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 PHYSICS EDUCATION RESEARCH CONFERENCE, 2010)
We have developed an assessment of students' ability to solve standard textbook style problems and are currently engaged in the validation and revision process. The assessment covers the topics of force and motion, conservation of momentum and conservation of energy at a level consistent with most calculus-based, introductory physics courses. This tool is discussed in more detail in an accompanying paper by Marx and Cummings. [1] Here we present preliminary beta-test data collected at four schools during the 2009/2010 academic year. Data include both pre- and post-instruction results for introductory physics courses as well as results for physics majors in later years. In addition, we present evidence that right/wrong grading may well be a perfectly acceptable grading procedure for a course-level assessment of this type. © 2010 American Institute of Physics.
Keywords: Problem solving in physics; assessment; dept.phy; introductory physics; right/wrong grading

Bridging the length scales between lithographic patterning and self assembly mechanisms in fabrication of semiconductor nanostructure arrays - Hull, Robert; Floro, J A; Gherasimova, M; Graham, J; Gray, J L; Portavoce, A; Ross, Frances M; Thorp, J (Journal of Physics: Conference Series, 2010)
We employ focused ion beam patterning of single crystal Si(100) surfaces to template the assembly of Ge(Si) nanostructure arrays. The evolution and final structures of the templated arrays are determined by combinations of transmission electron, low energy electron microscope, focused ion beam and scanning probe microscopies. It is shown how the positions of individual nanostructures may be controlled to the order of 10 nm. However, to achieve controlled spacings between elements that are in the 10 nm range requires careful matching of the characteristic lengths scales of self assembly mechanisms to the length scales of the external lithographic "forcing functions". © 2010 IOP Publishing Ltd.
Keywords: Assembly mechanism; Characteristic length; Electrons; Focused ion beams; Germanium; Ion beams; Lithographic patterning; Low energy electron microscopes; Nanostructure arrays; Nanostructures; Self assembly; Semiconductor nanostructures; Silicon wafers; Single crystal surfaces; Single crystals; Single-crystal Si; Transmission electron; dept.phy

Development of a Survey Instrument to Gauge Students’ Problem-Solving Abilities - Marx, Jeffrey; Cummings, Karen; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 PHYSICS EDUCATION RESEARCH CONFERENCE, 2010)
In this paper we discuss the early stages of development of a survey instrument to assess students' problem-solving abilities in a first-term, undergraduate, calculus-based physics course. Specifically, we present our motivation for the development of such a survey, details of a preliminary version of the survey, and some sample items. © 2010 American Institute of Physics.
Keywords: Problem-solving; assessment; dept.phy; introductory physics

Comparison of the ability of quantitative parameters to differentiate surface texture of Atomic Force Microscope (AFM) images - Niedzielski, Bethany; Broadbridge, Christine; Daponte, John S; Gherasimova, Maria (2010)
The purpose of this study was to compare the ability of several texture analysis parameters to differentiate textured samples from a smooth control on images obtained with an Atomic Force Microscope (AFM). Surface roughness plays a major role in the realm of material science, especially in integrated electronic devices. As these devices become smaller and smaller, new materials with better electrical properties are needed. New materials with smoother surface morphology have been found to have superior electrical properties than their rougher counterparts. Therefore, in many cases surface texture is indicative of the electrical properties that material will have. Physical vapor deposition techniques such as Jet Vapor Deposition and Molecular Beam Epitaxy are being utilized to synthesize these materials as they have been found to create pure and uniform thin layers. For the current study, growth parameters were varied to produce a spectrum of textured samples. The focus of this study was the image processing techniques associated with quantifying surface texture. As a result of the limited sample size, there was no attempt to draw conclusions about specimen processing methods. The samples were imaged using an AFM in tapping mode. In the process of collecting images, it was discovered that roughness data was much better depicted in the microscope's "height" mode as opposed to "equal area" mode. The AFM quantified the surface texture of each image by returning RMS roughness and the first order histogram statistics of mean roughness, standard deviation, skewness, and kurtosis. Color images from the AFM were then processed on an off line computer running NIH ImageJ with an image texture plug in. This plug in produced another set of first order statistics computed from each images' histogram as well as second order statistics computed from each images' cooccurrence matrix. The second order statistics, which were originally proposed by Haralick, include contrast, angular second moment, correlation, inverse difference moment, and entropy. These features were computed in the 0°, 45°, 90°, and 135° directions. The findings of this study propose that the best combination of quantitative texture parameters is standard deviation, 0° inverse difference moment, and 0° entropy, all of which are obtained from the NIH ImageJ texture plug in. © 2010 Copyright SPIE - The International Society for Optical Engineering.
Keywords: AFM; Angular second moment; Atomic force microscopes; Atomic force microscopy; Cluster analysis; Co-occurrence-matrix; Color images; Computer vision; Crystal growth; Deposition; Electric properties; Electrical property; First order; First-order statistics; Graphic methods; Growth parameters; Histogram statistics; Image processing technique; Image texture; Imaging systems; Integrated electronics; Inverse differences; Jet vapor depositions; Material science; Materials; Mean roughness; Microscopes; Molecular beam epitaxy; Molecular beams; New material; Photoresists; Physical vapor deposition; Plug-ins; Processing; Processing method; Quantitative parameters; RMS roughness; Regression analysis; Sample sizes; Second order statistics; Smooth control; Standard deviation; Statistics; Surface morphology; Surface roughness; Surface textures; Surfaces; Tapping modes; Texture analysis; Textures; Thin layers; dept.phy

Valence electron energy-loss spectroscopy of ultrathin SrTiO3 films grown on silicon (100) single crystal - Su, Dong; Yang, Bo; Jiang, Nan; Sawicki, Monica; Broadbridge, Christine; Couillard, M; Reiner, James W; Walker, Fred; Ahn, C H; Zhu, Yimei (Applied Physics Letters, 2010)
Valence electron energy-loss spectroscopy is used to investigate the plasmon excitations of ultrathin SrTiO3 sandwiched between amorphous Si and crystalline Si. Two plasmon excitations were observed, one at 15.8 eV and the other at 28.7 eV. Our calculations, based on dielectric-function theory, suggest that the former peak originates from the coupling of the Si layers and is related to the geometry of the structure, and the latter peak results from the SrTiO3 bulk plasmon after a redshift. Our findings demonstrate the value of valence electron energy-loss spectroscopy in detecting a local change in the effective electron mass. © 2010 American Institute of Physics.
Keywords: Amorphous Si; Amorphous silicon; Crystalline Si; Dissociation; Electron energy loss spectroscopy; Electron scattering; Electrons; Function theory; Plasmon excitations; Plasmons; Red shift; Si layer; Silicon (100); Silicon wafers; Single crystals; SrTiO; Strontium alloys; Ultra-thin; Valence electron energy-loss spectroscopies; dept.phy

Complex oxide interfaces: determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy (adv. mater. 26–27/2010) - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
Keywords: dept.phy

Determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
A method has been developed to use the finite escape depth of the photoelectrons emitted in ultraviolet photoemission spectroscopy (UPS) to determine the electronic density-of-states at the interface between two dissimilar metal oxides. Ultrathin films of one oxide are grown heteroepitaxially, one monolayer at a time, on a single-crystal substrate of the other oxide, and UPS spectra are taken after each complete monolayer. By comparing experimental UPS spectra with calculated spectra based on specific models of the interfacial structure, the interfacial density-of-states can be extracted. The two oxide systems studied here are NiO-Fe 3O 4 and CoO-Fe 3O 4. The former system is found to have an atomically abrupt interface, with no significant density of interface states. For CoO, however, an interfacial electronic spectrum, different from that of either the substrate or the overlayer, is found. The spatial extent and possible origin of those interfacial states is discussed. © 2010 WILEY-VCH Verlag GmbH &. Co. KGaA, Weinheim.
Keywords: Cobalt; Cobalt compounds; Density of interface state; Dissimilar metals; Electron energy levels; Electronic density; Electronic spectrum; Electronic structure; Emission spectroscopy; Escape depth; Ferumoxytol; Interfacial density; Interfacial state; Interfacial structures; Luminescence of organic solids; Models, Molecular; Monolayers; Nickel; Oxide films; Oxide systems; Oxide-oxide interfaces; Oxides; Photoelectron Spectroscopy; Photoelectron spectroscopy; Photoemission; Photoemission spectroscopy; Single-crystal substrates; Smelting; Spatial extent; UPS spectra; Ultrathin films; Ultraviolet photoemission spectroscopy; X ray photoelectron spectroscopy; article; chemical structure; chemistry; cobalt; cobalt oxide; dept.phy; ferumoxytol; nickel; nickel monoxide; oxide

Charge-dependent pair correlations relative to a third particle in p + Au and d + Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2019)
Quark interactions with topological gluon configurations can induce chirality imbalance and local parity violation in quantum chromodynamics. This can lead to electric charge separation along the strong magnetic field in relativistic heavy-ion collisions – the chiral magnetic effect (CME). We report measurements by the STAR collaboration of a CME-sensitive observable in p+Au and d+Au collisions at 200 GeV, where the CME is not expected, using charge-dependent pair correlations relative to a third particle. We observe strong charge-dependent correlations similar to those measured in heavy-ion collisions. This bears important implications for the interpretation of the heavy-ion data.
Keywords: dept.phy; peer-reviewed

A kinematically cold structure of candidate young OB stars toward the anticenter - Casetti-Dinescu, Dana I.; Girard, Terrence M. (The Astrophysical Journal, 2019)
We combine Galaxy Evolution Explorer and Gaia DR2 catalogs to track star formation in the outskirts of our Galaxy. Using photometry, proper motions, and parallaxes we identify a structure of ∼300 OB-type candidates located between 12 and 15 kpc from the Galactic center that are kinematically cold. The structure is located between l =120° and 200°, above the plane up to ∼700 pc and below the plane to ∼1 kpc. The bulk motion is disklike; however, we measure a mean upward vertical motion of 5.7 +0.4 km s-1, and a mean outward radial motion of between 8 and 16 km s-1. The velocity dispersion along the least dispersed of its proper-motion axes (perpendicular to the Galactic disk) is 6.0 +0.3 km s-1, confirming the young age of this structure. While spatially encompassing the outer spiral arm of the Galaxy, this structure is not a spiral arm. Its explanation as the Milky Way warp is equally unsatisfactory. The structure's vertical extent, mean kinematics, and asymmetry with respect to the plane indicate that its origin is more akin to a wobble generated by a massive satellite perturbing the Galaxy's disk. The mean stellar ages in this outer structure indicate the event took place some 200 Myr ago. © 2019. The American Astronomical Society. All rights reserved..
Keywords: dept.phy

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

High-resolution imaging transit photometry of Kepler-13AB - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Horch, Elliott P.; Stephens, Andrew (The Astronomical Journal, 2019)
Using the high-resolution imaging instrument, 'Alopeke, at the Gemini-N telescope, we obtained simultaneous two-channel time-series observations of the binary exoplanet host star Kepler13-AB. Our optical observations were obtained during a transit event of the exoplanet Kepler-13b and light curves were produced using both speckle interferometric and aperture photometry techniques. Both techniques confirm that the transiting object orbits the star Kepler-13A while different transit depths are seen across the optical wavelength range, being ∼2 times deeper in the blue. These measurements, as well as mass determinations in the literature, are consistent with Kepler-13b being a highly irradiated gas giant with a bloated atmosphere. Our observations highlight the ability of high-resolution speckle imaging to not only assess binarity in exoplanet host stars but robustly determine which of the stars the transiting object actually orbits. © 2019. The American Astronomical Society. All rights reserved.
Keywords: binaries: close; dept.phy; galaxies: photometry; instrumentation: high angular resolution; peer-reviewed; planetary systems; techniques: image processing

Collision-energy dependence of second-order off-diagonal and diagonal cumulants of net-charge, net-proton, and net-kaon multiplicity distributions in Au + Au collisions - STAR Collaboration (Physical Review C, 2019)
We report the first measurements of a complete second-order cumulant matrix of net-charge, net-proton, and net-kaon multiplicity distributions for the first phase of the beam energy scan program at the Relativistic Heavy Ion Collider. This includes the centrality and, for the first time, the pseudorapidity window dependence of both diagonal and off-diagonal cumulants in Au+Au collisions at √sNN= 7.7–200 GeV. Within the available acceptance of |η|<0.5, the cumulants grow linearly with the pseudorapidity window. Relative to the corresponding measurements in peripheral collisions, the ratio of off-diagonal over diagonal cumulants in central collisions indicates an excess correlation between net-charge and net-kaon, as well as between net-charge and net-proton. The strength of such excess correlation increases with the collision energy. The correlation between net-proton and net-kaon multiplicity distributions is observed to be negative at √sNN= 200 GeV and change to positive at the lowest collision energy. Model calculations based on nonthermal (UrQMD) and thermal (HRG) production of hadrons cannot explain the data. These measurements will help map the quantum chromodynamics phase diagram, constrain hadron resonance gas model calculations and provide new insights on the energy dependence of baryon-strangeness correlations.
Keywords: dept.phy; peer-reviewed

Speckle Interferometry at SOAR in 2018 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Horch, Elliott P.; Briceño, Cesar (The Astronomical Journal, 2019)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope (SOAR) in 2018 are given, totaling 3097 measurements of 2427 resolved pairs with separations from 11 mas to 5.″9 (median 0.″15, magnitude difference up to 7 mag) and nonresolutions of 624 targets. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. Also, pre-main-sequence stars in the Orion OB1 association were surveyed, resolving 26 out of 118 targets. In addition, we report the discovery of 35 new companions among field visual multiples (some of which are likely optical) and first-time resolutions of another 31 pairs. By combining the measurements given here with the published ones, we computed 76 orbits for the first time and updated orbital elements of 34 visual binaries. Their periods range from 0.65 to 1100 yr, and their quality varies from first tentative solutions of grade 5 to accurate elements of grades 1 and 2. Finally, a list of 53 spurious pairs discovered by various techniques and unresolved at SOAR is given. © 2019. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; material: machine-readable tables; peer-reviewed

Optical biopsy identification and grading of gliomas using label-free visible resonance Raman spectroscopy. - Zhou, Yan; Liu, Cheng-Hui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Wang, Kai; Zhang, Chunyuan; Zhao, Mingyue; Zong, Rui; Zhang, Lin; Shi, Lingyan; et al. (Journal of biomedical optics, 2019)
Glioma is one of the most refractory types of brain tumor. Accurate tumor boundary identification and complete resection of the tumor are essential for glioma removal during brain surgery. We present a method based on visible resonance Raman (VRR) spectroscopy to identify glioma margins and grades. A set of diagnostic spectral biomarkers features are presented based on tissue composition changes revealed by VRR. The Raman spectra include molecular vibrational fingerprints of carotenoids, tryptophan, amide I/II/III, proteins, and lipids. These basic in situ spectral biomarkers are used to identify the tissue from the interface between brain cancer and normal tissue and to evaluate glioma grades. The VRR spectra are also analyzed using principal component analysis for dimension reduction and feature detection and support vector machine for classification. The cross-validated sensitivity, specificity, and accuracy are found to be 100%, 96.3%, and 99.6% to distinguish glioma tissues from normal brain tissues, respectively. The area under the receiver operating characteristic curve for the classification is about 1.0. The accuracies to distinguish normal, low grade (grades I and II), and high grade (grades III and IV) gliomas are found to be 96.3%, 53.7%, and 84.1% for the three groups, respectively, along with a total accuracy of 75.1%. A set of criteria for differentiating normal human brain tissues from normal control tissues is proposed and used to identify brain cancer margins, yielding a diagnostic sensitivity of 100% and specificity of 71%. Our study demonstrates the potential of VRR as a label-free optical molecular histopathology method used for in situ boundary line judgment for brain surgery in the margins.
Keywords: *Biomarkers, Tumor/me [Metabolism]; *Brain Neoplasms/me [Metabolism]; *Brain Neoplasms/pa [Pathology]; *Glioma/me [Metabolism]; *Glioma/pa [Pathology]; *Spectrum Analysis, Raman/mt [Methods]; Amides; Amino acids; Biomarkers; Biomarkers, Tumor; Biomarkers, Tumor/ch [Chemistry]; Biopsy; Brain; Brain Neoplasms; Brain Neoplasms/su [Surgery]; Brain/me [Metabolism]; Brain/pa [Pathology]; Brain/su [Surgery]; Cancer grades; Cancer margins; Carotenoids; Carotenoids/me [Metabolism]; Diseases; Glioblastoma; Glioblastomas; Glioma; Glioma/su [Surgery]; Gliomas; Grading; Histology; Histopathology; Humans; Label free; Label-free; Lipid Metabolism; Margins of Excision; Neoplasm Grading; Nerve Tissue Proteins; Nerve Tissue Proteins/ch [Chemistry]; Nerve Tissue Proteins/me [Metabolism]; Optical Phenomena; Optical biopsies; Optical biopsy; Pigments; Principal Component Analysis; Principal component analysis; Protein Structure, Secondary; Raman spectrometry; Resonance; Resonance Raman; Spectrum Analysis, Raman; Support Vector Machine; Support vector machines; Surgery; Tryptophan; Tryptophan/me [Metabolism]; Tumors; brain; brain tumor; cancer grading; carotenoid; chemistry; dept.phy; glioma; human; light related phenomena; lipid metabolism; metabolism; nerve protein; pathology; peer-reviewed; principal component analysis; procedures; protein secondary structure; support vector machine; surgical margin; tryptophan; tumor marker

Beam energy dependence of (anti-)deuteron production in Au + Au collisions at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2019)
We report the energy dependence of mid-rapidity (anti-)deuteron production in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV, measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider. The yield of deuterons is found to be well described by the thermal model. The collision energy, centrality, and transverse momentum dependence of the coalescence parameter B2 are discussed. We find that the values of B2 for antideuterons are systematically lower than those for deuterons, indicating that the correlation volume of antibaryons is larger than that of baryons at √sNN from 19.6 to 39 GeV. In addition, values of B2 are found to vary with collision energy and show a broad minimum around √sNN=20–40 GeV, which might imply a change of the equation of state of the medium in these collisions.
Keywords: dept.phy; peer-reviewed

The DESI fiber view camera system - Baltay, C.; Rabinowitz, D.; Besuner, R.; Casetti, D.; Emmet, W.; Fagrelius, P.; Girard, T.; Heetderks, H.; Lampton, M.; Lathem, A.; Levi, M.; Padmanabhan, N.; et al. (Publications of the Astronomical Society of the Pacific, 2019)
Keywords: dept.phy; peer-reviewed

Detection of planetary and stellar companions to neighboring stars via a combination of radial velocity and direct imaging techniques - Kane, Stephen R.; Dalba, Paul A.; Li, Zhexing; Horch, Elliott P.; Hirsch, Lea A.; Horner, Jonathan; Wittenmyer, Robert A.; Howell, Steve B.; Everett, Mark E.; Butler, R. Paul; Tinney, Christopher G.; Carter, Brad D.; et al. (The Astronomical Journal, 2019)
The sensitivities of radial velocity (RV) surveys for exoplanet detection are extending to increasingly longer orbital periods, where companions with periods of several years are now being regularly discovered. Companions with orbital periods that exceed the duration of the survey manifest in the data as an incomplete orbit or linear trend, a feature that can either present as the sole detectable companion to the host star, or as an additional signal overlain on the signatures of previously discovered companion(s). A diagnostic that can confirm or constrain scenarios in which the trend is caused by an unseen stellar rather than planetary companion is the use of high-contrast imaging observations. Here, we present RV data from the Anglo-Australian Planet Search (AAPS) for 20 stars that show evidence of orbiting companions. Of these, six companions have resolved orbits, with three that lie in the planetary regime. Two of these (HD 92987b and HD 221420b) are new discoveries. Follow-up observations using the Differential Speckle Survey Instrument (DSSI) on the Gemini South telescope revealed that 5 of the 20 monitored companions are likely stellar in nature. We use the sensitivity of the AAPS and DSSI data to place constraints on the mass of the companions for the remaining systems. Our analysis shows that a planetary-mass companion provides the most likely self-consistent explanation of the data for many of the remaining systems.
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: radial velocities

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830, TOI-175); techniques: photometric

Formation and stability of complex metallic phases including quasicrystals explored through combinatorial methods - Wolf, Witor; Kube, Sebastian A.; Sohn, Sungwoo; Xie, Yujun; Cha, Judy J.; Scanley, B. Ellen; Kiminami, Claudio Shyinti; Bolfarini, Claudemiro; Botta, Walter José; Schroers, Jan (Scientific Reports, 2019)
Aluminum-based quasicrystals typically form across narrow composition ranges within binary to quaternary alloys, which makes their fabrication and characterization challenging. Here, we use combinatorial approaches together with fast characterization techniques to study a wide compositional range including known quasicrystal forming compositions. Specifically, we use magnetron co-sputtering to fabricate libraries of ~140 Al-Cu-Fe and ~300 Al-Cu-Fe-Cr alloys. The alloys compositions are measured through automated energy dispersive X-ray spectroscopy. Phase formation and thermal stability are investigated for different thermal processing conditions (as-sputtered and annealed at 400 °C, 520 °C and 600 °C for Al-Cu-Fe libraries; annealed at 600 °C for Al-Cu-Fe-Cr libraries) using automated X-ray diffraction and transmission electron microscopy. In both systems the compositional regions across which the quasicrystalline phase forms are identified. In particular, we demonstrate that the quasicrystalline phase forms across an unusually broad composition range in the Al-Cu-Fe-Cr system. Additionally, some of the considered alloys vitrify during sputtering, which also allows us to study their nucleation behavior. We find that phases with polytetrahedral symmetry, such as the icosahedral quasicrystal and the λ-Al 13 Fe 4 phase, exhibit higher nucleation rates but lower growth rates, as compared to other phases with a lower degree of polytetrahedral order. Altogether, the here used combinatorial approach is powerful to identify compositional regions of quasicrystals. © 2019, The Author(s).
Keywords: dept.phy

Azimuthal harmonics in small and large collision systems at RHIC top energies - STAR Collaboration (Physical Review Letters, 2019)
The first (vfluc1), second (v2), and third (v3) harmonic coefficients of the azimuthal particle distribution at midrapidity are extracted for charged hadrons and studied as a function of transverse momentum (pT) and mean charged particle multiplicity density ⟨Nch⟩ in U+U (√sNN=193 GeV), Au+Au, Cu+Au, Cu+Cu, d+Au, and p+Au collisions at √sNN=200 GeV with the STAR detector. For the same ⟨Nch⟩, the vfluc1 and v3 coefficients are observed to be independent of the collision system, while v2 exhibits such a scaling only when normalized by the initial-state eccentricity (ϵ2). The data also show that ln(v2/ϵ2) scales linearly with ⟨Nch⟩−1/3. These measurements provide insight into initial-geometry fluctuations and the role of viscous hydrodynamic attenuation on vn from small to large collision systems.
Keywords: Azimuthal harmonics; Charged hadrons; Charged particle multiplicities; Charged particles; Colliding beam accelerators; Collision systems; Germanium compounds; Gold compounds; Harmonic coefficients; Initial state; Particle distributions; Transverse momenta; dept.phy; peer-reviewed

Collision-energy dependence of pt correlations in Au + Au collisions at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2019)
We present two-particle pt correlations as a function of event centrality for Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV at the Relativistic Heavy Ion Collider using the STAR detector. These results are compared to previous measurements from CERES at the Super Proton Synchrotron and from ALICE at the Large Hadron Collider. The data are compared with UrQMD model calculations and with a model based on a Boltzmann-Langevin approach incorporating effects from thermalization. The relative dynamical correlations for Au+Au collisions at √sNN=200 GeV show a power-law dependence on the number of participant nucleons and agree with the results for Pb+Pb collisions at √sNN=2.76TeV from ALICE. As the collision energy is lowered from √sNN=200 to 7.7 GeV, the centrality dependence of the relative dynamical correlations departs from the power-law behavior observed at the higher collision energies. In central collisions, the relative dynamical correlations increase with collision energy up to √sNN=200 GeV in contrast to previous measurements that showed little dependence on the collision energy.
Keywords: dept.phy; peer-reviewed

Discovery of a compact companion to a nearby star - Kane, Stephen R.; Dalba, Paul A.; Horner, Jonathan; Li, Zhexing; Wittenmyer, Robert A.; Horch, Elliott P.; Howell, Steve B.; Everett, Mark E. (The Astrophysical Journal, 2019)
Radial velocity (RV) searches for exoplanets have surveyed many of the nearest and brightest stars for long-term velocity variations indicative of a companion body. Such surveys often detect high-amplitude velocity signatures of objects that lie outside the planetary mass regime, most commonly those of a low-mass star. Such stellar companions are frequently discarded as false-alarms to the main science goals of the survey, but high-resolution imaging techniques can be employed to either directly detect or place significant constraints on the nature of the companion object. Here, we present the discovery of a compact companion to the nearby star HD 118475. Our Anglo-Australian Telescope RV data allow the extraction of the full Keplerian orbit of the companion, which is found to have a minimum mass of 0.445 M o. Follow-up speckle imaging observations at the predicted time of maximum angular separation rule out a main-sequence star as the source of the RV signature at the 3.3σ significance level, implying that the companion must be a low-luminosity compact object, most likely a white dwarf. We provide an isochrone analysis combined with our data that constrain the possible inclinations of the binary orbit. We discuss the eccentric orbit of the companion in the context of tidal circularization timescales and show that non-circular orbit was likely inherited from the progenitor. Finally, we emphasize the need for utilizing such an observation method to further understand the demographics of white dwarf companions around nearby stars. © 2019. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; stars: individual (HD 118475); techniques: high angular resolution; techniques: radial velocities; white dwarfs

Distinguish chromophobe renal cell carcinoma and renal oncocytoma based on analysis of multiphoton microscopic images using convolutional neural network - Icaza, Michael; Judd, Nicolas; Jain, Manu; Mukherjee, Sushmita; Wu, Binlin (Optical Biopsy XVII: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2019)
Convolutional neural networks (CNN) are a class of machine learning model that are especially well suited for imagebased tasks. In this study, we design and train a CNN on tissue samples imaged using Multi-Photon Microscopy (MPM) and show that the model can distinguish between chromophobe renal cell carcinoma (chRCC) and oncocytoma. We demonstrate the method to train a model using simple max-pooling vote fusion, and use the model to highlight regions of the input that cause a positive classification. The model can be tuned for higher sensitivity at the cost of specificity with a constant threshold and little impact to accuracy overall. Several numerical experiments were run to measure the model’s accuracy on both image and patient level analysis. Our models were designed with a dropout parameter that biases the model towards higher sensitivity or specificity. Our best performance model, as measured by area under the receiver operating characteristic curve (AUC of ROC, or AUROC) on patient level classification, is measured with a 94% AUROC and 88% accuracy, along with 100% sensitivity and 75% specificity.
Keywords: Biopsy; Chromophobe renal cell carcinoma; Convolution; Convolutional neural network; Convolutional neural network (CNN); Deep learning; Deep neural networks; Harmonic generation; Image analysis; Kidney tumor; Learning algorithms; Malignancy; Multiphoton microscopy; Multiphoton microscopy (MPM); Neural networks; Nonlinear optics; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation (SHG); dept.phy

Characterization of ZnO and Fe doped ZnO nanoparticles using fluorescence spectroscopy - Singhal, Rahul; Fernando, Mihiri; LeMaire, Peter K.; Wu, Binlin (Oxide-based Materials and Devices X, 2019)
In this study, nanoparticles of pure zinc oxide (ZnO) and ZnO doped with iron of various doping concentrations (Zn1- xFexO) are analyzed using fluorescence spectroscopy. Excitation and emission spectra using various operating wavelengths were collected. Individual spectra and excitation emission matrix were analyzed. Various peaks including strong ultraviolet (UV) emission peaks and strong blue emission peaks that are corresponding to the near-band-edge emission (NBE) and defect emission (DE) peaks were studied based on the peak intensities, peak wavelengths, and NBE peak to defect peak ratios. The Zn1-xFexO materials were also analyzed using X-ray diffraction and optical absorption spectroscopy. The variation in the band gap energy and in the NBE emission energy with dopant concentration was analyzed. A red-shift was observed with the NBE emission peak. The NBE to DE ratio initially increases from pure ZnO to Zn0.97Fe0.03O and then decreases as the dopant concentration increases.
Keywords: Absorption spectroscopy; Band Gap; Band-edge emission (NBE); Band-edge emissions; Defect emission; Defect emission (DE); Defects; Dopant concentrations; Doping concentration; Emission spectroscopy; Energy gap; Excitation and emission spectra; Excitation emission matrices; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron; Laser radiation; Light absorption; Nanoparticles; Near band edge emissions; Red Shift; Semiconductor doping; X ray diffraction; X-ray diffraction; Zinc oxide; Zinc oxide (ZnO); ZnO nanoparticles; dept.phy

Constraining the initial conditions and temperature dependent viscosity with three-particle correlations in Au+Au collisions - STAR Collaboration (Physics Letters B, 2019)
We present three-particle mixed-harmonic correlations 〈cos⁡(mϕa+nϕb−(m+n)ϕc)〉 for harmonics m,n=1−3 for charged particles in sNN=200 GeV Au+Au collisions at RHIC. These measurements provide information on the three-dimensional structure of the initial collision zone and are important for constraining models of a subsequent low-viscosity quark–gluon plasma expansion phase. We investigate correlations between the first, second and third harmonics predicted as a consequence of fluctuations in the initial state. The dependence of the correlations on the pseudorapidity separation between particles show hints of a breaking of longitudinal invariance. We compare our results to a number of state-of-the art hydrodynamic calculations with different initial states and temperature dependent viscosities. These measurements provide important steps towards constraining the temperature dependent viscosity and longitudinal structure of the initial state at RHIC. © 2018 The Author
Keywords: dept.phy; peer-reviewed

The proton–Ω correlation function in Au + Au collisions at sNN=200GeV - STAR Collaboration (Physics Letters B, 2019)
We present the first measurement of the proton correlation function in heavy-ion collisions for the central (0–40%) and peripheral (40–80%) Au + Au collisions at sNN=200 GeV by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). Predictions for the ratio of peripheral collisions to central collisions for the proton correlation function are sensitive to the presence of a nucleon bound state. These predictions are based on the proton interaction extracted from (2+1)-flavor lattice QCD calculations at the physical point. The measured ratio of the proton correlation function between the peripheral (small system) and central (large system) collisions is less than unity for relative momentum smaller than 40 MeV/c. Comparison of our measured correlation ratio with theoretical calculation slightly favors a proton bound system with a binding energy of ∼ 27 MeV.
Keywords: Correlations; Femtoscopy; NΩ dibaryon; dept.phy; peer-reviewed

A pilot study for distinguishing basal cell carcinoma from normal human skin tissues using visible resonance Raman spectroscopy - Liu, Cheng-hui; Wu, Binlin; Sordillo, Laura A.; Boydston-White, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, Robert R. (Journal of Cancer Metastasis and Treatment, 2019)
Keywords: dept.phy; peer-reviewed

Orbits of 14 binaries based on 2018 SOAR speckle observations - Docobo, José A; Gomez, Jorge; Campo, Pedro P; Andrade, Manuel; Horch, Elliott P; Costa, Edgardo; Mendez, Rene A (Monthly Notices of the Royal Astronomical Society, 2019)
New data obtained during the 2018 March-April speckle run at the 4.1 m Southern Astrophysical Research (SOAR) telescope located at Cerro Pachón (Chile) allowed us to recalculate the orbits of the following visual binaries: WDS 06478+0020 (STT 157),WDS 07003-2207 (FIN 334Aa,Ab), WDS 07013-0906 (A 671), WDS 10174-5354 (CVN 16Aa,Ab), WDS 12155-3106 (RST 1658),WDS 12572+0818 (FIN 380),WDS 13044-1316 (HU 642),WDS 14243-3838 (RST 1785), WDS 16094-3103 (I 557), WDS 17115-1630 (HU 169), WDS 17119-0151 (LPM 629),WDS 17563 + 0259 (A 2189),WDS 18464-2755 (RST 2073), and WDS 19035-6845 (FIN 357). All but three of them are Southern stars. The recently published Gaia parallaxes were used to calculate the total mass of each of these systems, despite the fact that, in a few cases, only Hipparcos parallaxes were available. For two binaries, A 671 and RST 2073, there are no parallax data. However, in these cases, the masses deduced from the dynamical parallaxes provided relevant information. In addition, we also present the first orbit for each of three systems: HU 642, RST 1785, and RST 2073, using speckle measurements. Finally, using the dynamical parallaxes given by these orbits, we have been able to calculate the luminosity of these systems. Said luminosities allow us to indicate an approximate age for each of the components of the system, situating them within the HR diagram. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Techniques: high angular resolution - astrometry - binaries; Visual - stars: fundamental parameters; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Visible resonance raman spectroscopy in human brain tissues - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Wu, Binlin; Yu, Xinguang; Alfano, Robert R. (Neurophotonics and Biomedical Spectroscopy, 2019)
This chapter first reviews the research and applications of nonresonance and resonance Raman spectroscopy for analysis of human brain normal and abnormal tissues. Next, special emphasis is made on our recent achievements of visible resonance Raman (VRR) technique in primary human brain tumor disease investigation and diagnosis. Visible resonance Raman (VRR) spectroscopy technique uses excitation of visible light (532 nm) to evaluate the resonant and nonresonant molecular vibrational modes in biological tissues. The VRR signal intensities are enhanced by two to three orders of magnitude for faster use in medical applications in quasi real time. VRR opens up a new stainless “molecular optics based histopathology” diagnosis approach. © 2019 Elsevier Ltd. All rights reserved.
Keywords: Brain cancer margin assessment; Glioblastoma multiforme (GBM); Glioblastoma multiforme (gbm); Gliomas; Meninges; Optical biopsy; Visible resonance Raman (VRR) spectroscopy; Visible resonance raman (vrr) spectroscopy; Wavelength 532 nm; Wavelength 532nm; dept.phy

The Origins of Young Stars in the Direction of the Leading Arm of the Magellanic Stream: Abundances, Kinematics, and Orbits. - Zhang, Lan; Casetti-Dinescu, Dana I; Bidin, Christian Moni; Mendez, Rene A; Girard, Terrence M; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F; Zhao, Gang (The Astrophysical journal, 2019)
We explore the origins of the young B-type stars found by Casetti-Dinescu et al. (2014) at the outskirts of the Milky-Way disk in the sky region of Leading Arm of the Magellanic Stream. High-resolution spectroscopic observations made with the MIKE instrument on the Magellan Clay 6.5m telescope for nine stars are added to the previous sample analyzed by Zhang et al. (2017). We compile a sample of fifteen young stars with well-determined stellar types, ages, abundances and kinematics. With proper motions from Gaia DR2 we also derive orbits in a realistic Milky-Way potential. We find that our previous radial-velocity selected LA candidates have substantial orbital angular momentum. The substantial amount of rotational component for these stars is in contrast with the near-polar Magellanic orbit, thus rendering these stars unlikely members of the LA. There are four large orbital-energy stars in our sample. The highest orbital-energy one has an age shorter than the time to disk crossing, with a birthplace z = 2.5 kpc and R GC ~ 28 kpc. Therefore, the origin of this star is uncertain. The remaining three stars have disk runaway origin with birthplaces between 12 and 25 kpc from the Galactic center. Also, the most energetic stars are more metal poor ([Mg/H] =-0.50 +/- 0.07) and with larger He scatter (sigma [He/H] = 0.72) than the inner disk ones ([Mg/H] = 0.12 +/- 0.36, sigma [He/H] = 0.15). While the former group's abundance is compatible with that of the Large Magellanic Cloud, it could also reflect the metallicity gradient of the MW disk and their runaway status via different runaway mechanisms.
Keywords: dept.phy; stars: abundances; stars: early-type; stars: kinematics and dynamics

Combined spatial frequency spectroscopy analysis with visible resonance Raman for optical biopsy of human brain metastases of lung cancers - Zhou, Yan; Liu, Cheng-Hui; Pu, Yang; Wu, Binlin; Nguyen, Thien An; Cheng, Gangge; Zhou, Lixin; Zhu, Ke; Chen, Jun; Li, Qingbo; Alfano, Robert R. (Journal of Innovative Optical Health Sciences, 2019)
The purpose of this study is to examine optical spatial frequency spectroscopy analysis (SFSA) combined with visible resonance Raman (VRR) spectroscopic method, for the first time, to discriminate human brain metastases of lung cancers adenocarcinoma (ADC) and squamous cell carcinoma (SCC) from normal tissues. A total of 31 label-free micrographic images of three types of brain tissues were obtained using a confocal micro-Raman spectroscopic system. VRR spectra of the corresponding samples were synchronously collected using excitation wavelength of 532[Formula: see text]nm from the same sites of the tissues. Using SFSA method, the difference in the randomness of spatial frequency structures in the micrograph images was analyzed using Gaussian function fitting. The standard deviations, [Formula: see text] calculated from the spatial frequencies of the micrograph images were then analyzed using support vector machine (SVM) classifier. The key VRR biomolecular fingerprints of carotenoids, tryptophan, amide II, lipids and proteins (methylene/methyl groups) were also analyzed using SVM classifier. All three types of brain tissues were identified with high accuracy in the two approaches with high correlation. The results show that SFSA–VRR can potentially be a dual-modal method to provide new criteria for identifying the three types of human brain tissues, which are on-site, real-time and label-free and may improve the accuracy of brain biopsy.
Keywords: Amides; Amino acids; Article; Biopsy; Brain; Diseases; Histology; Human brain; Image analysis; Metastatic lung cancer; Pathology; Raman spectrometry; Resonance; Resonance Raman; Spatial frequency; Spatial frequency spectroscopy analysis (SFSA); Spatial variables measurement; Spectroscopic analysis; Spectrum analysis; Support vector machines; Tissue; accuracy; amide; brain metastasis; brain tissue; cancer classification; carbene; carotenoid; controlled study; dept.phy; diagnostic test accuracy study; excitation; fatty acid; high density lipoprotein; histopathology; human; human brain; human tissue; lipid; low density lipoprotein; lung adenocarcinoma; metastatic lung cancer; methyl group; molecular imaging; peer-reviewed; photomicrograph image; sensitivity and specificity; spatial frequency spectroscopy analysis; spectroscopy; squamous cell lung carcinoma; support vector machine; support vector machine (SVM); tryptophan; visible resonance Raman (VRR); visible resonance Raman spectroscopy

High performance logic and circuits for high-speed electronic systems - Jain, F; Broadbridge, C; Gherasimova, M; Tang, H (Selected Topics in Electronics and Systems, 2019)
In this volume, we have put together papers spanning a broad range from the area of modeling of strain and misfit dislocation densities, microwave absorption characteristics of nanocomposites, to X-ray diffraction studies. Specific topics in this volume include: Modeling of strain relaxation and defect dynamics in buffer layers for semiconductor devices fabricated on lattice-mismatched substrates, which enables technology for advanced computer chips, multi-junction solar cells, detectors, and microwave transistors. Physical Unclonable Functions (PUFs) are probabilistic circuit primitives that extract randomness from the physical characteristics of devices. One of the papers outlines PUF design based on resistor and capacitor variations for low pass filters (LoPUF). Spatial wavefunction switching (SWS) FETs, which can process 2-bits per FET using CMOS-SWS logic, thus enabling multivalued logic (MVL) and compact DRAMs. Perimeter gated single-photon avalanche diode (PGSPAD). The applied voltage at the gate terminal modulates the electric field, making it uniform throughout the junction. This gating technique is an efficient method to prevent premature edge breakdown, one of the major problems in operating avalanche photodiodes implemented in CMOS process. In summary, papers selected in this volume cover various aspects of high performance logic and circuits for high-speed electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: dept.phy

Phase selection motifs in High Entropy Alloys revealed through combinatorial methods: Large atomic size difference favors BCC over FCC - Kube, Sebastian A; Sohn, Sungwoo; Uhl, David; Datye, Amit; Mehta, Apurva; Schroers, Jan (Acta Materialia, 2019)
High Entropy Alloys are inherently complex and span a vast composition space, making their research and discovery challenging. Developing quantitative predictions of their phase selection requires a large quantity of consistently determined experimental data. Here, we use combinatorial methods to fabricate and characterize 2478 quinary alloys based on Al and transition metals. All data are publicly available at http://materialsatlasproject.org/. Phase selection can be predicted for considered alloys when combining the content of FCC/BCC elements and the constituents’ atomic size difference. Mining our data reveals that High Entropy Alloys with increasing atomic size difference prefer BCC structure over FCC. This preference is typically overshadowed by other selection motifs, which dominate during close-to-equilibrium processing. Not suggested by the Hume-Rothery rules, this preference originates from the ability of the BCC structure to accommodate a large atomic size difference with lower strain energy penalty which can be practically only realized in High Entropy Alloys. © 2019 Acta Materialia Inc.
Keywords: Aluminum alloys; Atomic size difference; Atomic sizes; Atoms; Combinatorial method; Combinatorial sputtering; Composition space; Crystal structure; Entropy; High entropy alloys; Hume-Rothery rules; Phase selection; Quantitative prediction; Strain energy; Transition metals; dept.phy; peer-reviewed

Study of MnO2-Graphene Oxide nanocomposites for supercapacitor applications - Singhal, Rahul; Fagnoni, Justin; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Manivannan, Mani; Pandey, Rishikesh (MRS Advances, 2019)
Graphene oxide (GO)/MnO2 nanocomposites were synthesized by adding KMnO4 in a solution of water and ethanol (3:1), containing 10 mg of GO. Brown precipitates were obtained after a continuous stirring for 1 hr. The precipitates were then washed with deionized water (DI) water and dried to obtain the MnO2-GO nanocomposites. Pure MnO2 was also synthesized using the same method without GO for the comparison. X-ray diffraction pattern confirm δ-MnO2 type of MnO2 with birnessite type MnO2 structure. The TEM images show the average diameter of MnO2 nanorods as 15 nm. Electrochemical characterizations were carried out in an aqueous solution of 3M KOH. Charge-discharge studies were carried out between 1A/g to 20 A/g current range. The MnO2-GO nanocomposites showed improved electrochemical performances. The capacitance of MnO2 and MnO2-GO electrodes was found to be as 300 F/g, and 350 F/g, respectively at a current of 0.5 A/g. © 2019 Materials Research Society.
Keywords: Average diameter; Charge-discharge; Continuous stirrings; Current range; Deionized water; Electric discharges; Electrochemical characterizations; Electrochemical performance; Energy storage; Graphene; Graphene oxide nanocomposites; Manganese oxide; Nanocomposites; Nanorods; Potassium hydroxide; Raman spectroscopy; Supercapacitor; Supercapacitor application; X ray diffraction; dept.phy; energy storage; graphene; peer-reviewed; x-ray diffraction (XRD)

Speckle observations and orbits of multiple stars. - Tokovinin, Andrei; Everett, Mark E; Horch, Elliott P; Torres, Guillermo; Latham, David W (Astronomical Journal, 2019)
We report results of speckle-interferometric monitoring of visual hierarchical systems using the newly commissioned instrument NN-EXPLORE Exoplanet and Stellar Speckle Imager at the 3.5 m WIYN telescope. During one year, 390 measurements of 129 resolved subsystems were made, while some targets were unresolved. Using our astrometry and archival data, we computed 36 orbits (27 for the first time). Spectro-interferometric orbits of seven pairs are determined by combining positional measurements with radial velocities measured, mostly, with the Center for Astrophysics digital speedometers. For the hierarchical systems HIP 65026 (periods 49 and 1.23 yr) and HIP 85209 (periods 34 and 1.23 yr) we determined both the inner and the outer orbits using astrometry and radial velocities and measured the mutual orbit inclinations of 11.°3 ± 1.°0 and 12.°0 ± 3.°0, respectively. Four bright stars are resolved for the first time; two of those are triple systems. Several visual subsystems announced in the literature are shown to be spurious. We note that subsystems in compact hierarchies with outer separations less than 100 au tend to have less eccentric orbits compared to wider hierarchies. © 2019. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; ⛔ No DOI found

Invited Article: Molecular biomarkers characterization for human brain glioma grading using visible resonance Raman spectroscopy - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Zhang, Chunyuan; Yu, Xinguang; Cheng, Gangge; Chen, Hong; Li, Shenglin; Liang, Qijun; Zhang, Mingqian; Zhu, Ke; Shi, Lingyan; et al. (APL Photonics, 2018)
The accurate identification of the human brain tumor boundary and the complete resection of the tumor are two essential factors for the removal of the glioma tumor in brain surgery. We present a visible resonance Raman (VRR) spectroscopy technique for differentiating the brain tumor margin and glioma grading. Eighty-seven VRR spectra from twenty-one human brain specimens of four types of brain tissues, including the control, glioma grade II, III, and IV tissues, were observed. This study focuses on observing the characteristics of new biomarkers and their changes in the four types of brain tissue. We found that two new RR peaks at 1129 cm-1 and 1338 cm-1 associated with molecular vibrational bonds in four types of brain tissues are significantly different in peak intensities of VRR spectra. These two resonance enhanced peaks may arise from lactic acid/phosphatidic acid and adenosine triphosphate (ATP)/nicotinamide adenine dinucleotide, respectively. We found that lactic acid and ATP concentrations vary with glioma gratings. The higher the grade of malignancy, the more the increase in lactic acid and ATP concentrations. These two RR peaks may be considered as new molecular biomarkers and used to evaluate glioma grades and identify the margin of gliomas from the control tissues. The metabolic process of lactic acid and ATP in glioma cells based on the VRR spectral changes may reveal the Warburg hypothesis. © 2018 Author(s).
Keywords: Adenosinetriphosphate; Biomarkers; Brain; Control tissues; Grading; Histology; Human brain tumors; Lactic acid; Metabolic process; Molecular biomarker; Resonance; Resonance Raman; Resonance Raman spectroscopy; Resonance enhanced; Spectral change; Tumors; dept.phy; peer-reviewed

J/ψ production cross section and its dependence on charged-particle multiplicity in p + p collisions at √s=200 GeV - STAR Collaboration (Physics Letters B, 2018)
We present a measurement of inclusive J/ψ production at mid-rapidity (|y|¡1) in p+p collisions at a center-of-mass energy of s=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The differential production cross section for J/ψ as a function of transverse momentum (pT) for 0¡pT¡14 GeV/c and the total cross section are reported and compared to calculations from the color evaporation model and the non-relativistic Quantum Chromodynamics model. The dependence of J/ψ relative yields in three pT intervals on charged-particle multiplicity at mid-rapidity is measured for the first time in p+p collisions at s=200 GeV and compared with that measured at s=7 TeV, PYTHIA8 and EPOS3 Monte Carlo generators, and the Percolation model prediction.
Keywords: Charged-particle multiplicity; Multiple parton interactions; Quarkonium; collisions; dept.phy; p+p collisions; peer-reviewed

The Three-dimensional orbit, orbital parallax, and individual masses of the double-lined spectroscopic binaries HD 183255, HD 114882, and HD 30712 - Docobo, J. A.; Campo, P. P; Gomez, J.; Horch, Elliott P. (The Astronomical Journal, 2018)
Recent speckle observations performed at the Discovery Channel Telescope, the Gemini North Telescope, and the Special Astrophysical Observatory 6 m Telescope have permitted us to calculate the visual orbit of SB2 HD 114882 for the first time and to improve the visual orbits of two other SB2 systems, HD 30712 and HD 183255, using algorithms published by the authors of this research. Recently, new high-quality spectroscopic orbits have been obtained for these binaries by other authors. We determine their 3D orbits, individual masses, and orbital parallaxes, and present them in this paper. The parallaxes are compared with those available from the Gaia mission, and a comparison between the values confirms the precision of the results obtained here. © 2018. The American Astronomical Society. All rights reserved.
Keywords: astrometry; binaries: spectroscopic; binaries: visual; dept.phy; peer-reviewed; stars: fundamental parameters; techniques: interferometric

Collision energy dependence of moments of net-kaon multiplicity distributions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Fluctuations of conserved quantities such as baryon number, charge, and strangeness are sensitive to the correlation length of the hot and dense matter created in relativistic heavy-ion collisions and can be used to search for the QCD critical point. We report the first measurements of the moments of net-kaon multiplicity distributions in Au+Au collisions at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV. The collision centrality and energy dependence of the mean (M), variance (σ2), skewness (S), and kurtosis (κ) for net-kaon multiplicity distributions as well as the ratio σ2/M and the products Sσ and κσ2 are presented. Comparisons are made with Poisson and negative binomial baseline calculations as well as with UrQMD, a transport model (UrQMD) that does not include effects from the QCD critical point. Within current uncertainties, the net-kaon cumulant ratios appear to be monotonic as a function of collision energy.
Keywords: dept.phy; peer-reviewed

Harmonic decomposition of three-particle azimuthal correlations at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2018)
We present measurements of three-particle correlations for various harmonics in Au+Au collisions at energies ranging from sNN=7.7√sNN=7.7 to 200 GeV using the STAR detector. The quantity 〈cos(mϕ1+nϕ2−(m+n)ϕ3)〉⟨cos(mϕ1+nϕ2−(m+n)ϕ3)⟩, with ϕϕ being the azimuthal angles of the particles is evaluated as a function of sNN√sNN, collision centrality, transverse momentum, pTpT, pseudorapidity difference, ΔηΔη, and harmonics (mm and nn). These data provide detailed information on global event properties such as the three-dimensional structure of the initial overlap region, the expansion dynamics of the matter produced in the collisions, and the transport properties of the medium. A strong dependence on ΔηΔη is observed for most harmonic combinations, which is consistent with breaking of longitudinal boost invariance. An interesting energy dependence is observed when one of the harmonics m,n,m,n, or m+nm+n is equal to two, for which the correlators are dominated by the two-particle correlations relative to the second-harmonic event plane. These measurements can be used to constrain models of heavy-ion collisions over a wide range of temperature and baryon chemical potential.
Keywords: dept.phy; peer-reviewed

Beam energy dependence of rapidity-even dipolar flow in Au+Au collisions - STAR Collaboration (Physics Letters B, 2018)
New measurements of directed flow for charged hadrons, characterized by the Fourier coefficient v1, are presented for transverse momenta pT, and centrality intervals in Au+Au collisions recorded by the STAR experiment for the center-of-mass energy range sNN=7.7–200 GeV. The measurements underscore the importance of momentum conservation, and the characteristic dependencies on sNN, centrality and pT are consistent with the expectations of geometric fluctuations generated in the initial stages of the collision, acting in concert with a hydrodynamic-like expansion. The centrality and pT dependencies of v1even, as well as an observed similarity between its excitation function and that for v3, could serve as constraints for initial-state models. The v1even excitation function could also provide an important supplement to the flow measurements employed for precision extraction of the temperature dependence of the specific shear viscosity.
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetries for π0 s in the forward direction for 510 GeV polarized pp collisions - STAR Collaboration (Physical Review D, 2018)
The STAR Collaboration reports measurements of the longitudinal double-spin asymmetry, ALL, for neutral pions produced at forward directions in polarized proton-proton collisions, at a center-of-mass energy of 510 GeV. Results are given for transverse momenta in the range 2<pT<10 GeV/c within two regions of pseudorapidity that span 2.65<η<3.9. These results are sensitive to the polarized gluon parton distribution function, Δg(x), down to the region of Bjorken x∼10−3. The asymmetries observed are less than ±5×10−3 in magnitude and will help constrain the contribution to the spin of the proton from polarized gluons at low x, when combined with other measurements as part of a global analysis.
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetries for dijet production at intermediate pseudorapidity in polarized pp collisions at √ s = 200 GeV - STAR Collaboration (Physical Review D, 2018)
We present the first measurements of the longitudinal double-spin asymmetry ALL for dijets with at least one jet reconstructed within the pseudorapidity range 0.8<η<1.8. The dijets were measured in polarized pp collisions at a center-of-mass energy s=200 GeV. Values for ALL are determined for several distinct event topologies, defined by the jet pseudorapidities, and span a range of parton momentum fraction x down to x∼0.01. The measured asymmetries are found to be consistent with the predictions of global analyses that incorporate the results of previous RHIC measurements. They will provide new constraints on Δg(x) in this poorly constrained region when included in future global analyses. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed

Correlation measurements between flow harmonics in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Flow harmonics (vn) in the Fourier expansion of the azimuthal distribution of particles are widely used to quantify the anisotropy in particle emission in high-energy heavy-ion collisions. The symmetric cumulants, SC(m,n), are used to measure the correlations between different orders of flow harmonics. These correlations are used to constrain the initial conditions and the transport properties of the medium in theoretical models. In this Letter, we present the first measurements of the four-particle symmetric cumulants in Au+Au collisions at sNN=39 and 200 GeV from data collected by the STAR experiment at RHIC. We observe that v2 and v3 are anti-correlated in all centrality intervals with similar correlation strengths from 39 GeV Au+Au to 2.76 TeV Pb+Pb (measured by the ALICE experiment). The v2–v4 correlation seems to be stronger at 39 GeV than at higher collision energies. The initial-stage anti-correlations between second and third order eccentricities are sufficient to describe the measured correlations between v2 and v3. The best description of v2–v4 correlations at sNN=200GeV is obtained with inclusion of the system's nonlinear response to initial eccentricities accompanied by the viscous effect with η/s¿0.08. Theoretical calculations using different initial conditions, equations of state and viscous coefficients need to be further explored to extract η/s of the medium created at RHIC.
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Beam energy dependence of jet-quenching effects in Au+Au collisions at √(sNN)= 7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV - STAR Collaboration (Physical Review Letters, 2018)
We report measurements of the nuclear modification factor RCP for charged hadrons as well as identified π+(−), K+(−), and p(¯p) for Au+Au collision energies of √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV. We observe a clear high-pT net suppression in central collisions at 62.4 GeV for charged hadrons which evolves smoothly to a large net enhancement at lower energies. This trend is driven by the evolution of the pion spectra but is also very similar for the kaon spectra. While the magnitude of the proton RCP at high pT does depend on the collision energy, neither the proton nor the antiproton RCP at high pT exhibit net suppression at any energy. A study of how the binary collision-scaled high-pT yield evolves with centrality reveals a nonmonotonic shape that is consistent with the idea that jet quenching is increasing faster than the combined phenomena that lead to enhancement.
Keywords: Au+Au collisions; Beam energies; Binary collisions; Charged hadrons; Colliding beam accelerators; Collision energies; Fighter aircraft; Germanium compounds; Hadrons; Lower energies; Measurements of; Nuclear modification factors; Quenching; dept.phy; peer-reviewed

Wide-field speckle techniques for small, urban telescopes - Granucci, Nicole M.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
Recent work with the NESSI speckle camera at Kitt Peak and the 'Alopeke speckle camera at Gemini-North indicates that speckle data reduction techniques can be successfully modified to produce high-resolution images over fields that are at least tens of arc seconds across. While these wide-field speckle image reconstructions are not diffraction-limited, the improvement in resolution over the seeing-limited case can be substantial. In this paper, we explore the application of these techniques to data taken with a small (0.6-m) telescope in an urban environment. Many telescopes located in urban communities, such as New Haven, Connecticut, where Southern Connecticut State University resides, have limited use scientifically due to substantial light pollution, poor seeing, poor telescope tracking, and other issues. We will present initial data using our set-up and discuss the potential for this approach for improving the imaging capabilities of small telescopes on our campus and beyond.
Keywords: Cameras; Diffraction limited; High resolution image; Image enhancement; Image reconstruction; Imaging capabilities; Interferometry; Pollution; Reduction techniques; Shift-and-add; Speckle; Speckle imaging; Telescopes; Unsharp masking; Urban environments; dept.phy; shift-and-add techniques; unsharp masking

Prospects for wireless optical intensity interferometry with the Southern Connecticut stellar interferometer - Horch, Elliott P.; Weiss, Samuel A.; Rupert, Justin D.; LaRue, Ryan; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a two-telescope astronomical intensity interferometer that was completed in June 2016 and has been taking photon correlation data since that time. It uses single-photon avalanche diode (SPAD) detectors at the telescope focal plane and a central timing module, which records the signals from both telescopes simultaneously. In the observations taken to date, single-pixel SPADs have been connected to signal cables that stretch from each telescope to the timing module. However, we are now in the process of making the instrument “wireless” by using a separate timing module at each telescope and synchronizing the signals recorded using GPS timing cards. We have also upgraded one of the two stations with an 8-pixel SPAD device, which allows us to achieve higher count rates in a variety of observing conditions. In this paper, we report on the current state of the instrument, including engineering tests made in preparation for wireless operation, and we discuss the expected capabilities in that mode.
Keywords: Avalanche diodes; Engineering tests; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Particle beams; Photon correlation; Photons; Single photon avalanche diode; Stars; Stellar interferometers; Telescopes; Timing module; Wireless operation; Wireless-optical; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Stellar photon correlation detection with the Southern Connecticut stellar interferometer - Weiss, Samuel A.; Rupert, Justin D.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a portable optical intensity interferometer located on the campus of Southern Connecticut State University in New Haven, Connecticut. Since its completion in 2016, the instrument has been used to take engineering data of bright stars. This paper will discuss the data collection and analysis methods, as well as the progress toward reliably measuring a significant stellar photon correlation. Vega has been the main star chosen for test observations to date because its diameter is well known by other methods, and it is not an extended source for the baselines used. The correlation peak in the processed data is compared to theoretical expectations. Given our expected sensitivity, a significant correlation peak is expected for small baselines (~2 m) to appear after a few hours of observation. So far, the observations indicate that the correlation peak is at the expected time delay, and the signal-to-noise ratio roughly scales as predicted.
Keywords: Avalanche diodes; Correlation peaks; Engineering data; Extended sources; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Optical intensities; Particle beams; Photon correlation; Photons; Quantum optics; Signal to noise ratio; Single photon avalanche diode; Stars; Stellar interferometers; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Zodiacal Exoplanets in Time (ZEIT). VII. A temperate candidate Super-Earth in the Hyades Cluster - Vanderburg, Andrew; Mann, Andrew W.; Rizzuto, Aaron; Bieryla, Allyson; Kraus, Adam L.; Berlind, Perry; Calkins, Michael L.; Curtis, Jason L.; Douglas, Stephanie T.; Esquerdo, Gilbert A.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2018)
Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluster. Using data from the K2 mission, we detected a single transit of a super-Earth-sized (1.96 0.12 R ⊕) planet candidate orbiting the K-dwarf HD 283869 with a period longer than 72 days. As we only detected a single-transit event, we cannot validate HD 283869 b with high confidence, but our analysis of the K2 images, archival data, and follow-up observations suggests that the source of the event is indeed a transiting planet. We estimated the candidate's orbital parameters and find that if real, it has a period P ≈ 100 days and receives approximately Earth-like incident flux, giving the candidate a 71% chance of falling within the circumstellar habitable zone. If confirmed, HD 283869 b would have the longest orbital period, lowest incident flux, and brightest host star of any known transiting planet in an open cluster, making it uniquely important to future studies of how stellar irradiation affects planetary evolution. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: detection; stars: individual (HD 283869)

Stellar companions of exoplanet host stars in K2 - Matson, Rachel A.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (The Astronomical Journal, 2018)
It is well established that roughly half of all nearby solar-type stars have at least one companion. Stellar companions can have significant implications for the detection and characterization of exoplanets, including triggering false positives and masking the true radii of planets. Determining the fraction of exoplanet host stars that are also binaries allows us to better determine planetary characteristics as well as establish the relationship between binarity and planet formation. Using high angular resolution speckle imaging, we detect stellar companions within ∼1 arcsec of K2 planet-candidate host stars. Comparing our detected companion rate to TRILEGAL star count simulations and known detection limits of speckle imaging, we estimate the binary fraction of K2 planet host stars to be 40%-50%, similar to that of Kepler exoplanet hosts and field stars. © 2018. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; binaries: visual; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

A spectroscopic survey of field red horizontal-branch stars - Afşar, Melike; Bozkurt, Zeynep; Topcu, Gamze Böcek; Casetti-Dinescu, Dana I.; Sneden, Christopher; Şehitog̅lu, Gizem (The Astronomical Journal, 2018)
A metallicity, chemical composition, and kinematic survey has been conducted for a sample of 340 candidate field red horizontal-branch (RHB) stars. Spectra with high resolution and high signal-to-noise ratio were gathered with the McDonald Observatory 2.7 m Tull and the Hobby-Eberly Telescope echelle spectrographs, and were used to determine effective temperatures, surface gravities, microturbulent velocities, [Fe/H] metallicities, and abundance ratios [X/Fe] for seven α and Fe-group species. The derived temperatures and gravities confirm that at least half of the candidates are true RHB stars, with (average) parameters T eff ∼ 5000 K and log g ∼ 2.5. From the α abundances alone, the thin and thick Galactic populations are apparent in our sample. Space motions for 90% of the program stars were computed from Hipparcos and Gaia parallaxes and proper motions. Correlations between chemical compositions and Galactic kinematics clearly indicate the existence of both thin-disk and thick-disk RHB stars. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; stars: abundances; stars: atmospheres; stars: evolution; stars: horizontal-branch

Speckle interferometry at SOAR in 2016 and 2017 - Tokovinin, Andrei; Mason, Brian D.; Hartkopf, William I.; Mendez, Rene A.; Horch, Elliott P. (The Astronomical Journal, 2018)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2016 and 2017 are given, totaling 2483 measurements of 1570 resolved pairs and 609 non-resolutions. We describe briefly recent changes in the instrument and observing method and quantify the accuracy of the pixel scale and position angle calibration. Comments are given on 44 pairs resolved here for the first time. The orbital motion of the newly resolved subsystem BU 83 Aa,Ab roughly agrees with its 36-year astrometric orbit proposed by J. Dommanget. Most Tycho binaries examined here turned out to be spurious. © 2018. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed

The NN-explore exoplanet stellar speckle imager: Instrument description and preliminary results - Scott, Nicholas J.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (Publications of the Astronomical Society of the Pacific, 2018)
A new speckle and wide-field imaging instrument for the WIYN telescope called NN-EXPLORE Exoplanet Stellar Speckle Imager (NESSI) is described. NESSI offers simultaneous two-color diffraction-limited imaging and wide-field traditional imaging for validation and characterization of transit and precision RV exoplanet studies. Many exoplanet targets will come from the NASA K2 and Transiting Exoplanet Survey Satellite (TESS) missions. NESSI is capable of resolving close binaries at sub-arcsecond separations down to the diffraction limit and >6 mag contrast difference in the visible band on targets as faint as 14th mag. Preliminary results from the instrument commissioning at WIYN and demonstrations of the instrument’s capabilities are presented. © 2018. The Astronomical Society of the Pacific. Printed in the U.S.A.
Keywords: Binaries (including multiple): close; Instrumentation: high angular resolution; Instrumentation: interferometers; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Transverse spin-dependent azimuthal correlations of charged pion pairs measured in p↑ + p collisions at √s=500 GeV - STAR Collaboration (Physics Letters B, 2018)
The transversity distribution, which describes transversely polarized quarks in transversely polarized nucleons, is a fundamental component of the spin structure of the nucleon, and is only loosely constrained by global fits to existing semi-inclusive deep inelastic scattering (SIDIS) data. In transversely polarized p↑+p collisions it can be accessed using transverse polarization dependent fragmentation functions which give rise to azimuthal correlations between the polarization of the struck parton and the final state scalar mesons. This letter reports on spin dependent di-hadron correlations measured by the STAR experiment. The new dataset corresponds to 25 pb−1 integrated luminosity of p↑+p collisions at s=500 GeV, an increase of more than a factor of ten compared to our previous measurement at s=200 GeV. Non-zero asymmetries sensitive to transversity are observed at a Q2 of several hundred GeV and are found to be consistent with the former measurement and a model calculation. We expect that these data will enable an extraction of transversity with comparable precision to current SIDIS datasets but at much higher momentum transfers where subleading effects are suppressed. © 2018 The Author(s)
Keywords: Di-hadron correlations; Interference fragmentation function; Transversity; dept.phy; peer-reviewed

Measurement of the ³H lifetime in Au+Au collisions at the BNL relativistic heavy ion collider - STAR Collaboration (Physical Review C, 2018)
An improved measurement of the HΛ3 lifetime is presented. In this paper, the mesonic decay modes HΛ3→He3 + π- and HΛ3→d+p+π- are used to reconstruct the HΛ3 from Au+Au collision data collected by the STAR collaboration at Relativistic Heavy Ion Collider (RHIC). A minimum χ2 estimation is used to determine the lifetime of τ=142-21+24(stat.)±29(syst.) ps. This lifetime is about 50% shorter than the lifetime τ=263±2 ps of a free Λ, indicating strong hyperon-nucleon interaction in the hypernucleus system. The branching ratios of the mesonic decay channels are also determined to satisfy B.R.(He3+π-)/(B.R.(He3+π-)+B.R.(d+p+π-))=0.32±0.05(stat.)±0.08(syst.). Our ratio result favors the assignment J(HΛ3)=12 over J(HΛ3)=32. These measurements will help to constrain models of hyperon-baryon interactions. © 2018 American Physical Society.
Keywords: dept.phy; peer-reviewed

Visible resonance Raman spectroscopy detect key molecular biomarker vibrations to characterize for human brain gliomas - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Yu, Xinguang; Gangge Cheng; Zhang, Chunyuan; Chen, Hong; Li, Shenglin; Zong, Rui; Liang, Qijun; Zhang, Ce; Zhang, Mingqian; et al. (Biomedical Imaging and Sensing Conference, 2018)
Visible resonant Raman (VRR) spectroscopy provides an effective way to enhance Raman signal from particular bonds associated with key molecules due to changes on molecular level. This paper reports on the VRR use for detection of human brain the control and gliomas of three grades. From the RR spectra additional two molecular vibrational biomarkers at 1129cm-1 and 1338cm-1, for the four types of brain tissues are significantly different in intensity. The new RR spectral peaks can be used as molecular biomarkers to evaluate glioma grades and identify the margin of gliomas from the controls. The metabolic process of glioma cells based on the RR spectral changes may reveal the Warburg hypothesis.
Keywords: 532nm; Biomarkers; Brain; Human brain tumors; Medical imaging; Raman probe; Raman spectroscopy; Resonance Raman; Tumors; Visible resonance Raman (VRR); confical Raman probe; dept.phy; gliomas; human brain tumor

In-situ Star Formation in the Outskirts of the Large Magellanic Cloud: Gaia DR2 Confirmation. - Casetti-Dinescu, Dana I; Girard, Terrence M; Bidin, Christian Moni; Zhang, Lan; Mendez, Rene A; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F (The Astrophysical journal, 2018)
We explore the Gaia data release 2 (DR2) proper motions of six young, main-sequence stars, members of the Large Magellanic Cloud (LMC) reported by Moni Bidin et al. These stars are located in the outskirts of the disk, between 7degree and 13degree from the LMC's center where there is very low H I content. Gaia DR2 proper motions confirm that four stars formed locally, in situ, while two are consistent with being expelled via dynamical interactions from inner, more gas-rich regions of the LMC. This finding establishes that recent star formation occurred in the periphery of the LMC, where thus far only old populations were known.
Keywords: Magellanic Clouds; dept.phy; stars: early-type; stars: kinematics and dynamics

High-resolution speckle imaging - Howell, Steve B.; Horch, Elliott P. (Physics Today, 2018)
Keywords: dept.phy

A Rapid Method Based on Fluorescence Spectroscopy for Meat Spoilage Detection - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (International Journal of High Speed Electronics and Systems, 2018)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and non-subjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19°C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~ -12°C), the changes are much less or even unnoticeable over a-week-long storage.
Keywords: Amino acids; Autofluorescence; Bacteria; Biological tissues; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Meats; Metabolism; Microbial metabolism; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Relative concentration; Spoilage; bacteria; collagen; dept.phy; fluorescence spectroscopy; meat food; microbial metabolism; peer-reviewed; tryptophan

Optical biopsy for prostate cancer diagnosis using fluorescence spectroscopy - Wu, Binlin; Gao, Xin; Smith, Jason (International Journal of High Speed Electronics and Systems, 2018)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using an unsupervised machine learning algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved scores of the components are used to estimate the relative concentrations of the native fluorophores such as NADH and FAD and the redox ratio. A supervised machine learning algorithm such as support vector machine (SVM) is used to classify normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. Various statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve are used to show the classification performance. A cross validation method such as leave-one-out is used to further evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting, and the accuracy was found to be 93.3%.
Keywords: Biopsy; Diseases; FAD; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Machine learning; Matrix algebra; NADH; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Optical emission spectroscopy; Prostate cancer; Prostate cancers; Redox ratio; Supervised learning; Support vector machines; Tissue; Urology; dept.phy; fluorescence spectroscopy; intrinsic tissue emission; machine learning; nonnegative matrix factorization; optical biopsy; peer-reviewed; redox ratio; support vector machine

275 candidates and 149 validated planets orbiting bright stars in K 2 campaigns 0–10 - Mayo, Andrew W.; Vanderburg, Andrew; Latham, David W.; Bieryla, Allyson; Morton, Timothy D.; Buchhave, Lars A.; Dressing, Courtney D.; Beichman, Charles; Berlind, Perry; Calkins, Michael L.; Ciardi, David R.; Crossfield, Ian J. M.; et al. (The Astronomical Journal, 2018)
Since 2014, NASA's K2 mission has observed large portions of the ecliptic plane in search of transiting planets and has detected hundreds of planet candidates. With observations planned until at least early 2018, K2 will continue to identify more planet candidates. We present here 275 planet candidates observed during Campaigns 0-10 of the K2 mission that are orbiting stars brighter than 13 mag (in Kepler band) and for which we have obtained high-resolution spectra (R = 44,000). These candidates are analyzed using the vespa package in order to calculate their false-positive probabilities (FPP). We find that 149 candidates are validated with an FPP lower than 0.1%, 39 of which were previously only candidates and 56 of which were previously undetected. The processes of data reduction, candidate identification, and statistical validation are described, and the demographics of the candidates and newly validated planets are explored. We show tentative evidence of a gap in the planet radius distribution of our candidate sample. Comparing our sample to the Kepler candidate sample investigated by Fulton et al., we conclude that more planets are required to quantitatively confirm the gap with K2 candidates or validated planets. This work, in addition to increasing the population of validated K2 planets by nearly 50% and providing new targets for follow-up observations, will also serve as a framework for validating candidates from upcoming K2 campaigns and the Transiting Exoplanet Survey Satellite, expected to launch in 2018. © 2018. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; methods: data analysis; peer-reviewed; planets and satellites: detection; techniques: photometric

Chemical abundances in the leading arm of the Magellanic stream - Fox, Andrew J.; Barger, Kathleen A.; Wakker, Bart P.; Richter, Philipp; Antwi-Danso, Jacqueline; Casetti-Dinescu, Dana I.; Howk, J. Christopher; Lehner, Nicolas; D’Onghia, Elena; Crowther, Paul A.; Lockman, Felix J. (The Astrophysical Journal, 2018)
The Leading Arm (LA) of the Magellanic Stream is a vast debris field of H i clouds connecting the Milky Way and the Magellanic Clouds. It represents an example of active gas accretion onto the Galaxy. Previously, only one chemical abundance measurement had been made in the LA. Here we present chemical abundance measurements using Hubble Space Telescope/Cosmic Origins Spectrograph and Green Bank Telescope spectra of four AGN sightlines passing through the LA and three nearby sightlines that may trace outer fragments of the LA. We find low oxygen abundances, ranging from 4.0-2.0+2.0% solar to 12.6-4.16.0% solar, in the confirmed LA directions, with the lowest values found in the region known as LA III, farthest from the LMC. These abundances are substantially lower than the single previous measurement, S/H =35 ±7% solar, but are in agreement with those reported in the SMC filament of the trailing Stream, supporting a common origin in the SMC (not the LMC) for the majority of the LA and trailing Stream. This provides important constraints for models of the formation of the Magellanic System. Finally, two of the three nearby sightlines show high-velocity clouds with H i columns, kinematics, and oxygen abundances consistent with LA membership. This suggests that the LA is larger than traditionally thought, extending at least 20° further to the Galactic northwest. © 2018. The American Astronomical Society. All rights reserved.
Keywords: Galaxy: evolution; Galaxy: halo; ISM: abundances; Magellanic Clouds; dept.phy; quasars: absorption lines

Resonance raman imaging for detecting and monitoring molecular pathological changes in human brain tumors related to Warburg effect - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Zhang, Chunyuan; Yang, Yang; Yu, Xinguang; Hu, Hailong; Cheng, Gangge; Wu, Binlin; Shi, Lingyan; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
The goal of the research is to determine the prognostic molecular pathological changes in components and composition, for human brain glioma gradings in comparison with normal tissues in three-dimensional Raman imaging profiles by visible Resonance Raman (VRR) imaging. VRR images from twenty-five specimens including three healthy tissues, one normal control, and twenty-one glioma tissues of grades II, II-III and III-IV with histology examination were measured and investigated using WITec300R confocal micro Raman imaging system with laser excitation of 532nm. Two-dimensional RR spectral mappings performed in 20μm x 20μm generated 400 images which integrated the intensity of the specific biochemical bonds as the third dimension. The three-dimension (3D) map demonstrated the spatial distributions of three selected sets of RR spectra of molecular biomarkers, and revealed significant differences in the spectra between normal and glioma tissues of different grades due to the composition changes in key molimageecules. These RR molecular spectral fingerprints have displayed: a clear enhancement of RR vibrational modes at 1129-1131cm-1 and 2934cm-1 which are supposed to be arising from lipoproteins; evident decreased RR vibrational modes at 1442cm-1 and 2854cm-1 which are from saturated fatty acids bonds in all-grades of glioma brain tissues compared with normal tissues; and the enhanced RR spectral modes of 1129 cm-1 and 2938cm-1 which suggest contribution from lactate. These findings may provide a novel proof for anaerobic glycolysis metabolic process in brain glioma cancer tissues that has been explained by Warburg effects.
Keywords: 2-d imaging; 2D imaging; Biopsy; Brain; Gliomas; Histology; Human Brain Tissues; Human brain; Laser excitation; Molecular imaging; Resonance; Resonance Raman; Saturated fatty acids; Tumors; Visible resonance Raman (VRR); Warburg effect; Warburg effects; dept.phy

Statistical analysis and machine learning algorithms for optical biopsy - Wu, Binlin; Liu, Cheng-hui; Boydston-White, Susie; Beckman, Hugh; Sriramoju, Vidyasagar; Sordillo, Laura; Zhang, Chunyuan; Zhang, Lin; Shi, Lingyan; Smith, Jason; Bailin, Jacob; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Analyzing spectral or imaging data collected with various optical biopsy methods is often times difficult due to the complexity of the biological basis. Robust methods that can utilize the spectral or imaging data and detect the characteristic spectral or spatial signatures for different types of tissue is challenging but highly desired. In this study, we used various machine learning algorithms to analyze a spectral dataset acquired from human skin normal and cancerous tissue samples using resonance Raman spectroscopy with 532nm excitation. The algorithms including principal component analysis, nonnegative matrix factorization, and autoencoder artificial neural network are used to reduce dimension of the dataset and detect features. A support vector machine with a linear kernel is used to classify the normal tissue and cancerous tissue samples. The efficacies of the methods are compared.
Keywords: Artificial neural network; Biological basis; Biopsy; Cancer diagnosis; Cancerous tissues; Factorization; Learning algorithms; Learning systems; Least squares approximations; Machine learning; Matrix algebra; Neural networks; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Partial least square (PLS); Partial least squares; Principal component analysis; Resonance Raman spectroscopy; Spatial signature; Support vector machine; Support vector machines; Tissue; Tissue engineering; dept.phy

Characterization and discrimination of human breast cancer and normal breast tissues using resonance Raman spectroscopy - Wu, Binlin; Smith, Jason; Zhang, Lin; Gao, Xin; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Worldwide breast cancer incidence has increased by more than twenty percent in the past decade. It is also known that in that time, mortality due to the affliction has increased by fourteen percent. Using optical-based diagnostic techniques, such as Raman spectroscopy, has been explored in order to increase diagnostic accuracy in a more objective way along with significantly decreasing diagnostic wait-times. In this study, Raman spectroscopy with 532-nm excitation was used in order to incite resonance effects to enhance Stokes Raman scattering from unique biomolecular vibrational modes. Seventy-two Raman spectra (41 cancerous, 31 normal) were collected from nine breast tissue samples by performing a ten-spectra average using a 500-ms acquisition time at each acquisition location. The raw spectral data was subsequently prepared for analysis with background correction and normalization. The spectral data in the Raman Shift range of 750- 2000 cm-1 was used for analysis since the detector has highest sensitivity around in this range. The matrix decomposition technique nonnegative matrix factorization (NMF) was then performed on this processed data. The resulting leave-oneout cross-validation using two selective feature components resulted in sensitivity, specificity and accuracy of 92.6%, 100% and 96.0% respectively. The performance of NMF was also compared to that using principal component analysis (PCA), and NMF was shown be to be superior to PCA in this study. This study shows that coupling the resonance Raman spectroscopy technique with subsequent NMF decomposition method shows potential for high characterization accuracy in breast cancer detection.
Keywords: Background correction; Biopsy; Breast Cancer; Breast cancer; Breast cancer detection; Cancer diagnosis; Couplings; Decomposition methods; Diagnostic techniques; Diseases; Factorization; Learning systems; Machine learning; Matrix algebra; Molecular optical pathology; Nonnegative matrix factorization; Principal component analysis; Principal component analysis (PCA); Raman scattering; Raman spectroscopy; Resonance; Resonance Raman spectroscopy; Spectrum analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Azimuthal transverse single-spin asymmetries of inclusive jets and charged pions within jets from polarized-proton collisions at √s = 500 GeV - STAR Collaboration (Physical Review D, 2018)
We report the first measurements of transverse single-spin asymmetries for inclusive jet and jet+π± production at midrapidity from transversely polarized proton-proton collisions at √s=500 GeV. The data were collected in 2011 with the STAR detector sampled from 23 pb−1 integrated luminosity with an average beam polarization of 53%. Asymmetries are reported for jets with transverse momenta 6<pT<55 GeV/c and pseudorapidity |η|<1. Presented are measurements of the inclusive-jet azimuthal transverse single-spin asymmetry, sensitive to twist-3 initial-state quark-gluon correlators; the Collins asymmetry, sensitive to quark transversity coupled to the polarized Collins fragmentation function; and the first measurement of the “Collins-like” asymmetry, sensitive to linearly polarized gluons. Within the present statistical precision, inclusive-jet and Collins-like asymmetries are small, with the latter allowing the first experimental constraints on gluon linear polarization in a polarized proton. At higher values of jet transverse momenta, we observe the first nonzero Collins asymmetries in polarized-proton collisions, with a statistical significance of greater than 5σ. The results span a range of x similar to results from semi-inclusive deep-inelastic scattering but at much higher Q2. The Collins results enable tests of universality and factorization breaking in the transverse momentum-dependent formulation of perturbative quantum chromodynamics.
Keywords: dept.phy; peer-reviewed

Proper motion of the Sextans dwarf galaxy from Subaru Suprime-Cam data - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Monthly Notices of the Royal Astronomical Society, 2018)
We have measured the absolute proper motion of the Sextans dwarf spheroidal galaxy using Subaru Suprime-Cam images taken at three epochs, with a time baseline of ~10 yr. We astrometrically calibrate each epoch by constructing distortion-correction 'maps' from the best available Subaru Suprime-Cam dithered data sets and from Gaia Data Release 1 positions. The magnitude limit of the proper motion study is V ~ 24. The area covered is 26.7 × 23.3 arcmin2, which is still within the core radius of Sextans. The derived proper motion is (μα, μδ) = (-0.409 ± 0.050, -0.047 ± 0.058) mas yr-1. The direction of motion is perpendicular to the major axis of the galaxy. Our measurement, combined with radial velocity and distance from the literature, implies a low eccentricity orbit, with a moderate inclination to the Galactic plane, and a period of 3 Gyr. Sextans is now some 0.4 Gyr away from its pericentre (rperi ~ 75 kpc), moving towards its apocentre (rapo ~ 132 kpc). Its orbit is inconsistent with membership to the vast polar structure of Galactic satellites. © 2018 The Author(s).
Keywords: Astrometry; Galaxies: dwarf; Galaxies: individual: Sextans; Proper motions; dept.phy; peer-reviewed

High performance materials and devices for high-speed electronic systems - Jain, F; Broadbridge, C; Tang, H; Gherasimova, M (Selected Topics in Electronics and Systems, 2018)
In this review volume, the editors have included the state-of-the-art research and development in nano composites, and optical electronics written by experts in the field. In addition, it also covers applications for emerging technologies in High-Speed Electronics. In summary, topics covered in this volume includes various aspects of high performance materials and devices for implementing High-Speed Electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Emerging technologies; High performance material; High-speed electronics; Materials; Nanocomposites; Optical electronics; State of the art; dept.phy

Exploring multiphoton microscopy as a novel tool to differentiate chromophobe renal cell carcinoma from oncocytoma in fixed tissue sections - Jain, Manu; Robinson, Brian D.; Wu, Binlin; Khani, Francesca; Mukherjee, Sushmita (Archives of Pathology & Laboratory Medicine, 2018)
Context.-Distinguishing chromophobe renal cell carcinoma (chRCC), especially in the presence of eosinophilic cytoplasm, from oncocytoma on hematoxylin-eosin can be difficult and often requires time-consuming ancillary procedures that ultimately may not be informative. Objective.-To explore the potential of multiphoton microscopy (MPM) as an alternative and rapid diagnostic tool in differentiating oncocytoma from chRCC at subcellular resolution without tissue processing. Design.-Unstained, deparaffinized tissue sections from 27 tumors (oncocytoma [n = 12], chRCC [n = 12], eosinophilic variant of chRCC [n = 1], and atypical oncocytic renal neoplasm [n = 2]) were imaged with MPM. Morphologic evaluation and automated quantitative morphometric analysis were conducted to distinguish between chRCC and oncocytoma. Results.-The typical cases of oncocytomas (12 of 12) and chRCC (12 of 12) could be readily differentiated on MPM based on the morphologic features similar to hematoxylin-eosin. The most striking MPM signature of both of the tumors was the presence of autofluorescent intracytoplasmic granules, which are not seen on hematoxylin-eosin-stained slides. Although we saw these granules in both types of tumors, they appeared distinct, based on their size, shape, cytoplasmic distribution, and autofluorescence wavelengths, and were valuable in arriving at a definitive diagnosis. For oncocytomas and chRCC, high diagnostic accuracies of 100% and 83.3% were achieved on blinded MPM and morphometric analysis, respectively. Conclusions.-To the best of our knowledge, this is the first demonstration of MPM to distinguish chRCC from oncocytoma in fixed tissues. Our study was limited by small sample size and only a few variants of oncocytic tumors. Prospective studies are warranted to assess the utility of MPM as a diagnostic aid in oncocytic renal tumors. © Copyright 2018 College of American Pathologists.
Keywords: Adenoma, Oxyphilic; Carcinoma, Renal Cell; Diagnosis, Differential; Humans; Kidney Neoplasms; Microscopy, Fluorescence, Multiphoton; Tissue Fixation; dept.phy; differential diagnosis; human; kidney tumor; multiphoton microscopy; oncocytoma; pathology; peer-reviewed; procedures; renal cell carcinoma; tissue fixation

Assessment of basal cell carcinoma from normal human skin tissues using Resonance Raman spectroscopy - Liu, Chenghui; Wu, Binlin; Sordillo, Laura A; Boydstonwhite, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, R R (OSA - The Optical Society, 2018)
VRR spectroscopy was used for BCC and normal skin tissues with 532nm excitation. The spectra showed significant changes in collagen, carotenoids and lipids. These enhanced fingerprints demonstrate a potential use as label-free pathology method. © 2018 The Author(s).
Keywords: Basal cell carcinoma; Histology; Human skin; Label free; Normal skin; Resonance Raman spectroscopy; Tissue; dept.phy

A pilot study for distinguishing chromophobe renal cell carcinoma and oncocytoma using second harmonic generation imaging and convolutional neural network analysis of collagen fibrillar structure - Wu, Binlin; Judd, Nicolas; Smith, Jason; Icaza, Michael; Mukherjee, Sushmita; Jain, Manu; Gallagher, Ryan M; Szeligowski, Richard V (2018)
A clear distinction between oncocytoma and chromophobe renal cell carcinoma (chRCC) is critically important for clinical management of patients. But it may often be difficult to distinguish the two entities based on hematoxylin and eosin (H and E) stained sections alone. In this study, second harmonic generation (SHG) signals which are very specific to collagen were used to image collagen fibril structure. We conduct a pilot study to develop a new diagnostic method based on the analysis of collagen associated with kidney tumors using convolutional neural networks (CNNs). CNNs comprise a type of machine learning process well-suited for drawing information out of images. This study examines a CNN model's ability to differentiate between oncocytoma (benign), and chRCC (malignant) kidney tumor images acquired with second harmonic generation (SHG), which is very specific for collagen matrix. To the best of our knowledge, this is the first study that attempts to distinguish the two entities based on their collagen structure. The model developed from this study demonstrated an overall classification accuracy of 68.7% with a specificity of 66.3% and sensitivity of 74.6%. While these results reflect an ability to classify the kidney tumors better than chance, further studies will be carried out to (a) better realize the tumor classification potential of this method with a larger sample size and (b) combining SHG with two-photon excited intrinsic fluorescence signal to achieve better classification. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: Biomedical signal processing; Biopsy; Chromophobe renal cell carcinoma; Classification accuracy; Collagen; Convolution; Convolutional Neural Networks (CNN); Convolutional neural network; Convolutional neural networks (CNN); Fluorescence; Harmonic analysis; Harmonic generation; Intrinsic fluorescence signals; Kidney tumor; Learning systems; Machine learning; Multiphoton microscopy; Multiphoton microscopy (MPM); Multiphoton processes; Neural networks; Nonlinear optics; Patient monitoring; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation; Tumor classification; Tumors; dept.phy

Diagnosis of glioma brain cancer using visible resonance Raman spectroscopy - Zhou, Yan; Wu, Binlin; Liu, Chenghui; Yu, Xinguang; Cheng, Gangge; Wang, Kai; Zhang, Chunyuan; Shi, Lingyan; Alfano, R R (OSA, 2018)
Resonance Raman spectroscopy using 532nm excitation was used to distinguish normal brain tissue from different grades of glioma tissues. Principal component analysis was used to analyze the spectral data and achieved high accuracy. © 2018 The Author(s).
Keywords: Brain cancer; Brain tissue; Different grades; Glioma tissues; High-accuracy; Principal component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Spectral data; Tumors; dept.phy

A search for binary star companions to the KELT planet hosts and a comparison sample. i. results of DSSI observations - Coker, Carl T.; Gaudi, B. Scott; Pogge, Richard W.; Horch, Elliott (The Astronomical Journal, 2017)
We are conducting a search for binary companions around 11 hot-Jupiter hosts from the Kilodegree Extremely Little Telescope (KELT) survey and a large comparison sample of stars shown by KELT to not host a transiting hot Jupiter. The primary stars are bright (7.5 < V < 11) and of similar distance from Earth (100 < d < 300 pc). In this paper, we present the results of our observations using the Differential Speckle Survey Instrument. We observed 9 of the 14 KELT planet hosts that are visible from the northern hemisphere and 51 comparison stars, discovering two new potential companions and re-observing two previously known possible binary systems and one confirmed binary system. We provide an estimate of the chance alignment probability for our observed candidate binaries. © 2017 The American Astronomical Society. All rights reserved.
Keywords: Astrometry; binaries: close; binaries: general; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: formation

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric

Characterizing K2 candidate planetary systems orbiting Low-mass stars. II. Planetary Systems observed during campaigns 1–7 - Dressing, Courtney D.; Vanderburg, Andrew; Schlieder, Joshua E.; Crossfield, Ian J. M.; Knutson, Heather A.; Newton, Elisabeth R.; Ciardi, David R.; Fulton, Benjamin J.; Gonzales, Erica J.; Howard, Andrew W.; Isaacson, Howard; Livingston, John; et al. (The Astronomical Journal, 2017)
We recently used near-infrared spectroscopy to improve the characterization of 76 low-mass stars around which K2 had detected 79 candidate transiting planets. 29 of these worlds were new discoveries that had not previously been published. We calculate the false positive probabilities that the transit-like signals are actually caused by non-planetary astrophysical phenomena and reject five new transit-like events and three previously reported events as false positives. We also statistically validate 17 planets (7 of which were previously unpublished), confirm the earlier validation of 22 planets, and announce 17 newly discovered planet candidates. Revising the properties of the associated planet candidates based on the updated host star characteristics and refitting the transit photometry, we find that our sample contains 21 planets or planet candidates with radii smaller than 1.25 R ⊕, 18 super-Earths (1.25-2 R ⊕), 21 small Neptunes (2-4 R ⊕), three large Neptunes (4-6 R ⊕), and eight giant planets (>6 R ⊕). Most of these planets are highly irradiated, but EPIC 206209135.04 (K2-72e, ), EPIC 211988320.01 (), and EPIC 212690867.01 () orbit within optimistic habitable zone boundaries set by the "recent Venus" inner limit and the "early Mars" outer limit. In total, our planet sample includes eight moderately irradiated 1.5-3 R ⊕ planet candidates (F p ≲ 20 F ⊕) orbiting brighter stars (Ks < 11) that are well-suited for atmospheric investigations with the Hubble, Spitzer, and/or James Webb Space Telescopes. Five validated planets orbit relatively bright stars (Kp < 12.5) and are expected to yield radial velocity semi-amplitudes of at least 2 m s-1. Accordingly, they are possible targets for radial velocity mass measurement with current facilities or the upcoming generation of red optical and near-infrared high-precision RV spectrographs. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: fundamental parameters; stars: fundamental parameters; stars: late-type; stars: low-mass; techniques: spectroscopic

Investigating local parity violation in heavy-ion collisions using Λ helicity - Finch, L. E.; Murray, S. J. (Physical Review C, 2017)
We propose the measurement of net Λ and Λ helicity, correlated event by event with the magnitude and sign of charge separation along the event's magnetic field direction, as a probe to investigate the chiral magnetic effect (CME) in heavy-ion collisions. With a simple simulation model of heavy-ion events that includes effects of local parity violation, we estimate the experimental correlation signal that could be expected at RHIC given the results of previous measurements that are sensitive to the CME. © 2017 American Physical Society.
Keywords: dept.phy; peer-reviewed

Bulk properties of the medium produced in relativistic heavy-ion collisions from the beam energy scan program - STAR Collaboration (Physical Review C, 2017)
We present measurements of bulk properties of the matter produced in Au+Au collisions at √sNN=7.7,11.5,19.6,27, and 39 GeV using identified hadrons (π±, K±, p, and ¯p) from the STAR experiment in the Beam Energy Scan (BES) Program at the Relativistic Heavy Ion Collider (RHIC). Midrapidity (|y|<0.1) results for multiplicity densities dN/dy, average transverse momenta ⟨pT⟩, and particle ratios are presented. The chemical and kinetic freeze-out dynamics at these energies are discussed and presented as a function of collision centrality and energy. These results constitute the systematic measurements of bulk properties of matter formed in heavy-ion collisions over a broad range of energy (or baryon chemical potential) at RHIC.
Keywords: dept.phy; peer-reviewed

Exclusion of stellar companions to exoplanet host stars - Wittrock, Justin M.; Kane, Stephen R.; Horch, Elliott P.; Howell, Steve B.; Ciardi, David R.; Everett, Mark E. (The Astronomical Journal, 2017)
Given the frequency of stellar multiplicity in the solar neighborhood, it is important to study the impacts this can have on exoplanet properties and orbital dynamics. There have been numerous imaging survey projects established to detect possible low-mass stellar companions to exoplanet host stars. Here, we provide the results from a systematic speckle imaging survey of known exoplanet host stars. In total, 71 stars were observed at 692 and 880 nm bands using the Differential Speckle Survey Instrument at the Gemini-north Observatory. Our results show that all but two of the stars included in this sample have no evidence of stellar companions with luminosities down to the detection and projected separation limits of our instrumentation. The mass-luminosity relationship is used to estimate the maximum mass a stellar companion can have without being detected. These results are used to discuss the potential for further radial velocity follow-up and interpretation of companion signals. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

Energy dependence of J/ψ production in Au + Au collisions at √sNN=39,62.4 and 200GeV - STAR Collaboration (Physics Letters B, 2017)
The inclusive J/ψ transverse momentum spectra and nuclear modification factors are reported at mid-rapidity (|y|<1.0) in Au + Au collisions at sNN = 39, 62.4 and 200 GeV taken by the STAR experiment. A suppression of J/ψ production, with respect to the production in p+p scaled by the number of binary nucleon–nucleon collisions, is observed in central Au + Au collisions at these three energies. No significant energy dependence of nuclear modification factors is found within uncertainties. The measured nuclear modification factors can be described by model calculations that take into account both suppression of direct J/ψ production due to the color screening effect and J/ψ regeneration from recombination of uncorrelated charm–anticharm quark pairs. © 2017 The Author
Keywords: dept.phy; peer-reviewed

Direct virtual photon production in Au+Au collisions at √sNN=200 GeV - STAR Collaboration (Physics Letters B, 2017)
We report the direct virtual photon invariant yields in the transverse momentum ranges 1<pT<3 GeV/c and 5<pT<10 GeV/c at mid-rapidity derived from the dielectron invariant mass continuum region 0.10<Mee<0.28 GeV/c2 for 0–80% minimum-bias Au+Au collisions at sNN=200 GeV. A clear excess in the invariant yield compared to the nuclear overlap function TAA scaled p+p reference is observed in the pT range 1<pT<3 GeV/c. For pT>6 GeV/c the production follows TAA scaling. Model calculations with contributions from thermal radiation and initial hard parton scattering are consistent within uncertainties with the direct virtual photon invariant yield. © 2017 The Author
Keywords: dept.phy; peer-reviewed

Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2017)
The glass forming ability (GFA) of metallic glasses (MGs) is quantified by the critical cooling rate (R C). Despite its key role in MG research, experimental challenges have limited measured R C to a minute fraction of known glass formers. We present a combinatorial approach to directly measure R C for large compositional ranges. This is realized through the use of compositionally-graded alloy libraries, which were photo-thermally heated by scanning laser spike annealing of an absorbing layer, then melted and cooled at various rates. Coupled with X-ray diffraction mapping, GFA is determined from direct R C measurements. We exemplify this technique for the Au-Cu-Si system, where we identify Au56Cu27Si17 as the alloy with the highest GFA. In general, this method enables measurements of R C over large compositional areas, which is powerful for materials discovery and, when correlating with chemistry and other properties, for a deeper understanding of MG formation.
Keywords: dept.phy; peer-reviewed

Global Λ hyperon polarization in nuclear collisions - STAR Collaboration (Nature, 2017)
The extreme energy densities generated by ultra-relativistic collisions between heavy atomic nuclei produce a state of matter that behaves surprisingly like a fluid, with exceptionally high temperature and low viscosity. Non-central collisions have angular momenta of the order of 1,000h, and the resulting fluid may have a strong vortical structure that must be understood to describe the fluid properly. The vortical structure is also of particular interest because the restoration of fundamental symmetries of quantum chromodynamics is expected to produce novel physical effects in the presence of strong vorticity. However, no experimental indications of fluid vorticity in heavy ion collisions have yet been found. Since vorticity represents a local rotational structure of the fluid, spin-orbit coupling can lead to preferential orientation of particle spins along the direction of rotation. Here we present measurements of an alignment between the global angular momentum of a non-central collision and the spin of emitted particles (in this case the collision occurs between gold nuclei and produces Λ baryons), revealing that the fluid produced in heavy ion collisions is the most vortical system so far observed. (At high energies, this fluid is a quark-gluon plasma.) We find that Λ and hyperons show a positive polarization of the order of a few per cent, consistent with some hydrodynamic predictions. (A hyperon is a particle composed of three quarks, at least one of which is a strange quark; the remainder are up and down quarks, found in protons and neutrons.) A previous measurement that reported a null result, that is, zero polarization, at higher collision energies is seen to be consistent with the trend of our observations, though with larger statistical uncertainties. These data provide experimental access to the vortical structure of the nearly ideal liquid created in a heavy ion collision and should prove valuable in the development of hydrodynamic models that quantitatively connect observations to the theory of the strong force. © 2017 Macmillan Publishers Limited, part of Springer Nature. All rights reserved.
Keywords: Article; baryon; dept.phy; gluon; heavy ion; hydrodynamics; hyperon; polarization; priority journal; proton; quantum mechanics; quark; viscosity

Measurement of d0 azimuthal anisotropy at midrapidity in Au+Au collisions at √sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2017)
We report the first measurement of the elliptic anisotropy (v2) of the charm meson D0 at midrapidity (|y|<1) in Au+Au collisions at sNN=200 GeV. The measurement was conducted by the STAR experiment at RHIC utilizing a new high-resolution silicon tracker. The measured D0 v2 in 0%-80% centrality Au+Au collisions can be described by a viscous hydrodynamic calculation for a transverse momentum (pT) of less than 4 GeV/c. The D0 v2 as a function of transverse kinetic energy (mT-m0, where mT=pT2+m02) is consistent with that of light mesons in 10%-40% centrality Au+Au collisions. These results suggest that charm quarks have achieved local thermal equilibrium with the medium created in such collisions. Several theoretical models, with the temperature-dependent, dimensionless charm spatial diffusion coefficient (2πTDs) in the range of ∼2-12, are able to simultaneously reproduce our D0 v2 result and our previously published results for the D0 nuclear modification factor. © 2017 American Physical Society.
Keywords: Anisotropy; Au+Au collisions; Azimuthal anisotropy; Bosons; Colliding beam accelerators; Hadrons; Hydrodynamic calculation; Kinetic energy; Kinetics; Local thermal equilibrium; Nuclear modification factors; STAR experiment; Star trackers; Temperature dependent; Transverse momenta; dept.phy

Young stars in the periphery of the Large Magellanic Cloud - Moni Bidin, C.; Casetti-Dinescu, D. I.; Girard, T. M.; Zhang, L.; Méndez, R. A.; Vieira, K.; Korchagin, V. I.; van Altena, W. F. (Monthly Notices of the Royal Astronomical Society, 2017)
Despite their close proximity, the complex interplay between the two Magellanic Clouds, the Milky Way and the resulting tidal features, is still poorly understood. Recent studies have shown that the Large Magellanic Cloud (LMC) has a very extended disc strikingly perturbed in its outskirts.We search for recent star formation in the far outskirts of the LMC, out to ~30° from its centre.We have collected intermediate-resolution spectra of 31 young star candidates in the periphery of the LMC and measured their radial velocity, stellar parameters, distance and age. Our measurements confirm membership to the LMC of six targets, for which the radial velocity and distance values match well with those of the Cloud. These objects are all young (10-50 Myr), main-sequence stars, projected between 7° and 13° from the centre of the parent galaxy. We compare the velocities of our stars with those of a disc model, and find that our stars have low to moderate velocity differences with the disc model predictions, indicating that they were formed in situ. Our study demonstrates that recent star formation occurred in the far periphery of the LMC, where thus far only old objects were known. The spatial configuration of these newly formed stars appears ring-like with a radius of 12 kpc and a displacement of 2.6 kpc from the LMC's centre. This structure, if real, would be suggestive of a star formation episode triggered by an off-centre collision between the Small Magellanic Cloud and the LMC's disc. © 2016 The Authors.
Keywords: Magellanic Clouds; Stars: early-type; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VII. Measures from 2010 September to 2012 February at the WIYN Telescope - Horch, Elliott P.; Casetti-Dinescu, Dana I.; Camarata, Matthew A.; Bidarian, Akbar; Altena, William F. van; Sherry, William H.; Everett, Mark E.; Howell, Steve B.; Ciardi, David R.; Henry, Todd J.; Nusdeo, Daniel A.; Winters, Jennifer G. (The Astronomical Journal, 2017)
We report on speckle observations of binary stars carried out at the WIYN Telescope over the period from 2010 September through 2012 February, providing relative astrometry for 2521 observations of 883 objects, 856 of which are double stars and 27 of which are triples. The separations measured span a range of 0.01-1.75 arcsec. Wavelengths of 562, 692, and 880 nm were used, and differential photometry at one or more of these wavelengths is presented in most cases. 66 components were resolved for the first time. We also estimate detection limits at 0.2 and 1.0 arcsec for high-quality observations in cases where no companion was seen, a total of 176 additional objects. Detection limits vary based on observing conditions and signal-to-noise ratio, but are approximately 4 mag at 0.2 arcsec and 6 mag at 1.0 arcsec on average. Analyzing the measurement precision of the data set, we find that the individual separations obtained have linear measurement uncertainties of approximately 2 mas, and photometry is uncertain to approximately 0.1 mag in general. This work provides fundamental, well-calibrated data for future orbit and mass determinations, and we present three first orbits and total mass estimates of nearby K-dwarf systems as examples of this potential. © 2017. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

HAT-P-67b: An extremely low density Saturn transiting an F-subgiant confirmed via doppler tomography - Zhou, G.; Bakos, G. Á.; Hartman, J. D.; Latham, D. W.; Torres, G.; Bhatti, W.; Penev, K.; Buchhave, L.; Kovács, G.; Bieryla, A.; Quinn, S.; Isaacson, H.; et al. (The Astronomical Journal, 2017)
We report the discovery of HAT-P-67b, which is a hot-Saturn transiting a rapidly rotating F-subgiant. HAT-P-67b has a radius of Rp=2.085 -0.071 +0.096 RJ, and orbites a M∗ = 1.642-0.072 +0.155 M, R∗ = 2.546-0.099 +0.0084 R host star in a ∼4.81 day period orbit. We place an upper limit on the mass of the planet via radial velocity measurements to be Mp < 0.59 MJ, and a lower limit of >0.056 MJ by limitations on Roche lobe overflow. Despite being a subgiant, the host star still exhibits relatively rapid rotation, with a projected rotational velocity of v sin I∗ = 35.8 ±1.1 km s-1, which makes it difficult to precisely determine the mass of the planet using radial velocities. We validated HAT-P-67b via two Doppler tomographic detections of the planetary transit, which eliminate potential eclipsing binary blend scenarios. The Doppler tomographic observations also confirm that HAT-P-67b has an orbit that is aligned to within 12, in projection, with the spin of its host star. HAT-P-67b receives strong UV irradiation and is among one of the lowest density planets known, which makes it a good candidate for future UV transit observations in the search for an extended hydrogen exosphere. © 2017. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HAT-P-67); techniques: photometric; techniques: spectroscopic

Using Gaia as an astrometric tool for deep ground-based surveys - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Cambridge University Press, 2017)
Gaia DR1 positions are used to astrometrically calibrate three epochs’ worth of Subaru SuprimeCam images in the fields of globular cluster NGC 2419 and the Sextans dwarf spheroidal galaxy. Distortion-correction “maps” are constructed from a combination of offset dithers and reference to Gaia DR1. These are used to derive absolute proper motions in the field of NGC 2419. Notably, we identify the photometrically-detected Monoceros structure in the foreground of NGC 2419 as a kinematically-cold population of stars, distinct from Galactic-field stars. This project demonstrates the feasibility of combining Gaia with deep, ground-based surveys, thus extending high-quality astrometry to magnitudes beyond the limits of Gaia.
Keywords: Galaxy: kinematics and dynamics; astrometry; dept.phy; galaxies: dwarf

Four sub-Saturns with dissimilar densities: Windows into planetary cores and envelopes - Petigura, Erik A.; Sinukoff, Evan; Lopez, Eric D.; Crossfield, Ian J. M.; Howard, Andrew W.; Brewer, John M.; Fulton, Benjamin J.; Isaacson, Howard T.; Ciardi, David R.; Howell, Steve B.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
We present results from a Keck/HIRES radial velocity campaign to study four sub-Saturn-sized planets, K2-27b, K2-32b, K2-39b, and K2-108b, with the goal of understanding their masses, orbits, and heavy-element enrichment. The planets have similar sizes (RP=4.5-5.5 ), but have dissimilar masses (MP=16-60 ), implying a diversity in their core and envelope masses. K2-32b is the least massive (MP = 16.5 ± 2.7 M) and orbits in close proximity to two sub-Neptunes near a 3:2:1 period commensurability. K2-27b and K2-39b are significantly more massive at MP = 30.9 ± 4.6 M and MP = 39.8 ± 4.4 M, respectively, and show no signs of additional planets. K2-108b is the most massive at MP = 59.4 ± 4.4 M, implying a large reservoir of heavy elements of about ≈50 . Sub-Saturns as a population have a large diversity in planet mass at a given size. They exhibit remarkably little correlation between mass and size; sub-Saturns range from ≈6-60 M, regardless of size. We find a strong correlation between planet mass and host star metallicity, suggesting that metal-rich disks form more massive planet cores. The most massive sub-Saturns tend to lack detected companions and have moderately eccentric orbits, perhaps as a result of a previous epoch of dynamical instability. Finally, we observe only a weak correlation between the planet envelope fraction and present-day equilibrium temperature, suggesting that photo-evaporation does not play a dominant role in determining the amount of gas sub-Saturns accrete from their protoplanetary disks. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planets and satellites: composition; planets and satellites: detection; planets and satellites: dynamical evolution and stability; planets and satellites: formation; planets and satellites: gaseous planets; planets and satellites: interiors

Assessing the effect of stellar companions from high-resolution imaging of Kepler objects of interest - Hirsch, Lea A.; Ciardi, David R.; Howard, Andrew W.; Everett, Mark E.; Furlan, Elise; Saylors, Mindy; Horch, Elliott P.; Howell, Steve B.; Teske, Johanna; Marcy, Geoffrey W. (The Astronomical Journal, 2017)
We report on 176 close (<2″) stellar companions detected with high-resolution imaging near 170 hosts of Kepler Objects of Interest (KOIs). These Kepler targets were prioritized for imaging follow-up based on the presence of small planets, so most of the KOIs in these systems (176 out of 204) have nominal radii <6 . Each KOI in our sample was observed in at least two filters with adaptive optics, speckle imaging, lucky imaging, or the Hubble Space Telescope. Multi-filter photometry provides color information on the companions, allowing us to constrain their stellar properties and assess the probability that the companions are physically bound. We find that 60%-80% of companions within 1″ are bound, and the bound fraction is >90% for companions within 0.″5; the bound fraction decreases with increasing angular separation. This picture is consistent with simulations of the binary and background stellar populations in the Kepler field. We also reassess the planet radii in these systems, converting the observed differential magnitudes to a contamination in the Kepler bandpass and calculating the planet radius correction factor, X R = R p(true)/R p(single). Under the assumption that planets in bound binaries are equally likely to orbit the primary or secondary, we find a mean radius correction factor for planets in stellar multiples of X R = 1.65. If stellar multiplicity in the Kepler field is similar to the solar neighborhood, then nearly half of all Kepler planets may have radii underestimated by an average of 65%, unless vetted using high-resolution imaging or spectroscopy. © 2017. The American Astronomical Society. All rights reserved.
Keywords: binaries: visual; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: fundamental parameters; techniques: high angular resolution; techniques: photometric

Resonance raman of BCC and normal skin - Liu, Cheng-hui; Sriramoju, Vidyasagar; Boydston-White, Susie; Wu, Binlin; Zhang, Chunyuan; Pei, Zhe; Sordillo, Laura; M.d, Hugh Beckman; Alfano, Robert R. (Optical Biopsy XV: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2017)
The Resonance Raman (RR) spectra of basal cell carcinoma (BCC) and normal human skin tissues were analyzed using 532nm laser excitation. RR spectral differences in vibrational fingerprints revealed skin normal and cancerous states tissues. The standard diagnosis criterion for BCC tissues are created by native RR biomarkers and its changes at peak intensity. The diagnostic algorithms for the classification of BCC and normal were generated based on SVM classifier and PCA statistical method. These statistical methods were used to analyze the RR spectral data collected from skin tissues, yielding a diagnostic sensitivity of 98.7% and specificity of 79% compared with pathological reports.
Keywords: Basal cell carcinoma; Basel cell carcinoma (BCC); Biopsy; Cell carcinoma; Diagnostic algorithms; Histology; Human skin; Human skin tissues; Laser excitation; Principal component analysis; Principal component analysis (PCA); Resonance; Resonance Raman spectra; Resonance Raman spectroscopy; Skin cancer; Skin cancers; Spectral differences; Statistical methods; Support vector machine (SVM); Support vector machines; Tissue; Tissue engineering; dept.phy

Rapid measurement of meat spoilage using fluorescence spectroscopy - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (Imaging, Manipulation, and Analysis of Biomolecules, Cells, and Tissues XV, 2017)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and nonsubjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19° C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~-12° C), the changes are much less or even unnoticeable over a-week-long storage.
Keywords: Amino acids; Bacteria; Biological tissues; Biomolecules; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Histology; Meat food; Meats; Metabolism; Microbial metabolism; Molecular biology; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Physiology; Rapid measurement; Relative concentration; Spectrum analysis; Spoilage; Tissue; Tryptophan; dept.phy

Optical biopsy using fluorescence spectroscopy for prostate cancer diagnosis - Wu, Binlin; Gao, Xin; Smith, Jason; Bailin, Jacob (Therapeutics and Diagnostics in Urology: Lasers, Robotics, Minimally Invasive, and Advanced Biomedical Devices, 2017)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using a multivariate analysis algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved weights of the components, e.g. NADH and FAD are used to estimate the relative concentrations of the native fluorophores and the redox ratio. A machine learning algorithm such as support vector machine (SVM) is used for classification to distinguish normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. The classification performance is shown based on statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve. A cross validation method such as leave-one-out is used to evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting.
Keywords: Artificial intelligence; Biopsy; Cross validation; Diseases; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Matrix algebra; Multivariant analysis; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Prostate cancers; Redox ratio; Robotics; Support vector machines; Tissue; Urology; cross validation; dept.phy; fluorescence spectroscopy; machine learning; nonnegative matrix factorization; optical biopsy; prostate cancer; redox ratio; support vector machine

Chemical composition of young stars in the leading arm of the Magellanic system - Zhang, Lan; Moni Bidin, Christian; Casetti-Dinescu, Dana I.; Méndez, Réne A.; Girard, Terrence M.; Korchagin, Vladimir I.; Vieira, Katherine; van Altena, William F.; Zhao, Gang (The Astrophysical Journal, 2017)
Chemical abundances of eight O- and B-type stars are determined from high-resolution spectra obtained with the MIKE instrument on the Magellan 6.5 m Clay telescope. The sample is selected from 42 candidates for membership in the Leading Arm (LA) of the Magellanic System. Stellar parameters are measured by two independent grids of model atmospheres and analysis procedures, confirming the consistency of the stellar parameter results. Abundances of seven elements (He, C, N, O, Mg, Si, and S) are determined for the stars, as are their radial velocities and estimates of distances and ages. Among the seven B-type stars analyzed, the five that have radial velocities compatible with membership of the LA have an average [Mg/H] of -0.42 ±0.16, significantly lower than the average of the remaining two, [Mg/H] = -0.07 ±0.06, which are kinematical members of the Galactic disk. Among the five LA members, four have individual [Mg/H] abundance compatible with that in the LMC. Within errors, we cannot exclude the possibility that one of these stars has an [Mg/H] consistent with the more metal-poor, SMC-like material. The remaining fifth star has an [Mg/H] close to Milky Way values. Distances to the LA members indicate that they are at the edge of the Galactic disk, while ages are of the order of ∼50-70 Myr, lower than the dynamical age of the LA, suggesting a single star-forming episode in the LA. V LSR of the LA members decreases with decreasing Magellanic longitude, confirming the results of previous LA gas studies. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Combinatorial screening of Pd-based quaternary electrocatalysts for oxygen reduction reaction in alkaline media - Li, Jinyang; Stein, Helge S.; Sliozberg, Kirill; Liu, Jingbei; Liu, Yanhui; Sertic, Genevieve; Scanley, Ellen; Ludwig, Alfred; Schroers, Jan; Schuhmann, Wolfgang; Taylor, André D. (Journal of Materials Chemistry, 2017)
The implementation of electrochemical systems such as fuel cells has been hindered by the slow development of low cost high activity catalysts. Here we examine the oxygen reduction reaction performance of a combinatorial Pd-Au-Ag-Ti thin film library using high-throughput screening and correlate the electrochemical behavior to the crystallographic properties. We find compositions of ca. 40-60 at% Pd and 30-35 at% Au exhibit both a low overpotential of close to the value of pure Pt as well as high current density. We also observe a volcano-like relationship between the overpotential and the solid formation strain. This study provides compositional guidance towards the future synthesis of nanostructured quaternary Pd-Au-Ag-Ti alloys and suggests the potential for broader application of high-throughput electrochemical characterization by means of an automatic scanning droplet cell. © The Royal Society of Chemistry.
Keywords: Catalyst activity; Combinatorial screenings; Crystallographic properties; Electrocatalysts; Electrochemical behaviors; Electrochemical characterizations; Electrochemical systems; Electrolytic reduction; Fuel cells; Gold; High current densities; High throughput screening; Oxygen reduction reaction; Reduction; Silver; Silver alloys; Throughput; Titanium alloys; dept.phy

Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy

Introducing an analytical solution and an improved one-factor gaussian copula model for the pricing of heterogeneous CDOs - Gao, Xin; Wu, Binlin; Schäfer, Tobias (International Journal of Financial Engineering, 2017)
This paper introduced an analytical solution and improved one-factor Gaussian copula models to the pricing of tranches of a Collateralized debt obligations (CDO) portfolio. Prices of CDO tranches are calculated and compared using the analytical model and different one-factor Gaussian copula models including a two-category heterogeneous model and a completely heterogeneous model that uses individual rate parameter and correlation coefficient for each reference entity in a CDO portfolio. When correlation among reference entities is low, the price calculated from the analytical model matches very well with the one-factor Gaussian copula models. However, as the correlation among reference entities increases, prices calculated using both the analytical solution and the homogeneous or two-category one-factor Gaussian copula models significantly deviate from the completely heterogeneous one-factor Gaussian copula model. This result verifies our belief that uniform parameters cannot completely capture all the heterogeneities in a CDO portfolio. Completely heterogeneous one-factor Gaussian copula model using individual rate parameters and correlation coefficients for each reference entities provides more reliable and accurate prices for structured securities.
Keywords: dept.phy

Carbon nanotube synthesis from block copolymer deposited catalyst - Woods, K; Silliman, J; Schwendemann, Todd C (International Journal of High Speed Electronics and Systems, 2017)
A block copolymer/metal-salt solution was used to deposit metal nanoparticles on substrates, from which carbon nanotubes (CNTs) were grown in a chemical vapor deposition (CVD) chamber. Mono and hybrid catalysts of Fe, Ni, and Co-nitrates were tested, and separately Co, Ni, and Cu-chlorides. In both cases cobalt/cobalt-hybrids produced the highest density of multi-wall carbon nanotubes (MWCNTs). Slight vertical growth, though sparse, was observed after growth at 800°C from a nickel catalyst on single-crystal aluminium oxide (~130nm diameter). © 2017 World Scientific Publishing Company.
Keywords: Aluminium oxide; Block copolymers; Carbon nanotube synthesis; Carbon nanotubes; Catalysts; Chemical vapor deposition; Chemical vapor depositions (CVD); Hybrid catalysts; Metal nanoparticles; Multiwalled carbon nanotubes (MWCN); Nanotubes; Nickel; Nickel catalyst; Vertical growth; Yarn; block copolymer; carbon nanotube; dept.phy; peer-reviewed

Quantitative characterization for identification of brain cancer surgical margin using resonance Raman spectroscopy - Zhou, Yan; Liu, Chenghui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhang, Chunyuan; Alfano, R R (OSA - The Optical Society, 2017)
A new criterion was developed to characterize brain tissue using resonance Raman spectroscopy, by which, negative margins of cancer can be differentiated from normal tissues. This method may help a surgeon better decide surgical margins. © OSA 2017.
Keywords: Brain cancer; Brain tissue; Diseases; Normal tissue; Quantitative characterization; Raman spectroscopy; Resonance Raman spectroscopy; Surgery; Tissue; dept.phy

Teaching Materials Science and Engineering (MSE) in the pre-college classroom as a vehicle for NGSS implementation - Granucci, Nicole; Jenkins, Carol; Bauer, Melanie; Gard, Ashley L.; Pinkerton, Bryn; Broadbridge, Christine (MRS Advances, 2017)
Adoption of Materials Science and Engineering (MSE) into the pre-college classroom is an ideal strategy for addressing Next Generation Science Standards (NGSS), specifically the Science and Engineering Practices. MSE offers core science and engineering topics that can be incorporated into existing Science, Technology, Engineering, and Mathematic (STEM) curricula through teaching modules. Using MSE as a teaching vehicle, the Center for Research on Interface Structures and Phenomena (CRISP) conducted a series of small-scale studies of its teacher professional development workshops and a student summer program, along with related teaching modules, in an effort to measure the contribution MSE has on students and K-12 STEM educators. Based on participant survey feedback, CRISP found improvement in students' MSE knowledge, interests, and career goals. For teachers, in addition to improving their MSE knowledge, they also increased their comfort and confidence in teaching MSE concepts in their classroom. These results provide evidence for the use of MSE modules as productive teaching tools for NGSS Science and Engineering Practices, as well as producing workforce-competitive STEM students. Copyright © Materials Research Society 2017.
Keywords: Aerogels; Curricula; Education; Government interactions; Interface structures; Materials science and engineering; STEM (science, technology, engineering and mathematics); Science , technology , engineering , and mathematics; Science and engineering; Science standards; Standards; Students; Surveys; Teacher professional development; Teaching; Teaching materials; aerogel; dept.phy; education; government interactions; peer-reviewed

A component‐by‐component characterisation of high‐risk atherosclerotic plaques by multiphoton microscopic imaging - Jain, Manu; Wu, Binlin; Pisapia, David J; Salvatore, Steven P; Mukherjee, Sushmita; Narula, Navneet; Mukherjee, Sushmita; Narula, Navneet (Journal of Microscopy, 2017)
Aims: Atherosclerotic plaques vulnerable to rupture are almost always inflamed, and carry a large lipid core covered by a thin fibrous cap. The other components may include neovascularisation, intraplaque haemorrhage and spotty calcification. In contrast, stable plaques are characterised by a predominance of smooth muscle cells and collagen, and lipid core is usually deep seated or absent. This study is a proof of principle experiment to evaluate the feasibility of multiphoton microscopy (MPM) to identify aforementioned plaque components. Methods and Results: MPM is a nonlinear optical technique that allows imaging based on intrinsic tissue signals including autofluorescence and higher-order scattering. In our study, MPM imaging was performed on morphologically diverse aortic and coronary artery plaques obtained during autopsy. Various histologically verified plaque components including macrophages, cholesterol crystals, haemorrhage, collagen and calcification were recognised by MPM. Conclusions: Recognition of the distinct signatures of various plaque components suggests that MPM has the potential to offer next-generation characterisation of atherosclerotic plaques. The higher lateral resolution (comparable to histology) images generated by MPM for identifying plaque components might complement larger field of view and greater imaging depth currently available with optical coherence tomography imaging. As the next step MPM would need to be evaluated for intact vessel imaging ex vivo and in vivo. © 2017 The Authors Journal of Microscopy © 2017 Royal Microscopical Society
Keywords: Aorta; Article; Atherosclerotic plaque; Calcinosis; Cholesterol; Collagen; Coronary Vessels; Hemorrhage; Humans; Image Processing, Computer-Assisted; Macrophages; Nonlinear Optical Microscopy; Plaque, Atherosclerotic; aorta; atherosclerotic plaque; autofluorescence; autopsy; bleeding; calcinosis; cholesterol; clinical article; collagen; coronary artery; coronary artery calcification; coronary blood vessel; dept.phy; ex vivo; ex vivo study; feasibility study; histopathology; human; human tissue; image processing; immunology; macrophage; macrophages; multiphoton microscopy; nonlinear optical microscopy; pathology; priority journal; procedures